Adaptive immune responses are larger and functionally preserved in a hypervaccinated individual - Kocher, Katharina; Moosmann, Carolin; Drost, Felix; Schülein, Christine; Irrgang, Pascal; Steininger, Philipp; Zhong, Jahn; Träger, Johannes; Spriewald, Bernd; Bock, Christoph; Busch, Dirk H.; Bogdan, Christian; et al. (Lancet Infectious Diseases, 2024)
CRIS-Team Scopus Importer:2024-03-29

A mutation within the SH2 domain of slp-76 regulates the tissue distribution and cytokine production of iNKT cells in mice - Danzer, Claudia Agnes; Koller, Anna; Baier, Julia; Arnold, Harald; Giessler, Claudia; Opoka, Robert; Schmidt, Stephanie; Willers, Maike; Mihai, Sidonia; Parsch, Hans; Wirtz, Stefan; Daniel, Christoph; et al. (European Journal of Immunology, 2016)
TCR ligation is critical for the selection, activation, and integrin expression of T lymphocytes. Here, we explored the role of the TCR adaptor protein slp-76 on iNKT-cell biology. Compared to B6 controls, slp-76(ace/ace) mice carrying a missense mutation (Thr428Ile) within the SH2-domain of slp-76 showed an increase in iNKT cells in the thymus and lymph nodes, but a decrease in iNKT cells in spleens and livers, along with reduced ADAP expression and cytokine response. A comparable reduction in iNKT cells was observed in the livers and spleens of ADAP-deficient mice. Like ADAP(-/-) iNKT cells, slp-76(ace/ace) iNKT cells were characterized by enhanced CD11b expression, correlating with an impaired induction of the TCR immediate-early gene Nur77 and a decreased adhesion to ICAM-1. Furthermore, CD11b-intrinsic effects inhibited cytokine release, concanavalin A-mediated inflammation, and iNKT-cell accumulation in the liver. Unlike B6 and ADAP(-/-) mice, the expression of the transcription factors Id3 and PLZF was reduced, whereas NP-1-expression was enhanced in slp-76(ace/ace) mice. Blockade of NP-1 decreased the recovery of iNKT cells from peripheral lymph nodes, identifying NP-1 as an iNKT-cell-specific adhesion factor. Thus, slp-76 contributes to the regulation of the tissue distribution, PLZF, and cytokine expression of iNKT cells via ADAP-dependent and -independent mechanisms.
EVALuna2:2050

Analysis of the antimicrobial activity of local anaesthetics used for dental analgesia - Pelz, Klaus; Wiedmann-Al-Ahmad, Margit; Bogdan, Christian; Otten, Jörg Elard (Journal of Medical Microbiology, 2008)
Seven local anaesthetics and their active anaesthetic components [Ultracaine D-S (articaine hydrochloride), Carbostesin (bupivacaine hydrochloride), Scandicaine (mepivacaine hydrochloride), Xylonest (prilocaine hydrochloride), Xylocaine (lidocaine hydrochloride), Hostacaine (butanilicaine phosphate) and Novocaine (procaine hydrochloride)] were tested for their antimicrobial activity against 311 bacterial strains from 52 different species and 14 Candida albicans strains. The tested pathogens were members of the oral flora, and partly members of the skin and intestinal flora. Additionally, the antimicrobial activity of methyl-4-hydroxybenzoate, sodium disulfite, adrenaline hydrogen tartrate and adrenaline (the preservative and vasoconstrictive components of the anaesthetics) was tested. For determination of MIC and minimal bactericidal concentration (MBC), the agar dilution method using Wilkins-Chalgren agar was applied. The trade preparation Ultracaine D-S showed the most prominent antimicrobial activity with regard to both MIC and MBC. Ultracaine D-S and its active substance, articaine hydrochloride, showed similar MIC values, suggesting that the antimicrobial activity is mainly caused by the anaesthetic component. Novocaine showed the lowest antimicrobial activity and did not inhibit 35 of the species tested. The MIC values of all local anaesthetics were between 0.25 and 16 mg ml-1. The routinely applied concentration of Ultracaine D-S was roughly four times higher, and of Hostacaine was two times higher, than the MBC values for the tested bacteria, whereas for the other anaesthetics, the MBC values were not reached or exceeded with the concentrations used. The MIC range of the preservatives was 0.5-1.0 mg ml -1 for methyl-4-hydroxybenzoate and 0.2-0.5 mg ml-1 for sodium disulfite. The articaine MIC values were two to three serial dilution steps lower, and the butanilicaine MIC values one to two serial dilution steps lower, than the MIC of the preservatives. The mepivacaine mean MIC values were slightly lower for Fusobacterium nucleatum, Prevotella intermedia, Porphyromonas gingivalis and Staphylococcus aureus, but higher for Streptococcus intermedius, compared with the preservative methyl-4-hydroxybenzoate. The same result was found with Streptococcus intermedius and lidocaine. Screening of 20 MIC values of 4 pure anaesthetic substances and the corresponding preservative found 2/20 instances where the MICs of the preservatives against 5 representative species (67 strains) were lower, indicating that the antimicrobial effect was mainly due to the preservative, but 18/20 results where the pure anaesthetic component showed greater antimicrobial effects compared with the preservative. The in vitro results for Carbostesin, Scandicaine and especially for Novocaine indicate that a local disinfection should be done prior to injection of the anaesthetics. Due to the results obtained with nosocomial strains (Escherichia coli, S. aureus and Pseudomonas), disinfection of the mucous membranes should be performed routinely in immunocompromised patients, regardless of the anaesthetic used. © 2008 SGM.
CRIS-Team Scopus Importer:2024-02-26

Anaplasma phagocytophilum Induces TLR- and MyD88-Dependent Signaling in In Vitro Generated Murine Neutrophils - Muller, Beate J.; Westheider, Arne; Birkner, Katharina; Seelig, Birte; Kirschnek, Susanne; Bogdan, Christian; Von Loewenich, Friederike D. (Frontiers in Cellular and Infection Microbiology, 2021)
Anaplasma phagocytophilum is a tick-transmitted obligate intracellular Gram-negative bacterium that replicates in neutrophils. It elicits febrile disease in humans and in animals. In a mouse model, elimination of A. phagocytophilum required CD4+ T cells, but was independent of IFN-γ and other classical antibacterial effector mechanisms. Further, mice deficient for immune recognition and signaling via Toll-like receptor (TLR) 2, TLR4 or MyD88 were unimpaired in pathogen control. In contrast, animals lacking adaptor molecules of Nod-like receptors (NLR) such as RIP2 or ASC showed delayed clearance of A. phagocytophilum. In the present study, we investigated the contribution of further pattern recognition receptor (PRR) pathways to the control of A. phagocytophilum in vivo. Mice deficient for the NLR NOD2 had elevated bacterial loads in the early phase of infection, but were unimpaired in pathogen elimination. In contrast, animals lacking adaptor proteins of different C-type lectin receptors (CLR) such as DAP12, Fc-receptor γ-chain (FcRγ) and SYK controlled A. phagocytophilum as efficiently as wild-type mice. Further, we investigated which PRR pathways are involved in the sensing of A. phagocytophilum by in vitro generated Hoxb8 murine neutrophils. In vitro, recognition of A. phagocytophilum by murine neutrophils was dependent on TLR- and MyD88 signaling. However, it remained intact in the absence of the NLR NOD1, NOD2 and NALP3 and of the CLR adaptor molecules DAP12 and FcRγ. From these results, we conclude that TLR rather than NLR or CLR are critical for the detection of A. phagocytophilum by neutrophils although in vivo defective TLR-signaling is compensated probably because of the redundancy of the immune system.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Anaplasma phagocytophilum; chemokine; CLR; cytokine; iNOS; MyD88; NLR; TLR

A Novel Thymoma-Associated Immunodeficiency with Increased Naive T Cells and Reduced CD247 Expression - Christopoulos, Petros; Dopfer, Elaine P.; Malkovsky, Miroslav; Esser, Philipp R.; Schaefer, Hans-Eckart; Marx, Alexander; Kock, Sylvia; Rupp, Nicole; Lorenz, Myriam R.; Schwarz, Klaus; Harder, Jan; Martin, Stefan F.; et al. (Journal of Immunology, 2015)
The mechanisms underlying thymoma-associated immunodeficiency are largely unknown, and the significance of increased blood ?? ? cells often remains elusive. In this study we address these questions based on an index patient with thymoma, chronic visceral leishmaniasis, myasthenia gravis, and a marked increase of rare ?? T cell subsets in the peripheral blood. This patient showed cutaneous anergy, even though he had normal numbers of peripheral blood total lymphocytes as well as CD4(+) and CD8(+) T cells. Despite his chronic infection, analyses of immunophenotypes and spectratyping of his lymphocytes revealed an unusual accumulation of naive ?? and ?? T cells, suggesting a generalized T cell activation defect. Functional studies in vitro demonstrated substantially diminished IL-2 and IFN-? production following TCR stimulation of his "untouched" naive CD4(+) T cells. Biochemical analysis revealed that his ?? and ?? T cells carried an altered TCR complex with reduced amounts of the ?-chain (CD247). No mutations were found in the CD247 gene that encodes the homodimeric ? protein. The diminished presence of CD247 and increased numbers of ?? T cells were also observed in thymocyte populations obtained from three other thymoma patients. Thus, our findings describe a novel type of a clinically relevant acquired T cell immunodeficiency in thymoma patients that is distinct from Good's syndrome. Its characteristics are an accumulation of CD247-deficient, hyporresponsive naive ?? and ?? T cells and an increased susceptibility to infections.
EVALuna2:7674

A randomized controlled phase IIb wound healing trial of cutaneous leishmaniasis ulcers with 0.045% pharmaceutical chlorite (DAC N-055) with and without bipolar high frequency electro-cauterization versus intralesional antimony in Afghanistan - Stahl, Hans-Christian; Ahmadi, Faridullah; Schleicher, Ulrike; Sauerborn, Rainer; Bermejo, Justo Lorenzo; Amirih, Mohammed Latif; Sakhayee, Ibrahim; Bogdan, Christian; Stahl, Kurt-Wilhelm (BMC Infectious Diseases, 2014)
A previously published proof of principle phase IIa trial with 113 patients from Kabul showed that bipolar high-frequency (HF) electro-cauterization (EC) of cutaneous leishmaniasis (CL) ulcers and subsequent moist wound treatment (MWT) closed 85% of all Leishmania (L.) tropica lesions within 60 days.A three-armed phase IIb, randomized and controlled clinical trial was performed in Mazar-e-Sharif. L. tropica- or L. major-infected CL patients received intradermal sodium stibogluconate (SSG) (Group I); HF-EC followed by MWT with 0.045% DAC N-055 (Group II); or MWT with 0.045% DAC N-055 in basic crème alone (Group III). The primary outcome was complete epithelialisation before day 75 after treatment start.87 patients enrolled in the trial were randomized into group I (n = 24), II (n = 32) and III (n = 31). The per-protocol analysis of 69 (79%) patients revealed complete epithelialisation before day 75 in 15 (of 23; 65%) patients of Group I, in 23 (of 23; 100%) patients of Group II, and in 20 (of 23; 87%) patients of Group III (p = 0.004, Fisher's Exact Test). In the per-protocol analysis, wound closure times were significantly different between all regimens in a pair-wise comparison (p = 0.000039, Log-Rank (Mantel-Cox) test). In the intention-to-treat analysis wound survival times in Group II were significantly different from those in Group I (p = 0.000040, Log-Rank (Mantel-Cox) test). Re-ulcerations occurred in four (17%), three (13%) and seven (30%) patients of Group I, II or III, respectively (p = 0.312, Pearson Chi-Square Test).Treatment of CL ulcers with bipolar HF-EC followed by MWT with 0.045% DAC N-055 or with DAC N-055 alone showed shorter wound closure times than with the standard SSG therapy. The results merit further exploration in larger trials in the light of our current knowledge of in vitro and in vivo activities of chlorite. Clinicaltrials.gov ID: NCT00996463. Registered: 15th October 2009.
EVALuna2:7639

Arginase 1 of myeloid cells accounts for disease chronicity in Leishmania mexicana-infected mice - Rai, Baplu; Debus, Andrea; Liang Chunguang; Kunz, Meik; Rauh, Manfred; Bogdan, Christian; Schleicher, Ulrike (EUROPEAN JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2022-03-11

Arginase expression impedes the resolution of intestinal inflammation by altering the fecal microbiome and the metabolome - Baier, Julia; Gänsbauer, Maximilian; Giessler, Claudia; Arnold, Harald; Muske, Mercedes; Schleicher, Ulrike; Lukassen, Sören; Ekici, Arif Bülent; Rauh, Manfred; Daniel, Christoph; Hartmann, Arndt; Schmid, Benjamin; et al. (Journal of Clinical Investigation, 2020)
Arginase 1 (Arg1), which converts L-arginine into ornithine and urea, exerts pleiotropic immunoregulatory effects. However, the function of Arg1 in inflammatory bowel disease (IBD) remains poorly characterized. Here, we found that Arg1 expression correlated with the degree of inflammation in intestinal tissues from IBD patients. In mice, Arg1 was upregulated in an IL-4-/IL-13- and intestinal microbiota-dependent manner. Tie2-Cre+/-Arg1fl/fl mice lacking Arg1 in hematopoietic and endothelial cells recovered faster from experimental colitis than Arg1-expressing littermates. This correlated with decreased vessel density, compositional changes in intestinal microbiota, diminished infiltration by myeloid cells and an accumulation of intraluminal polyamines that promote epithelial healing. The pro-resolving effect of Arg1-deletion was reduced by an L-arginine-free diet, but rescued by simultaneous deletion of other L-arginine-metabolizing enzymes such as Arg2 or Nos2, demonstrating that protection from colitis requires L-arginine. Fecal microbiota transfers from Tie2-Cre+/-Arg1fl/fl mice into wild-type recipients ameliorated intestinal inflammation while transfers from wild-type littermates into Arg1-deficient mice prevented an advanced recovery from colitis. Thus, an increased availability of L-arginine as well as altered intestinal microbiota and metabolic products account for the accelerated resolution from colitis in the absence of Arg1. Consequently, the metabolism of L-arginine may serve as target for clinical intervention in IBD patients.<br

Aspergillus fumigatus Spores Are Not Able to Penetrate Silicone Breast Implant Shells - Horch, Raymund E.; Krappmann, Sven; Duemig, Michaela; Schmitz, Marweh; Kengelbach-Weigand, Annika; Schubert, Dirk W.; Kremser, Thomas; Bogdan, Christian; Ludolph, Ingo (Annals of Plastic Surgery, 2019)
Bacterial contamination is hypothesized to be one reason for the development of capsular contracture after alloplastic breast reconstruction using silicone breast implants. The role of fungal colonization or infection in this context as well as the question if microorganisms can penetrate the shell of silicone breast implants remains an unresolved question to date. Therefore, the aim of this study was to assess whether fungal spores are able to penetrate the shell of silicone implants. In an experimental in vitro setup with different arrangements of growth compartments, silicone chambers were placed in culture dishes filled with Aspergillus minimal medium or liquid culture medium. Inoculation was performed with conidia of Aspergillus fumigatus and incubated for seven days. On a daily basis, plates were inspected for conidial germination and hyphal growth. In none of the different experimental settings nutrients or hyphae of Aspergillus fumigatus were able to penetrate the silicone material.ConclusionsFungal spores and hyphae do not permeate through an intact silicone shell used in breast implants; thus, the silicone material serves as an impenetrable barrie
Keywords: Aspergillus fumigatus; penetration; silicone implants; breast

A spinal epidural abscess due to Streptobacillus moniliformis infection following a rat bite: case report - Hammer, Alexander; Wolff, Dorit; Geißdörfer, Walter; Schrey, Michael; Ziegler, Renate; Steiner, Hans-Herbert; Bogdan, Christian (Journal of Neurosurgery-Spine, 2017)
The authors describe the case of a 40-year-old man suffering from an epidural abscess in the thoracic spine due to a rarely isolated pathogen, Streptobacillus moniliformis, the causative agent of rat bite fever. Besides diffuse abdominal pain, ataxia, paresthesia, hypesthesia, and enhanced reflexes of the lower extremities, the patient suffered from a decreased sensation of bladder filling. His history was also positive for a rat bite 6 weeks earlier. Magnetic resonance imaging showed an epidural, space-occupying lesion compressing the spinal cord at the vertebral levels of T6-8. Neurosurgery revealed an epidural abscess, which was drained via laminectomy (T-7) and excision of the ligamentum flavum (T6-8). The etiological agent S. moniliformis was identified by 16S rRNA-based polymerase chain reaction and sequencing as well as by culture and mass spectrometry. Treatment with penicillin G led to complete resolution of the abscess and clinical recovery of the patient, who regained his bladder-filling sensation and free walking ability. This case demonstrates that careful attention to the patient's history is essential in suspecting unusual bacterial pathogens as the cause of an epidural abscess and initiating the optimal diagnostic procedure and antimicrobial therapy.
EVALuna2:7753

Background Paper for the update of meningococcal vaccination recommendations in Germany: use of the serogroup B vaccine in persons at increased risk for meningococcal disease - Hellenbrand, Wiebke; Koch, Judith; Harder, Thomas; Bogdan, Christian; Heininger, Ulrich; Tenenbaum, Tobias; Terhardt, Martin; Vogel, Ulrich; Wichmann, Ole; Von Kries, Ruediger (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2015)
In December 2013 Bexsero® became available in Germany for vaccination against serogroup B meningococci (MenB). In August 2015 the German Standing Committee on Vaccination (STIKO) endorsed a recommendation for use of this vaccine in persons at increased risk of invasive meningococcal disease (IMD). This background paper summarizes the evidence underlying the recommendation. Bexsero® is based on surface protein antigens expressed by about 80% of circulating serogroup B meningococci in Germany. The paper reviews available data on immunogenicity and safety of Bexsero® in healthy children and adolescents; data in persons with underlying illness and on the effectiveness in preventing clinical outcomes are thus far unavailable.STIKO recommends MenB vaccination for the following persons based on an individual risk assessment: (1) Persons with congenital or acquired immune deficiency or suppression. Among these, persons with terminal complement defects and properdin deficiency, including those under eculizumab therapy, are at highest risk with reported invasive meningococcal disease (IMD) incidences up 10,000-fold higher than in the general population. Persons with asplenia were estimated to have a 20-30-fold increased risk of IMD, while the risk in individuals with other immune defects such as HIV infection or hypogammaglobulinaemia was estimated at no more than 5-10-fold higher than the background risk. (2) Laboratory staff with a risk of exposure to N. meningitidis aerosols, for whom an up to 271-fold increased risk for IMD has been reported. (3) Unvaccinated household (-like) contacts of a MenB IMD index case, who have a roughly 100-200-fold increased IMD risk in the year after the contact despite chemoprophylaxis. Because the risk is highest in the first 3 months and full protective immunity requires more than one dose (particularly in infants and toddlers), MenB vaccine should be administered as soon as possible following identification of the serogroup of the index case.
EVALuna2:7680

Background paper to the updated pneumococcal vaccination recommendation for older adults in Germany - Falkenhorst, G.; Remschmidt, C.; Harder, T.; Wichmann, O.; Glodny, S.; Hummers-Pradier, E.; Ledig, T.; Bogdan, Christian (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2016)
EVALuna2:7725

Bacterial coinfection restrains antiviral CD8 T-cell response via LPS-induced inhibitory NK cells - Straub, Tobias; Freudenberg, Marina A.; Schleicher, Ulrike; Bogdan, Christian; Gasteiger, Georg; Pircher, Hanspeter (Nature Communications, 2018)
Infection of specific pathogen-free mice with lymphocytic choriomeningitis virus (LCMV) is a widely used model to study antiviral T-cell immunity. Infections in the real world, however, are often accompanied by coinfections with unrelated pathogens. Here we show that in mice, systemic coinfection with E. coli suppresses the LCMV-specific cytotoxic T-lymphocyte (CTL) response and virus elimination in a NK cell- and TLR2/4-dependent manner. Soluble TLR4 ligand LPS also induces NK cell-mediated negative CTL regulation during LCMV infection. NK cells in LPS-treated mice suppress clonal expansion of LCMV-specific CTLs by a NKG2D- or NCR1-independent but perforin-dependent mechanism. These results suggest a TLR4-mediated immunoregulatory role of NK cells during viral-bacterial coinfections.
EVALuna2:36425

Biomimetic Magnetic Particles for the Removal of Gram-Positive Bacteria and Lipoteichoic Acid. - Friedrich, Bernhard; Eichermüller, Julia; Bogdan, Christian; Cunningham, Sarah; Hackstein, Holger; Strauss, Richard; Alexiou, Christoph; Lyer, Stefan; Tietze, Rainer (Pharmaceutics, 2022)
Gram+ bacteria are very common in clinical medicine and responsible for a large number of infectious diseases. For example, Gram+ bacteria play a major role in causing bloodstream infections and sepsis. Therefore, the detection of Gram+ bacteria is of great importance for the diagnosis and treatment of infectious diseases. Furthermore, these bacteria are often present in biofilms that cover implants. Recent research work has mainly focused on the biologic activity and removal of Gram-negative bacteria or bacterial components such as lipopolysaccharides (LPS). In contrast, the effects of lipoteichoic acid (LTA) have been less well studied so the relevance of their removal from body fluids is possibly underestimated. To address this topic, we evaluated superparamagnetic iron oxide particles (SPION) carrying different peptides derived from the innate immune receptor (GP-340) for their ability to bind and remove Gram+ bacteria and LTA from different media. Our results show that, beyond S. aureus, effective agglutinating and removing of S. pneumoniae was possible. Furthermore, we were able to show for the first time that this was possible with LTA alone and that the magnetic removal of bacteria was also efficient under flow conditions. We also found that this method was able to capture Stapyhylococcus aureus from platelet concentrates, which can help to enhance the sensitivity of microbiological diagnostics, quality control measures, and blood product safety.
EVALuna2:508460

Case report: Cutaneous pseudolymphoma caused by a Leishmania infantum infection in a patient treated with anti-TNF antibody for plaque psoriasis - Scholl, Sarah; Schuster, Daniel; Technau-Hafsi, Kristin; Stete, Katarina; Rieg, Siegbert; May, Annette M.; Bogdan, Christian; Schauer, Franziska (Frontiers in Medicine, 2022)
For psoriasis, which affects up to 2% of the population and adalimumab is approved from the age of 4 years. Here, we present a middle-aged Italian man with long-term history of plaque psoriasis and psoriasis arthropathica and adalimumab therapy. He developed ulcers or nodules within the psoriatic plaques, resembling cutaneous infection with Leishmania infantum. TNF and other cytokines such as IL-12 and IFN-γ are central in the early control of the infection. Discontinuation of the anti-TNF-treatment resolved the infection without specific therapy.
CRIS-Team Scopus Importer:2022-12-30
Keywords: adalimumab; anti-TNF therapy; cutaneous leishmaniasis; skin pseudolymphoma; skin ulceration

Case Report: Local Treatment of a Leishmania tropica Infection in a Syrian Child with a Novel Filmogenic Preparation of Pharmaceutical Sodium Chlorite (LeiProtect®) - Debus, Dirk; Genç, Semra; Kurz, Philipp; Holzer, Martin; Bauer, Kurt; Heimke-Brinck, Ralph; Baier, Martin; Sebald, Heidi; Debus, Andrea; Bogdan, Christian; Stahl, Kurt Wilhelm (American Journal of Tropical Medicine and Hygiene, 2022)
Cutaneous leishmaniasis (CL) frequently entails chronic skin lesions that heal only slowly. Until now, the available therapeutic options are very limited. Here, we present a case of a 5½-year-old Syrian refugee with two progressive lower-leg skin ulcers caused by Leishmania tropica. The patient received topical treatment with LeiProtect®, a newly developed, hydroxypropylcellulose-based, filmogenic gel containing nontoxic concentrations of pharmaceutical sodium chlorite. The skin lesions completely healed within 8 weeks and did not relapse during 1 year of follow-up, underlining the efficacy of this novel local therapy of CL.
CRIS-Team Scopus Importer:2022-04-01

CD101 inhibits the expansion of colitogenic T cells - Schey, Regina; Dornhoff, H.; Baier, J. L. C.; Purtak, M.; Opoka, R.; Koller, A. K.; Atreya, Raja; Rau, Tilman; Daniel, Christoph; Amann, Kerstin Ute; Bogdan, Christian; Mattner, Jochen (Mucosal Immunology, 2016)
CD101 exerts negative-costimulatory effects in vitro, but its function in vivo remains poorly defined. CD101 is abundantly expressed on lymphoid and myeloid cells in intestinal tissues, but absent from naïve splenic T cells. Here, we assessed the impact of CD101 on the course of inflammatory bowel disease (IBD). Using a T-cell transfer model of chronic colitis, we found that in recipients of naïve T cells from CD101(+/+) donors up to 30% of the recovered lymphocytes expressed CD101, correlating with an increased interleukin (IL)-2-mediated FoxP3 expression. Transfer of CD101(-/-) T cells caused more severe colitis and was associated with an expansion of IL-17-producing T cells and an enhanced expression of IL-2R?/? independently of FoxP3. The co-transfer of naïve and regulatory T cells (Treg) protected most effectively from colitis, when both donor and recipient mice expressed CD101. Although the expression of CD101 on T cells was sufficient for Treg-function and the inhibition of T-cell proliferation, sustained IL-10 production required additional CD101 expression by myeloid cells. Finally, in patients with IBD a reduced CD101 expression on peripheral and intestinal monocytes and CD4(+) T cells correlated with enhanced IL-17 production and disease activity. Thus, CD101 deficiency is a novel marker for progressive colitis and potential target for therapeutic intervention.
EVALuna2:2051

Cell type-specific modulation of metabolic, immune-regulatory, and anti-microbial pathways by CD101 - Wrage, Marius; Holland, Tim; Nüse, Björn; Kaltwasser, Johanna; Fröhlich, Jessica; Arnold, Harald; Gießler, Claudia; Flamann, Cindy; Bruns, Heiko; Berges, Johannes; Daniel, Christoph; Hoffmann, Markus; et al. (Mucosal Immunology, 2024)
T lymphocytes and myeloid cells express the immunoglobulin-like glycoprotein cluster of differentiation (CD)101, notably in the gut. Here, we investigated the cell-specific functions of CD101 during dextran sulfate sodium (DSS)-induced colitis and Salmonella enterica Typhimurium infection. Similar to conventional CD101−/− mice, animals with a regulatory T cell-specific Cd101 deletion developed more severe intestinal pathology than littermate controls in both models. While the accumulation of T helper 1 cytokines in a CD101-deficient environment entertained DSS-induced colitis, it impeded the replication of Salmonella as revealed by studying CD101−/− x interferon-g−/− mice. Moreover, CD101-expressing neutrophils were capable to restrain Salmonella infection in vitro and in vivo. Both cell-intrinsic and -extrinsic mechanisms of CD101 contributed to the control of bacterial growth and spreading. The CD101-dependent containment of Salmonella infection required the expression of Irg-1 and Nox2 and the production of itaconate and reactive oxygen species. The level of intestinal microbial antigens in the sera of inflammatory bowel disease patients correlated inversely with the expression of CD101 on myeloid cells, which is in line with the suppression of CD101 seen in mice following DSS application or Salmonella infection. Thus, depending on the experimental or clinical setting, CD101 helps to limit inflammatory insults or bacterial infections due to cell type-specific modulation of metabolic, immune-regulatory, and anti-microbial pathways.
CRIS-Team Scopus Importer:2024-07-19

Characterization of the Protein Tyrosine Phosphatase LmPRL-1 Secreted by Leishmania major via the Exosome Pathway - Leitherer, Sabine; Clos, Joachim; Liebler-Tenorio, Elisabeth M.; Schleicher, Ulrike; Bogdan, Christian; Soulat, Didier (Infection and Immunity, 2017)
Similar to other intracellular pathogens, Leishmania parasites are known to evade the antimicrobial effector functions of host immune cells. To date, however, only a few virulence factors have been described for Leishmania major, one of the causative agents of cutaneous leishmaniasis. Here, we have characterized the expression and function of an L. major phosphatase, which we termed LmPRL-1. This enzyme shows a strong structural similarity to the human phosphatases of regenerating liver (PRL-1, -2, and -3) that regulate the proliferation, differentiation, and motility of cells. The biochemical characterization of the L. major phosphatase revealed that the enzyme is redox sensitive. When analyzing the subcellular localization of LmPRL-1 in promastigotes, amastigotes, and infected macrophages, we found that the phosphatase was predominantly expressed and secreted by promastigotes via the exosome route. Finally, we observed that ectopic expression of LmPRL-1 in L. major led to an increased number of parasites in macrophages. From these data, we conclude that the L. major phosphatase LmPRL-1 contributes to the intracellular survival of the parasites in macrophages.
EVALuna2:7751

Chronic mycobacterial infection induces an immune suppressive microenvironment altering dendritic cell function - Merga, K. A.; Schleicher, Ulrike; Bogdan, Christian; Weiss, S.; Goethe, R. (2018)
EVALuna2:212766

Chronic Systemic Infection of Mice with Leishmania infantum Leads to Increased Bone Mass - Lai, Chaobo; Heinemann, Jennifer; Schleicher, Ulrike; Schett, Georg; Bogdan, Christian; Bozec, Aline; Soulat, Didier (Journal of Bone and Mineral Research, 2022)
Vector-borne infections of humans with the protozoan parasite Leishmania (L.) infantum can cause a systemic and potentially lethal disease termed visceral leishmaniasis. In the corresponding mouse model, an intravenous infection with L. infantum leads to the persistence of parasites in various organs, including bone marrow (BM). Considering the anatomical proximity between the BM and the cortical bone, we investigated whether a chronic infection with L. infantum affected bone homeostasis. Unexpectedly, chronic infection with L. infantum caused an increase in bone mass in mice. In vivo, an increased number of osteoblasts and osteocytes and a decreased maturation of osteoclasts characterized the phenotype. Confocal laser scanning fluorescence microscopy confirmed the infection of BM macrophages but also revealed the presence of parasites in osteoclasts. In vitro, mature osteoclasts took up L. infantum parasites. However, infection of osteoclast progenitors abolished their differentiation and function. In addition, secretory products of infected BM-derived macrophages inhibited the maturation of osteoclasts. Both in vitro and in vivo, infected macrophages and osteoclasts showed an enhanced expression of the anti-osteoclastogenic chemokine CCL5 (RANTES). Neutralization of CCL5 prevented the inhibition of osteoclast generation seen in the presence of culture supernatants from L. infantum-infected macrophages. Altogether, our study shows that chronic infection with Leishmania increases bone mass by inducing bone formation and impairing osteoclast differentiation and function. (c) 2022 American Society for Bone and Mineral Research (ASBMR).
CRIS-Team WoS Importer:2022-12-02

Class switch towards non-inflammatory, spike-specific IgG4 antibodies after repeated SARS-CoV-2 mRNA vaccination - Irrgang, Pascal; Gerling, Juliane; Kocher, Katharina; Lapuente, Dennis; Steininger, Philipp; Habenicht, Katharina Marie; Wytopil, Monika; Beileke, Stephanie; Schäfer, Simon; Zhong, Jahn; Ssebyatika, George; Krey, Thomas; et al. (Science immunology, 2022)
RNA vaccines are efficient preventive measures to combat the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. High levels of neutralizing SARS-CoV-2 antibodies are an important component of vaccine-induced immunity. Shortly after the initial two mRNA vaccine doses, the immunoglobulin G (IgG) response mainly consists of the proinflammatory subclasses IgG1 and IgG3. Here, we report that several months after the second vaccination, SARS-CoV-2–specific antibodies were increasingly composed of noninflammatory IgG4, which were further boosted by a third mRNA vaccination and/or SARS-CoV-2 variant breakthrough infections. IgG4 antibodies among all spike-specific IgG antibodies rose, on average, from 0.04% shortly after the second vaccination to 19.27% late after the third vaccination. This induction of IgG4 antibodies was not observed after homologous or heterologous SARS-CoV-2 vaccination with adenoviral vectors. Single-cell sequencing and flow cytometry revealed substantial frequencies of IgG4-switched B cells within the spike-binding memory B cell population [median of 14.4%; interquartile range (IQR) of 6.7 to 18.1%] compared with the overall memory B cell repertoire (median of 1.3%; IQR of 0.9 to 2.2%) after three immunizations. This class switch was associated with a reduced capacity of the spike-specific antibodies to mediate antibody-dependent cellular phagocytosis and complement deposition. Because Fc-mediated effector functions are critical for antiviral immunity, these findings may have consequences for the choice and timing of vaccination regimens using mRNA vaccines, including future booster immunizations against SARS-CoV-2.<br

Clinical complexity of Leishmania (Viannia) braziliensis infections amongst travelers - Eichner, Saskia; Thoma-Uszynski, Sybille; Herrgott, Ilka; Sebald, Heidi; Debus, Andrea; Tsianakas, Athanasios; Ehrchen, Jan; Harms, Gundel; Simon, Miklos; Sunderkoetter, Cord; Bogdan, Christian (European Journal of Dermatology, 2013)
The protozoan parasite Leishmania (Viannia) braziliensis is one of the main causes of cutaneous and mucocutaneous leishmaniasis in South America. Here, we describe three cases of L. (V.) braziliensis infection which were acquired during travelling in Bolivia, Peru or Paraguay and illustrate the phenotypic heterogeneity and therapeutic complexity of the disease. Two patients presented with unusual clinical manifestations, i.e. with prominent regional lymphadenopathy ("bubonic leishmaniasis") and with simultaneously emerged skin and mucosal lesions, respectively. Both patients insufficiently responded to oral treatment with miltefosine; resolution of the lesions was only achieved after a course of intravenous liposomal amphotericin B. Key words cutaneous leishmaniasis, mucosal leishmaniasis, Leishmania (V.) braziliensis.
CRIS-Team Scopus Importer:2024-02-26
Keywords: cutaneous leishmaniasis; mucosal leishmaniasis; Leishmania (V.) braziliensis

Clinical Manifestation of Cutaneous Leishmaniasis Following a Mechanical Trauma - Busch, Dorothee; Bogdan, Christian; Erfurt-Berge, Cornelia (International Journal of Lower Extremity Wounds, 2020)
Unusual skin ulcers frequently represent a diagnostic challenge. When the most common disease entities such as arterial, venous or diabetic ulcers have been excluded, the question of further differential diagnoses and procedures arises. Other possible causes include chronic inflammatory diseases, neoplasia, self-inflicted wounds, primary infectious diseases and physical/chemical damage to the skin. To narrow down the differential diagnoses, a detailed history of the patient is essential, which also needs to include events further back in time.
CRIS-Team Scopus Importer:2020-11-13
Keywords: delayed diagnosis; leg ulcer; leishmaniasis; trauma

Comment on: “New recommendation on yellow fever booster vaccination in Germany” - Kling, Kerstin; Domingo, Cristina; Bogdan, Christian; Mertens, Thomas; Wolff, Robert; Wiedermann, Ursula (Travel Medicine and Infectious Disease, 2023)
CRIS-Team Scopus Importer:2023-04-14

Comment on "TLR9-dependent activation of dendritic cells by DNA from Leishmania major favors Th1 cell development and the resolution of lesions" - Bogdan, Christian; Schleicher, Ulrike (Journal of Immunology, 2009)
CRIS-Team Scopus Importer:2024-02-26

Comparative Analysis of the Euroimmun CXCL13 Enzyme-Linked Immunosorbent Assay and the ReaScan Lateral Flow Immunoassay for Diagnosis of Lyme Neuroborreliosis - Ziegler, Katharina; Rath, Anca; Schoerner, Christoph; Meyer, Renate; Bertsch, Thomas; Erbguth, Frank; Bogdan, Christian; Steinmann, Jörg; Held, Jürgen (Journal of Clinical Microbiology, 2020)
Diagnosis of Lyme neuroborreliosis (LNB) is challenging, as long as Borrelia-specific intrathecal antibodies are not yet detectable. The chemokine CXCL13 is elevated in the cerebrospinal fluid (CSF) of LNB patients. Here, we compared the performances of the Euroimmun CXCL13 enzyme-linked immunosorbent assay (CXCL13 ELISA) and the ReaScan CXCL13 lateral flow immunoassay (CXCL13 LFA), a rapid point-of-care test, to support the diagnosis of LNB. In a dual-center case-control study, CSF samples from 90 patients (34 with definite LNB, 10 with possible LNB, and 46 with other central nervous system [CNS] diseases [non-LNB group]) were analyzed with the CXCL13 ELISA and the CXCL13 LFA. Classification of patients followed the European Federation of Neurological Societies (EFNS) guidelines on LNB. The CXCL13 ELISA detected elevated CXCL13 levels in all patients with definite LNB (median, 1,409 pg/ml) compared to the non-LNB controls (median, 20.7 pg/ml; P < 0.0001), with a sensitivity of 100% and a specificity of 84.8% (cutoff value, 78.6 pg/ml; area under the receiver operating characteristic [ROC] curve, 0.93). Similarly, the CXCL13 LFA yielded elevated CXCL13 levels in 31 patients with definite LNB (median arbitrary value, 223.5) compared to the non-LNB control patients (median arbitrary value, 0; P < 0.0001) and had a sensitivity and specificity of 91.2% and 93.5%, respectively (cutoff arbitrary value, 22.5; area under the ROC curve, 0.94). The correlation between the CXCL13 levels obtained by ELISA and LFA was strong (Spearman correlation coefficient r = 0.89; P < 0.0001). The CXCL13 ELISA and the CXCL13 LFA are comparable diagnostic tools for the detection of CXCL13 in the CSF of patients with definite LNB. The advantage of the CXCL13 LFA is the shorter time to result.
CRIS-Team Scopus Importer:2020-09-04
Keywords: biomarker; Borrelia burgdorferi; CSF; Lyme disease; meningitis; neuroborreliosis

Comparative Analysis of the Wako β-Glucan Test and the Fungitell Assay for Diagnosis of Candidemia and Pneumocystis jirovecii Pneumonia - Friedrich, Ricarda; Rappold, Elfriede; Bogdan, Christian; Held, Juergen (Journal of Clinical Microbiology, 2018)
(1→3)-β-d-Glucan (BDG) is a biomarker for invasive fungal disease. Until now, all BDG data in the Western Hemisphere were obtained using the Fungitell assay (FA). How it compares to the Wako β-glucan test (GT), which was recently launched in Europe, is largely unknown. We conducted a case-control study to compare the two assays in serum samples from 120 candidemia and 63 Pneumocystis jirovecii pneumonia (PCP) patients. Two hundred patients with bacteremia or negative blood cultures served as candidemia control group. In patients with candidemia the median BDG values of the FA and the GT were 351 and 8.4 pg/ml, respectively. With both assays, the BDG levels in candidemia were significantly higher than those measured in the control group (P < 0.001). The sensitivity, specificity, and positive and negative predictive values for the diagnosis of candidemia were 86.7%, 85.0%, 6.0%, and 99.8% for the FA and 42.5%, 98.0%, 19.0%, and 99.4% for the GT, respectively. In PCP patients the median BDG values of the FA and the GT were 963 and 57.7 pg/ml, respectively. The sensitivities for PCP diagnosis were 100% for the FA and 88.9% for the GT. In practical terms, the GT proved to be robust and applicable for testing single samples, whereas for economic reasons the FA required the samples to be tested in batch. The sensitivity of the FA is superior to that of the GT. However, the GT is a valuable alternative to the FA, especially for patients with suspected PCP and in laboratories with low sample throughput.
EVALuna2:34508

Conventional non-woven vs. novel nano FFP2 masks - a competetive study on the filtration performance after various types of conditions - Halamicek, Robin; Wiesmann, Carolin; Kröner, Richard; Bogdan, Christian; Schubert, Dirk W. (Nordic Polymer Days, 2023)
Filtering face piece (FFP) masks, categorized by different filtration efficiency standards, are mandatory to achieve an efficient protection against viruses like the severe acute respirato- ry syndrome coronavirus type 2 (SARS-CoV-2) [1]. They conventionally comprise an electro- statically treated melt blown non-woven layer as the main filtering medium if the standard is FFP2. However, novel nanofibrous masks with the same standard are arising on the market, promising a higher safety alongside a high- er better wearing comfort – but for a higher unit price. This study compared different mask models from both mask types regard- ing their filtration performance after various types of conditions (change of temperature and air humidity, exposure to isopropyl al- cohol (IPA) and an autoclave sterilization) to evaluate the superior FFP2 mask type. Due to the absence of prior electrostatic treatment, the nanofibrous masks did not show a signi- ficant change in filtration efficiency when exposed to IPA, unlike to the melt blown non-woven masks. However, most melt blown type masks maintained a sufficient filtration efficiency after all other treatments and also at the untreated condition – with even better results than the nanofibrous competitors. This applied particulary for the capacity to filter smallest particles/droplets with a size of around 0.1 μm, which is below the range of typical filtering standards but important for the retention of virally contaminated nano- aerosols or unattached viruses [2-4]. Based on their better filtration performance, lower price and potential reusability, it can be concluded that conventional melt blown non-woven masks with an electrostatic treatment are the preferable FFP2 mask type for a protective purpo

Correction to: Diagnostic performance of four SARS-CoV-2 antibody assays in patients with COVID-19 or with bacterial and non-SARS-CoV-2 viral respiratory infections (European Journal of Clinical Microbiology & Infectious Diseases, (2021), 10.1007/s10096-021-04285-4) - Huber, Timo; Steininger, Philipp; Irrgang, Pascal; Korn, Klaus; Tenbusch, Matthias; Diesch, Katharina; Achenbach, Susanne; Kremer, Andreas; Werblow, Marissa; Vetter, Marcel; Bogdan, Christian; Held, Jürgen (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
In the originally published version of the article, captions of Figures 1, 2, 3, 4, and 5 have missing figure denominations. The figures are presented here with correct captions. Layout adjustments are also made to Tables 2-5 for readability. The original article has been corrected. (Figure presented.).
CRIS-Team Scopus Importer:2021-07-30

Cytokine-Mediated Regulation of ARG1 in Macrophages and Its Impact on the Control of Salmonella enterica Serovar Typhimurium Infection - Brigo, Natascha; Pfeifhofer-Obermair, Christa; Tymoszuk, Piotr; Demetz, Egon; Engl, Sabine; Barros-Pinkelnig, Marina; Dichtl, Stefanie; Fischer, Christine; Valente De Souza, Lara; Petzer, Verena; Von Raffay, Laura; Hilbe, Richard; et al. (Cells, 2021)
Arginase 1 (ARG1) is a cytosolic enzyme that cleaves L-arginine, the substrate of inducible nitric oxide synthase (iNOS), and thereby impairs the control of various intracellular pathogens. Herein, we investigated the role of ARG1 during infection with Salmonella enterica serovar Typhimurium (S.tm). To study the impact of ARG1 on Salmonella infections in vitro, bone marrow-derived macrophages (BMDM) from C57BL/6N wild-type, ARG1-deficient Tie2Cre(+/-)ARG1(fl/fl) and NRAMP(G169) C57BL/6N mice were infected with S.tm. In wild-type BMDM, ARG1 was induced by S.tm and further upregulated by the addition of interleukin (IL)-4, whereas interferon-gamma had an inhibitory effect. Deletion of ARG1 did not result in a reduction in bacterial numbers. In vivo, Arg1 mRNA was upregulated in the spleen, but not in the liver of C57BL/6N mice following intraperitoneal S.tm infection. The genetic deletion of ARG1 (Tie2Cre(+/-)ARG1(fl/fl)) or its pharmacological inhibition with CB-1158 neither affected the numbers of S.tm in spleen, liver and blood nor the expression of host response genes such as iNOS, IL-6 or tumour necrosis factor (TNF). Furthermore, ARG1 was dispensable for pathogen control irrespective of the presence or absence of the phagolysosomal natural resistance-associated macrophage protein 1 (NRAMP1). Thus, unlike the detrimental function of ARG1 seen during infections with other intraphagosomal microorganisms, ARG1 did not support bacterial survival in systemic salmonellosis, indicating differential roles of arginine metabolism for host immune response and microbe persistence depending on the type of pathogen.
CRIS-Team WoS Importer:2021-08-06

Defining metaniches in the oral cavity according to their microbial composition and cytokine profile - Seidel, Corinna Lesley; Gerlach, Roman; Wiedemann, Patrick; Weider, Matthias; Rodrian, Gabriele; Hader, Michael; Frey, Benjamin; Gaipl, Udo; Bozec, Aline; Cieplik, Fabian; Kirschneck, Christian; Bogdan, Christian; et al. (International Journal of Molecular Sciences, 2020)
The human oral microbiota consists of over 700 widespread taxa colonizing the oral cavity in several anatomically diverse oral niches. Lately, sequencing of the 16S rRNA genes has become an acknowledged, culture-independent method to characterize the oral microbiota. However, only a small amount of data are available concerning microbial differences between oral niches in periodontal health and disease. In the context of periodontitis, the cytokine expression in the gingival crevicular fluid has been studied in detail, whereas little is known about the cytokine profile in hard and soft tissue biofilms. In order to characterize oral niches in periodontal health, the oral microbiota and cytokine pattern were analyzed at seven different sites (plaque (P), gingival crevicular fluid (GCF), saliva (S), tongue (T), hard palate (HP), cheek (C) and sublingual area (U)) of 20 young adults using next-generation sequencing and multiplex immunoassays. Site-specific microbial compositions were detected, which clustered into three distinct metaniches (“P-GCF”, “S-T-HP” and “C-U”) and were associated with niche-/metaniche-specific cytokine profiles. Our findings allow the definition of distinct metaniches according to their microbial composition, partly reflected by their cytokine profile, and provide new insights into microenvironmental similarities between anatomical diverse oral niches.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Cytokine profile; Metaniches; Multiplex immunoassay; Next-generation sequencing; Oral biofilms and fluids; Oral microbiota; Oral niches

Diagnosis and therapy of cutaneous and mucocutaneous Leishmaniasis in Germany - Boecken, Gerhard; Sunderkötter, Cord; Bogdan, Christian; Weitzel, Thomas; Fischer, Marcellus; Müller, Andreas; Löbermann, Micha; Anders, Gerlind; Von Stebut, Esther; Schunk, Mirjam; Burchard, Gerd; Grobusch, Martin; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2011)
The incidence of cutaneous and mucocutaneous Leishmaniasis (CL/MCL) is increasing globally, also in Germany, although the cases are imported and still low in number. The current evidence for the different therapies has many limitations due to lack of sufficient studies on the different Leishmania species with differing virulence. So far there is no international gold standard for the optimal management. The aim of the German joint working group on Leishmaniasis, formed by the societies of Tropical Medicine (DTG), Chemotherapy (PEG) and Dermatology (DDG), was to establish a guideline for the diagnosis and treatment of CL and MCL in Germany, based on evidence (Medline search yielded 400 articles) and, where lacking, on consensus of the experts. As the clinical features do not necessarily reflect the involved Leishmania species and, as different parasite species and even geographically distinct strains of the same species may require different treatments or varying dosagesor durations of therapy, the guidelines suggest for Germany to identify the underlying parasite prior to treatment. Because of relevant differences in prognosis and ensuing therapy species should be identified in i) New World CL/MCL (NWCL/ MCL) to distinguish between L. mexicana-complex and subgenus Viannia, ii) in suspected infections with L. mexicana-complex to distinguish from L. amazonensis, and iii) in Old World CL (OWCL) to distinguish between L. infantum and L. major, L. tropica, or L. aethiopica. A state-of-the-art diagnostic algorithm is presented. For recommendations on localized and systemic drug treatment and physical procedures, data from the accessible literature were adjusted according to the involved parasite species and a clinical differentiation into uncomplicated or complex lesions. Systemic therapy was strictly recommended for i) complex lesions (e. g. > 3 infected lesions, infections in functionally or cosmetically critical areas such as face or hands, presence of lymphangitis), ii) lesions refractory to therapy, iii) NWCL by the subgenus Viannia or by L. amazonensis, iv) in MCL and v) in recalcitrant, or disseminating or diffuse cutaneous courses. In e. g. infection with L. major it encompasses miltefosine, fluconazole and ketoconazole, while antimony or allopurinol were here considered second choice. Local therapy was considered appropriate for i) uncomplicated lesions of OWCL, ii) L. mexicana-complex and iii) pregnant women. In e. g. infection with L. major it encompasses perilesional antimony, combined with cryotherapy, paromomycin 15 %/in methylbenzethoniumchlorid 12 % and thermotherapy. The group also stated that there is an urgent need for improving the design and the way of publishing of clinical trials in leishmaniasis. © 2011 The Authors.
CRIS-Team Scopus Importer:2024-02-26
Keywords: clinical disease; cutaneous; diagnosis; epidemiology; guideline; leishmaniasis; mucocutaneous; treatment

Diagnostic performance of four SARS-CoV-2 antibody assays in patients with COVID-19 or with bacterial and non-SARS-CoV-2 viral respiratory infections - Huber, Timo; Steininger, Philipp; Irrgang, Pascal; Korn, Klaus; Tenbusch, Matthias; Diesch, Katharina; Achenbach, Susanne; Kremer, Andreas; Werblow, Marissa; Vetter, Marcel; Bogdan, Christian; Held, Jürgen (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
SARS-CoV-2 antibody assays are used for epidemiological studies and for the assessment of vaccine responses in highly vulnerable patients. So far, data on cross-reactivity of SARS-CoV-2 antibody assays is limited. Here, we compared four enzyme-linked immunosorbent assays (ELISAs; Vircell SARS-CoV-2 IgM/IgA and IgG, Euroimmun SARS-CoV-2 IgA and IgG) for detection of anti-SARS-CoV-2 antibodies in 207 patients with COVID-19, 178 patients with serological evidence of different bacterial infections, 107 patients with confirmed viral respiratory disease, and 80 controls from the pre-COVID-19 era. In COVID-19 patients, the assays showed highest sensitivity in week 3 (Vircell-IgM/A and Euroimmun-IgA: 78.9% each) and after week 7 (Vircell-IgG: 97.9%; Euroimmun-IgG: 92.1%). The antibody indices were higher in patients with fatal disease. In general, IgM/IgA assays had only limited or no benefit over IgG assays. In patients with non-SARS-CoV-2 respiratory infections, IgG assays were more specific than IgM/IgA assays, and bacterial infections were associated with more false-positive results than viral infections. The specificities in bacterial and viral infections were 68.0 and 81.3% (Vircell-IgM/IgA), 84.8 and 96.3% (Euroimmun-IgA), 97.8 and 86.0% (Vircell-IgG), and 97.8 and 99.1% (Euroimmun-IgG), respectively. Sera from patients positive for antibodies against Mycoplasma pneumoniae, Chlamydia psittaci, and Legionella pneumophila yielded particularly high rates of unspecific false-positive results in the IgM/IgA assays, which was revealed by applying a highly specific flow-cytometric assay using HEK 293 T cells expressing the SARS-CoV-2 spike protein. Positive results obtained with anti-SARS-CoV-2 IgM/IgA ELISAs require careful interpretation, especially if there is evidence for prior bacterial respiratory infections.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Antibody; Bacterial infections; Coronavirus; COVID-19; Euroimmun; SARS-CoV-2; Vircell

Diagnostic Value of Vaginal Discharge, Wet Mount and Vaginal pH - An Update on the Basics of Gynecologic Infectiology - Frobenius, Wolfgang; Bogdan, Christian (Geburtshilfe und Frauenheilkunde, 2015)
The majority of uncomplicated vulvovaginal complaints (e.g. bacterial vaginosis, vulvovaginal candidiasis, trichomoniasis) can be detected with uncomplicated basic infectiological tests and can usually be treated effectively without requiring further diagnostic procedures. Tests include measurement of vaginal pH, preparation and assessment of wet mount slides prepared from vaginal or cervical discharge, and the correct clinical and microbiological classification of findings. In Germany, at least in recent years, this has not been sufficiently taught or practiced. As new regulations on specialist gynecologic training in Germany are currently being drawn up, this overview provides basic information on gynecologic infectiology and summarizes clinically relevant aspects of recent microbiological findings on the physiology and pathology of vaginal flora. The clinical signs and symptoms of aerobic vaginitis, the pathogenesis of which is still not completely understood, are also reviewed. Finally, the symptoms, indications and risk factors for pelvic inflammatory disease (PID) are presented. In contrast to the above-listed infections, PID requires immediate culture of the pathogen from samples (e.g. obtained by laparoscopy) with microbiological diagnostic procedures carried out by specialist laboratories. A schematic summary of all pathologies discussed here is presented.
EVALuna2:7681

Duration of Protection After Vaccination Against Yellow Fever-Systematic Review and Meta-analysis - Kling, Kerstin; Domingo, Cristina; Bogdan, Christian; Duffy, Steven; Harder, Thomas; Howick, Jeremy; Kleijnen, Jos; Mcdermott, Kevin; Wichmann, Ole; Wilder-Smith, Annelies; Wolff, Robert (Clinical Infectious Diseases, 2022)
The duration of protection after a single dose of yellow fever vaccine is a matter of debate. To summarize the current knowledge, we performed a systematic literature review and meta-analysis. Studies on the duration of protection after 1 and >= 2 vaccine doses were reviewed. Data were stratified by time since vaccination. In our meta-analysis, we used random-effects models. We identified 36 studies from 20 countries, comprising more than 17 000 participants aged 6 months to 85 years. Among healthy adults and children, pooled seroprotection rates after single vaccination dose were close to 100% by 3 months and remained high in adults for 5 to 10 years. In children vaccinated before age 2 years, the seroprotection rate was 52% within 5 years after primary vaccination. For immunodeficient persons, data indicate relevant waning. The extent of waning of seroprotection after yellow fever vaccination depends on age and immune status at primary vaccination.
CRIS-Team WoS Importer:2022-08-19

Durch Biofilm bakteriell besiedelte Implantate bedingen Wundheilungsstörungen - Beier, Justus; Bogdan, Christian; Schmitz, Markus; Schubert, Dirk W.; Schultz, Gregory; Horch, Raymund E. (Chirurgische Allgemeine - Zeitung für Klinik und Praxis, 2013)

Dynamics of humoral and cellular immune responses after homologous and heterologous SARS-CoV-2 vaccination with ChAdOx1 nCoV-19 and BNT162b2 - Vogel, Emanuel; Kocher, Katharina; Priller, Alina; Cheng, Cho Chin; Steininger, Philipp; Liao, Bo Hung; Körber, Nina; Willmann, Annika; Irrgang, Pascal; Held, Jürgen; Moosmann, Carolin; Schmidt, Viviane; et al. (EBioMedicine, 2022)
Background: Vaccines are an important means to overcome the SARS-CoV-2 pandemic. They induce specific antibody and T-cell responses but it remains open how well vaccine-induced immunity is preserved over time following homologous and heterologous immunization regimens. Here, we compared the dynamics of humoral and cellular immune responses up to 180 days after homologous or heterologous vaccination with either ChAdOx1-nCoV-19 (ChAd) or BNT162b2 (BNT) or both. Methods: Various tests were used to determine the humoral and cellular immune response. To quantify the antibody levels, we used the surrogate neutralization (sVNT) assay from YHLO, which we augmented with pseudo- and real virus neutralization tests (pVNT and rVNT). Antibody avidity was measured by a modified ELISA. To determine cellular reactivity, we used an IFN-γ Elispot, IFN-γ/IL Flurospot, and intracellular cytokine staining. Findings: Antibody responses significantly waned after vaccination, irrespective of the regimen. The capacity to neutralize SARS-CoV-2 – including variants of concern such as Delta or Omicron – was superior after heterologous compared to homologous BNT vaccination, both of which resulted in longer-lasting humoral immunity than homologous ChAd immunization. All vaccination regimens induced stable, polyfunctional T-cell responses. Interpretation: These findings demonstrate that heterologous vaccination with ChAd and BNT is a potent alternative to induce humoral and cellular immune protection in comparison to the homologous vaccination regimens. Funding: The study was funded by the German Centre for Infection Research (DZIF), the European Union's “Horizon 2020 Research and Innovation Programme" under grant agreement No. 101037867 (VACCELERATE), the “Bayerisches Staatsministerium für Wissenschaft und Kunst” for the CoVaKo-2021 and the For-COVID projects and the Helmholtz Association via the collaborative research program “CoViPa”. Further support was obtained from the Federal Ministry of Education and Science (BMBF) through the “Netzwerk Universitätsmedizin”, project “B-Fast” and “Cov-Immune”. KS is supported by the German Federal Ministry of Education and Research (BMBF, 01KI2013) and the Else Kröner-Stiftung (2020_EKEA.127).
CRIS-Team Scopus Importer:2022-10-21
Keywords: antibody avidity; BNT162b2; ChAdOx1-nCoV-19; COVID-19; Heterologous vaccination; long-term; maintenance; SARS-CoV-2; T cell immunity; vaccine

Effectiveness, immunogenicity and safety of 23-valent pneumococcal polysaccharide vaccine revaccinations in the elderly: a systematic review - Remschmidt, Cornelius; Harder, Thomas; Wichmann, Ole; Bogdan, Christian; Falkenhorst, Gerhard (BMC Infectious Diseases, 2016)
In many industrialized countries routine vaccination with the 23-valent pneumococcal polysaccharide vaccine (PPSV-23) is recommended to prevent pneumococcal disease in the elderly. However, vaccine-induced immunity wanes after a few years, and there are controversies around revaccination with PPSV-23. Here, we systematically assessed the effectiveness and safety of PPSV-23 revaccination.We conducted a systematic literature review in MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials from inception to June 2015. We included all study types that compared effectiveness, immunogenicity and/or safety of PPSV-23 as a primary vs. a revaccination dose in persons aged 50 years and older. With respect to immunogenicity, we calculated the ratio of geometric mean antibody concentrations and opsonophagocytic indexes at identical time-points after primary and revaccination. Additionally, we compared rates and severity of adverse events (AEs) after primary and revaccination.We included 14 observational studies. 10 studies had a prospective design and analysed data on (i) the same individuals after a first and a second dose of PPSV-23 given 1 to 10 years later (n = 5) or (ii) two groups consisting of participants receiving PPSV-23 who were either vaccine-naïve or had received a first PPSV-23 dose 3 to 13 years earlier (n = 5). Three studies used electronic data bases to compare AEs after primary vs. revaccination doses of PPSV-23 after 1 to 10 years and one study had a cross-sectional design. Number of participants in the non-register-based and register-based studies ranged from 29 to 1414 and 360 to 316,000, respectively. 11 out of 14 included studies were at high risk of bias, three studies had an unclear risk of bias. None of the studies reported data on clinical effectiveness. Immunogenicity studies revealed that during the first two months antibody levels tended to be lower after revaccination as compared to primary vaccination. Thereafter, no obvious differences in antibody levels were observed. Compared to primary vaccination, revaccination was associated with an increased risk of local and systemic AEs, which, however, were usually mild and self-limiting. The risk and severity of AEs appeared to decrease with longer intervals between primary and revaccination.Data comparing the effectiveness of primary vs. revaccination with PPSV-23 are still lacking, because there are no studies with clinical endpoints. Data from observational studies indicates that revaccination with PPSV-23 is likely to induce long-term antibody levels that are comparable to those after primary vaccination. Given the high disease burden and the waning of vaccine-induced immunity, revaccination with PPSV-23 could be considered in the elderly. The increased risk of local and systemic AEs can likely be mitigated when giving revaccination at least five years after the primary dose. Adequately powered randomized controlled trials using clinical endpoints are urgently needed.
EVALuna2:7724

Effectiveness of the 23-Valent Pneumococcal Polysaccharide Vaccine (PPV23) against Pneumococcal Disease in the Elderly: Systematic Review and Meta-Analysis - Falkenhorst, Gerhard; Remschmidt, Cornelius; Harder, Thomas; Hummers-Pradier, Eva; Wichmann, Ole; Bogdan, Christian (PLoS ONE, 2017)
Routine vaccination of elderly people against pneumococcal diseases is recommended in many countries. National guidelines differ, recommending either the 23-valent polysaccharide vaccine (PPV23), the 13-valent conjugate vaccine (PCV13) or both. Considering the ongoing debate on the effectiveness of PPV23, we performed a systematic literature review and meta-analysis of the vaccine efficacy/effectiveness (VE) of PPV23 against invasive pneumococcal disease (IPD) and pneumococcal pneumonia in adults aged >=60 years living in industrialized countries.We searched for pertinent clinical trials and observational studies in databases MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, and Cochrane Database of Systematic Reviews. We assessed the risk of bias of individual studies using the Cochrane Risk of Bias tool for randomized controlled trials and the Newcastle-Ottawa Scale for observational studies. We rated the overall quality of the evidence by GRADE criteria. We performed meta-analyses of studies grouped by outcome and study design using random-effects models. We applied a sensitivity analysis excluding studies with high risk of bias.We identified 17 eligible studies. Pooled VE against IPD (by any serotype) was 73% (95%CI: 10-92%) in four clinical trials, 45% (95%CI: 15-65%) in three cohort studies, and 59% (95%CI: 35-74%) in three case-control studies. After excluding studies with high risk of bias, pooled VE against pneumococcal pneumonia (by any serotype) was 64% (95%CI: 35-80%) in two clinical trials and 48% (95%CI: 25-63%) in two cohort studies. Higher VE estimates in trials (follow-up 2.5 years) than in observational studies (follow-up 5 years) may indicate waning protection. Unlike previous meta-analyses, we excluded two trials with high risk of bias regarding the outcome pneumococcal pneumonia, because diagnosis was based on serologic methods with insufficient specificity.Our meta-analysis revealed significant VE of PPV23 against both IPD and pneumococcal pneumonia by any serotype in the elderly, comparable to the efficacy of PCV13 against vaccine-serotype disease in a recent clinical trial in elderly people. Due to its broader serotype coverage and the decrease of PCV13 serotypes among adults resulting from routine infant immunization with PCV13, PPV23 continues to play an important role for protecting adults against IPD and pneumococcal pneumonia.
EVALuna2:7727

Electroporation of siRNA into Mouse Bone Marrow-Derived Macrophages and Dendritic Cells - Siegert, Isabel; Schatz, Valentin; Prechtel, Alexander T.; Steinkasserer, Alexander; Bogdan, Christian; Jantsch, Jonathan (Methods in Molecular Biology, 2014)
Dendritic cells (DC) and macrophages (M?) play a pivotal role in antimicrobial defense, in the regulation of immune responses, and in maintaining tissue homeostasis. The analysis of DC and M? function relies on primary cells albeit these cells are known to be difficult to transfect. This makes the use of small interfering RNA (siRNA) for targeted manipulation of gene expression by RNA interference difficult. In the following chapter, we provide a detailed protocol for the successful transfer of siRNA via electroporation into a defined population of mouse bone marrow-derived M? or DC that does not cause toxicity to the myeloid cells or nonspecific alterations of their biological functions. Factors that influence the transfection and knockdown rate will be highlighted.
EVALuna2:7575

Emergence of novel ST1299 vanA lineages as possible cause for the striking rise of vancomycin resistance among invasive strains of Enterococcus faecium at a German university hospital - Valenza, Giuseppe; Eisenberger, David; Voigtländer, Sven; Alsalameh, Rayya; Gerlach, Roman; Koch, Sonja; Kunz, Bernd; Held, Jürgen; Bogdan, Christian (Microbiology Spectrum, 2023)
IMPORTANCE: The proportion of VREfm among all Enterococcus faecium isolated from blood cultures in German hospitals has increased in the period 2015-2020 from 11.9% to 22.3% with a country-wide spread of the clonal lineage ST117/CT71 vanB. In this study, we provided useful information about the genetic diversity of invasive strains of E. faecium. Moreover, our findings confirm the nosocomial spread of novel ST1299 vanA lineages, which recently had a rapid expansion in Austria and the south-eastern part of Germany.
CRIS-Team Scopus Importer:2023-12-29
Keywords: bloodstream Infection; core genome multilocus sequence typing; Enterococcus faecium; ST1299 vanA; vancomycin resistance

Eosinophils, but Not Type 2 Innate Lymphoid Cells, Are the Predominant Source of Interleukin 4 during the Innate Phase of Leishmania major Infection - Sasse, Carolin; Barinberg, David; Obermeyer, Stephanie; Debus, Andrea; Schleicher, Ulrike; Bogdan, Christian (Pathogens, 2022)
Interleukin (IL)-4 plays a central role in the initiation of a type 2 T helper cell (Th2) response, which leads to non-healing and progressive infections with the protozoan parasite Leishmania (L.) major. Here, we tested the hypothesis that type 2 innate lymphoid cells (ILC2), which promote the development of Th2 cells, form an important source of IL-4 early after intradermal or subcutaneous L. major infection. Lineage-marker negative CD90.2(+)CD127(+)PD1(-) ILC2 were readily detectable in the ear or foot skin, but hardly in the draining lymph nodes of both naive and L. major-infected self-healing C57BL/6 and non-healing BALB/c mice and made up approximately 20% to 30% of all CD45(+)SiglecF(-) cells. Dermal ILC2 of C57BL/6 mice expressed the inducible T cell-costimulator (ICOS, CD278), whereas BALB/C ILC2 were positive for the stem cell antigen (Sca)-1. Within the first 5 days of infection, the absolute numbers of ILC2 did not significantly change in the dermis, which is in line with the unaltered expression of cytokines activating (IL-18, IL-25, IL-33, TSLP) or inhibiting ILC2 (IL-27, IFN-gamma). At day 5 to 6 post infection, we observed an upregulation of IL-4, but not of IL-5, IL-10 or IL-13 mRNA. Using IL-4-reporter (4get) mice, we found that the production of IL-4 by C57BL/6 or BALB/c mice was largely restricted to CD45(+)FSiglecF(+) cells of high granularity, i.e., eosinophils. From these data, we conclude that eosinophils, but not ILC2, are a major innate source of IL-4 at the skin site of L. major infection.
CRIS-Team WoS Importer:2022-09-09

Erfolgreiche Therapie der kutanen Leishmaniose mit simulierter Tageslicht-photodynamischer Therapie - Hobelsberger, Sarah; Krauss, Marie-Paloma; Bogdan, Christian; Aschoff, Roland (Hautarzt, 2021)
A 5-year-old Syrian boy , presented with a complex cutaneous leishmaniasis (CL) of the right ankle caused by Leishmania (L.) tropica. The patient received photodynamic therapy (PDT; 6 cycles with application of 5‑aminolevulinic acid and foil occlusion for 3 h). Due to pain during exposure to red light, exposure was continued with simulated daylight (sDL-PDT). The lesion healed with an atrophic scar. Due to fewer side effects and less pain, sDL-PDT seems to be a good therapeutic strategy for CL caused by L. tropica.
CRIS-Team Scopus Importer:2021-07-16
Keywords: 5‑Aminolevulinic acid; Child; Foil occlusion; Leishmania tropica; Simulated daylight photodynamic therapy

Erratum to "Incidence of invasive pneumococcal disease in 5-15 year old children with and without comorbidities in Germany after the introduction of PCV13: Implications for vaccinating children with comorbidities" [Vaccine 33 (2015) 6617-6621], DOI: 10.1016/j.vaccine.2015.10.102 - Weinberger, Raphael; Falkenhorst, Gerhard; Bogdan, Christian; van der Linden, Mark; Imöhl, Matthias; von Kries, Rüdiger (Vaccine, 2016)
CRIS-Team Scopus Importer:2024-02-26

Erratum to: Pneumokokkenimpfung im Säuglings- und im Kleinkindalter: Epidemiologische und immunologische Basis der pädiatrischen Pneumokokkenimpfung (Monatsschrift Kinderheilkunde, (2024), 10.1007/s00112-024-01940-w) - Vygen-Bonnet, Sabine; Schlaberg, Johanna; Kremer-Flach, Katrin; Perriat, Delphine; Bogdan, Christian (Monatsschrift Kinderheilkunde, 2024)
Dieser Artikel enthielt ursprünglich den Satz „Für PCV20 ist nur ein modifiziertes 3 + 1 Schema (Impfung im Alter von 2, 4, 6 und 11 Monaten) zugelassen.“ Korrekt ist: „Für PCV20 ist nur ein 3 + 1 Schema zugelassen.“ Der Originalbeitrag wurde korrigiert.
CRIS-Team Scopus Importer:2024-04-12

Erratum zu: Impfen bei Immundefizienz: Anwendungshinweise zu den von der Ständigen Impfkommission empfohlenen Impfungen.(II) Impfen bei 1. Primären Immundefekterkrankungen und 2. HIV-Infektion (Bundesgesundheitsblatt - Gesundheitsforschung - Gesundheitsschutz, (2018), 61, 8, (1034-1051), 10.1007/s00103-018-2761-8) - Ehl, Stephan; Bogdan, Christian; Niehues, Tim; Burchard, Gerd; Baumann, Ulrich; Hecht, Jane; Koch, Judith; Liese, Johannes G.; Neubert, Jennifer; Wiese-Posselt, Miriam; Zepp, Fred (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2019)
CRIS-Team Scopus Importer:2019-05-28

Evaluation of the amplex eazyplex loop-mediated isothermal amplification assay for rapid diagnosis of pneumocystis jirovecii pneumonia - Huber, Timo; Serr, Annerose; Geißdörfer, Walter; Hess, Christina; Lynker-Assmus, Christian; Von Loewenich, Friederike D.; Bogdan, Christian; Held, Jürgen (Journal of Clinical Microbiology, 2020)
Quantitative PCR (qPCR) assays are the gold standard for diagnosis of Pneumocystis jirovecii pneumonia (PCP). However, they are laborious and require skilled personnel. Therefore, execution outside regular working hours of the molecular biology laboratory is limited. The eazyplex P. jirovecii assay (PJA) uses loopmediated isothermal amplification for detection of P. jirovecii. It is performed directly with respiratory specimens, without the need for special skills, and delivers a result within 3 to 25 min. The goal of our study was to compare the performance of the eazyplex PJA with that of established P. jirovecii qPCR assays. All archived bronchoalveolar lavage fluid (BALF) samples that had previously tested positive for P. jirovecii by qPCR assay and 50 control samples (retrospective part), as well as all BALF samples received for P. jirovecii analysis over a period of 4 months (prospective part), were tested. Forty-nine patients with proven PCP and 126 patients without PCP were included. The sensitivity and specificity of the eazyplex PJA (95.7% and 96.5%, respectively) were comparable to those for three different P. jirovecii qPCR assays. The detection limit of the eazyplex PJA was analogous to 103 copies of the major surface glycoprotein gene per 25 μl of BALF, corresponding to 10 to 20 P. jirovecii cells. The eazyplex PJA reliably discriminated patients with PCP from patients with P. jirovecii colonization. It delivered a positive result within a mean of 9 min 38 s and required a hands-on time of 2 min 45 s. In summary, the eazyplex PJA showed identical performance for the diagnosis of PCP, compared to qPCR assays. However, in terms of time to result, practicability, and robustness, the eazyplex PJA is clearly superior and allows for around-the-clock molecular testing.
CRIS-Team Scopus Importer:2020-12-11
Keywords: AIDS; BALF; HIV; LAMP; NAT; PCP; PCR; Pneumocystis carinii; Point-of-care

Experimental Cutaneous Leishmaniasis: Mouse Models for Resolution of Inflammation Versus Chronicity of Disease - Bogdan, Christian; Debus, Andrea; Sebald, Heidi; Rai, Baplu; Schäfer, Johanna; Obermeyer, Stephanie; Schleicher, Ulrike (Leishmania, 2019)
Experimental cutaneous leishmaniasis of mice is a valuable model to study the immune response to the protozoan pathogen Leishmania and to define mechanisms of parasite control and resolution of inflammation as well as of parasite evasion and chronicity of disease. In addition, over many years Leishmania-infected mice have been successfully used to analyze the function of newly discovered immune cell types, transcription factors, cytokines, and effector mechanisms in vivo. In this chapter we present detailed protocols for the culture, propagation, and inoculation of Leishmania promastigotes, the monitoring of the course of cutaneous infection, the determination of the tissue parasite burden and for the phenotyping of the ensuing immune response. The focus lies on the L. major mouse model, but an overview on other established models of murine cutaneous leishmaniasis is also provided.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Cutaneous leishmaniasis; Leishmania major; Mouse models

Ex vivo metabolic profiling of physiological human T cell responses - Schuster, Ev-Marie; Frischholz, Sina; Schuelein, C.; Alsalameh, R.; Esse, Jan; Bogdan, Christian; Held, Jürgen; Schober, Kilian (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-02-17

Fatal Leishmaniasis in the Absence of TNF Despite a Strong Th1 Response - Fromm, Phillip D.; Kling, Jessica C.; Remke, Annika; Bogdan, Christian; Koerner, Heinrich (Frontiers in Microbiology, 2015)
Induction of inducible nitric oxide synthase in mononuclear phagocytes by IFN-? and innate tumor necrosis factor (TNF) provide the basis for an effective immune response to the intracellular parasite Leishmania (L.) major. In previous experiments, we observed a fatal visceral form of leishmaniasis in L. major-infected C57BL/6 TNF(-/-) mice. To further delineate the protective function of TNF and its receptor requirements, we comparatively assessed L. major-infected C57BL/6 mice that were either deficient for membrane and soluble TNF (Tnf (-) (/) (-)), for soluble TNF alone (memTnf(?/?) ), or the TNF receptors type 1 (Tnfr1 (-) (/) (-)) or type 2 (Tnfr2 (-) (/) (-)). We detected locally and systemically increased levels of the cytokine IFN-? in the absence of the TNF-TNFR1-signaling pathway. An analysis of transcription factors and cytokines revealed that activated Tnf (-) (/) (-) CD4(+) T cells displayed a highly active Th1 phenotype with a strong usage of the T cell receptor V?5.1/2. From these data we conclude that the fatal outcome of L. major infection in Tnf (-) (/) (-) mice does not result from a skewed or deficient Th1 differentiation.
EVALuna2:7701

Fatal Mycotic Aneurysm of the Basilar Artery Caused by Aspergillus fumigatus in a Patient with Pituitary Adenoma and Meningitis - Winterholler, Martin; Coras, Roland; Geißdörfer, Walter; Rammensee, Rudolf; Gölitz, Philipp; Bogdan, Christian; Lang, Roland (Frontiers in Medicine, 2017)
Fungal infections of the central nervous system (CNS) frequently occur in immunosuppressed patients. Here, we describe the case of an immunocompetent 64-year-old man who presented with diplopia, right-sided hemiparesis, and a mild headache after cleaning and replacing nesting boxes of wild birds during the preceding months. Lumbar puncture revealed pleocytosis, elevated protein, and lactate levels in the cerebrospinal fluid (CSF). Initial imaging showed ischemia in the left thalamus and an enlargement of the sellar region. Antibiotic treatment and corticosteroids led to an initial improvement but was followed by rapid deterioration. Antibiotic treatment was modified and antifungal therapy was added. Eighteen days after admission, the patient died from a subarachnoid hemorrhage resulting from the rupture of a fusiform aneurysm of the basilar artery. Microbiological culture of CSF was negative, but a positive galactomannan assay suggested fungal infection which was corroborated by detection of Aspergillus fumigatus DNA in pan-fungal PCR and sequencing. The presence of septated hyphae in the wall of the basilar artery confirmed the diagnosis of a mycotic aneurysm caused by hyphomycetal infection. In addition, brain autopsy revealed the presence of an invasive adrenocorticotrophic hormone-producing pituitary adenoma with arrosion of the sellar bone. This process and its invasiveness likely facilitated the spread of the fungal pathogen from the sphenoid sinus to the dura mater and finally led to cerebral angioinvasion. Our case demonstrates the challenge to timely diagnose and effectively treat aspergillosis as a cause of CNS infection also in apparently immunocompetent patients. The potential of assays detecting fungal antigens and of PCR to facilitate a timely diagnosis is discussed.
EVALuna2:7760

Ferritin-Mediated Iron Sequestration Stabilizes Hypoxia-Inducible Factor-1α upon LPS Activation in the Presence of Ample Oxygen. - Siegert, Isabel; Schödel, Johannes; Nairz, Manfred; Schatz, Valentin; Dettmer, Katja; Dick, Christopher; Kalucka, Joanna; Franke, Kristin; Ehrenschwender, Martin; Schley, Gunnar; Beneke, Angelika; Sutter, Jörg; et al. (Cell Reports, 2015)
Both hypoxic and inflammatory conditions activate transcription factors such as hypoxia-inducible factor (HIF)-1α and nuclear factor (NF)-κB, which play a crucial role in adaptive responses to these challenges. In dendritic cells (DC), lipopolysaccharide (LPS)-induced HIF1α accumulation requires NF-κB signaling and promotes inflammatory DC function. The mechanisms that drive LPS-induced HIF1α accumulation under normoxia are unclear. Here, we demonstrate that LPS inhibits prolyl hydroxylase domain enzyme (PHD) activity and thereby blocks HIF1α degradation. Of note, LPS-induced PHD inhibition was neither due to cosubstrate depletion (oxygen or α-ketoglutarate) nor due to increased levels of reactive oxygen species, fumarate, and succinate. Instead, LPS inhibited PHD activity through NF-κB-mediated induction of the iron storage protein ferritin and subsequent decrease of intracellular available iron, a critical cofactor of PHD. Thus, hypoxia and LPS both induce HIF1α accumulation via PHD inhibition but deploy distinct molecular mechanisms (lack of cosubstrate oxygen versus deprivation of co-factor iron).

First assessment for the presence of phlebotomine vectors in bavaria, southern germany, by combined distribution modeling and field surveys - Haeberlein, Simone; Fischer, Dominik; Thomas, Stephanie Margarete; Schleicher, Ulrike; Beierkuhnlein, Carl; Bogdan, Christian (PLoS ONE, 2013)
Leishmaniasis is caused by protozoa of the genus Leishmania and transmitted by sand flies from mammalian reservoirs to humans. In recent years, a northward spread of L. infantum from highly endemic Mediterranean countries into previously non-endemic Central European areas has been suspected based on presumed sporadic cases of autochthonous leishmaniasis. Here, we investigated whether sand flies are prevalent in Bavaria in Southern Germany, a federal state in which autochthonous cases have previously been reported. Considering the present and future climatic conditions, we determined whether Bavaria is suitable for five sand fly species with assumed spreading tendencies towards Central Europe: Phlebotomus ariasi , P. neglectus , P. perfiliewi and P. perniciosus that are known vectors for Leishmania in Europe, and P. mascittii, a suspected but not proven vector. Within Bavaria we defined sampling regions based on their climatic suitability and their spatial distance to the sites of the autochthonous cases and/or to areas of reported sand fly detection in states adjacent to Bavaria. At 155 locations in 7 sampling regions, CDC light traps were placed during 38 nights in the summers of 2009 and 2010, resulting in 202 trap-nights. All traps were negative for sand flies. The results suggest that Bavaria is not yet endemic for sand flies, but do not exclude the possibility of sporadic cases of autochthonous human or zoonotic Leishmania infections. This study, which combined methodological approaches from different disciplines, serves as reference for future surveys and risk analyses of sand flies and leishmaniasis in so far non-endemic areas of Europe. © 2013 Simone Haeberlein.
CRIS-Team Scopus Importer:2024-02-26

First report of the new emerging global clone ST1193 among clinical isolates of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli from Germany - Valenza, Giuseppe; Werner, Markus; Eisenberger, David; Nickel, Silke; Lehner-Reindl, Verena; Hoeller, Christiane; Bogdan, Christian (Journal of Global Antimicrobial Resistance, 2019)
Objectives: Sequence type 1193 (ST1193) is a new emerging global clone of Escherichia coli. The main goal of this study was to determine the prevalence and molecular characteristics of ST1193 among clinical isolates of extended-spectrum beta-lactamase (ESBL)-producing E. coli from University Hospital of Erlangen, Germany.
CRIS-Team WoS Importer:2019-07-09

Follicular Conjunctivitis due to Chlamydia felis-Case Report, Review of the Literature and Improved Molecular Diagnostics - Wons, Juliana; Meiller, Ralph; Bergua, Antonio; Bogdan, Christian; Geißdörfer, Walter (Frontiers in Medicine, 2017)
A 29-year-old woman presented with unilateral, chronic follicular conjunctivitis since 6 weeks. While the conjunctival swab taken from the patient's eye was negative in a Chlamydia (C.) trachomatis-specific PCR, C. felis was identified as etiological agent using a pan-Chlamydia TaqMan-PCR followed by sequence analysis. A pet kitten of the patient was found to be the source of infection, as its conjunctival and pharyngeal swabs were also positive for C. felis. The patient was successfully treated with systemic doxycycline. This report, which presents one of the few documented cases of human C. felis infection, illustrates that standard PCR tests are designed to detect the most frequently seen species of a bacterial genus but might fail to be reactive with less common species. We developed a modified pan-Chlamydia/C. felis duplex TaqMan-PCR assay that detects C. felis without the need of subsequent sequencing. The role of chlamydiae-specific serum antibody titers for the diagnosis of follicular conjunctivitis is discussed.
EVALuna2:7759

FRA-1 TRANSCRIPTION FACTOR EXPRESSION IN MACROPHAGES FOSTER INFLAMMATION DURING RHEUMATOID ARTHRITIS DEVELOPMENT - Hannemann, Nicole; Schnelzer, Anne; Jordan, Jutta; Eberhardt, Martin; Schleicher, Ulrike; Hueber, Axel; Reid, Stephen; Sonnewald, Sophia; Bäuerle, Tobias; Vera, Julio; Bogdan, Christian; Schett, Georg; et al. (2017)
EVALuna2:13497

Functionality of antigen-specific T cell receptor repertoires after SARS-CoV-2 vaccination - Kocher, Katharina; Drost, F.; Schuelein, C.; Moosmann, Carolin; D'Ippolito, E.; Busch, D. H.; Bogdan, Christian; Tenbusch, Matthias; Schubert, B.; Schober, Kilian (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Function of Macrophage and Parasite Phosphatases in Leishmaniasis - Soulat, Didier; Bogdan, Christian (Frontiers in Immunology, 2017)
The kinetoplastid protozoan parasites belonging to the genusLeishmaniaare the causative agents of different clinical forms of leishmaniasis, a vector-borne infectious disease with worldwide prevalence. The protective host immune response againstLeishmaniaparasites relies on myeloid cells such as dendritic cells and macrophages in which upon stimulation by cytokines (e.g., interferon-γ) a complex network of signaling pathways is switched on leading to strong antimicrobial activities directed against the intracellular parasite stage. The regulation of these pathways classically depends on post-translational modifications of proteins, with phosphorylation events playing a cardinal role.Leishmaniaparasites deactivate their phagocytic host cells by inducing specific mammalian phosphatases that are capable to impede signaling. On the other hand, there is now also evidence thatLeishmaniaspp. themselves express phosphatases that might target host cell molecules and thereby facilitate the intracellular survival of the parasite. This review will present an overview on the modulation of host phosphatases byLeishmaniaparasites as well as on the known families ofLeishmaniaphosphatases and their possible function as virulence factors. A more detailed understanding of the role of phosphatases inLeishmania-host cell interactions might open new avenues for the treatment of non-healing, progressive forms of leishmaniasis.
EVALuna2:33306

Gaps in Vaccine Coverage and Adverse Effects of Vaccines - An Overview - Bogdan, Christian (Deutsche Medizinische Wochenschrift, 2019)
The success of vaccination programs is jeopardized by gaps in vaccine coverage of the target population. These are frequently due to a lack of awareness, but also result from misconceptions of adverse effects of vaccines. Subject of this article are the current vaccination rates of children, adolescents and adults as well as of medical personnel in Germany, the reporting and surveillance system for adverse effects of vaccines, the magnitude of registered permanent vaccine-induced damages and the possible immunological mechanisms underlying vaccine-triggered autoimmune diseases.
CRIS-Team WoS Importer:2019-03-06

Generation, culture and flow-cytometric characterization of primary mouse macrophages - Schleicher, Ulrike; Bogdan, Christian (Macrophages and Dendritic Cells: Methods and Protocols, 2009)
Macrophages are not only host cells for many pathogens, but also fulfill several key functions in the innate and adaptive immune response, including the release of pro- and anti-inflammatory cytokines, the generation of organic and inorganic autacoids, the phagocytosis and killing of intracellular microorganisms or tumor cells, and the degradation and presentation of antigens. Several of these functions are shared by other immune cells, including dendritic cells, granulocytes, NK cells, and/or T lymphocytes. Thus, the analysis of macrophage functions in vitro using primary mouse cell populations requires standardized methods for the generation and culture of macrophages that guarantee high cell purity as well as the absence of stimulatory microbial contaminants. This chapter presents methodology to achieve these aims. © 2009 Humana Press, a part of Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2024-02-26
Keywords: Bone marrow-derived macrophages; Cell sorting; Cytokines; Flow cytometry; Interferon-gamma; Macrophages; Peritoneal exudate macrophages; Resident peritoneal macrophages; Teflon bags

Group 2 Innate Lymphoid Cells (ILC2) Suppress Beneficial Type 1 Immune Responses During Pulmonary Cryptococcosis - Kindermann, Markus; Knipfer, Lisa; Obermeyer, Stephanie; Müller, Uwe; Alber, Gottfried; Bogdan, Christian; Schleicher, Ulrike; Neurath, Markus; Wirtz, Stefan (Frontiers in Immunology, 2020)
Cryptococcus neoformans is an opportunistic fungal pathogen preferentially causing disease in immunocompromised individuals such as organ-transplant-recipients, patients receiving immunosuppressive medications or, in particular, individuals suffering from HIV infection. Numerous studies clearly indicated that the control of C. neoformans infections is strongly dependent on a prototypic type 1 immune response and classical macrophage activation, whereas type 2-biased immunity and alternative activation of macrophages has been rather implicated in disease progression and detrimental outcomes. However, little is known about regulatory pathways modulating and balancing immune responses during early phases of pulmonary cryptococcosis. Here, we analyzed the role of group 2 innate lymphoid cells (ILC2s) for the control of C. neoformans infection. Using an intranasal infection model with a highly virulent C. neoformans strain, we found that ILC2 numbers were strongly increased in C. neoformans-infected lungs along with induction of a type 2 response. Mice lacking ILC2s due to conditional deficiency of the transcription factor RAR-related orphan receptor alpha (Rora) displayed a massive downregulation of features of type 2 immunity as reflected by reduced levels of the type 2 signature cytokines IL-4, IL-5, and IL-13 at 14 days post-infection. Moreover, ILC2 deficiency was accompanied with increased type 1 immunity and classical macrophage activation, while the pulmonary numbers of eosinophils and alternatively activated macrophages were reduced in these mice. Importantly, this shift in pulmonary macrophage polarization in ILC2-deficient mice correlated with improved fungal control and prolonged survival of infected mice. Conversely, adoptive transfer of ILC2s was associated with a type 2 bias associated with less efficient anti-fungal immunity in lungs of recipient mice. Collectively, our date indicate a non-redundant role of ILC2 in orchestrating myeloid anti-cryptococcal immune responses toward a disease exacerbating phenotype.
CRIS-Team Scopus Importer:2020-03-10
Keywords: fungi (Candida; Cryptococcus); ILC2; innate immunity; lung infection; type 2 immune response

Guidelines for the use of flow cytometry and cell sorting in immunological studies (second edition) - Cossarizza, Andrea; Acs, Andreas; Adam, Dieter; Adam-Klages, Sabine; Agace, William W.; Aghaeepour, Nima; Akdis, Mübeccel; Allez, Matthieu; Almeida, Larissa Nogueira; Alvisi, Giorgia; Anderson, Graham; Andrä, Immanuel; et al. (European Journal of Immunology, 2019)
These guidelines are a consensus work of a considerable number of members of the immunology and flow cytometry community. They provide the theory and key practical aspects of flow cytometry enabling immunologists to avoid the common errors that often undermine immunological data. Notably, there are comprehensive sections of all major immune cell types with helpful Tables detailing phenotypes in murine and human cells. The latest flow cytometry techniques and applications are also described, featuring examples of the data that can be generated and, importantly, how the data can be analysed. Furthermore, there are sections detailing tips, tricks and pitfalls to avoid, all written and peer-reviewed by leading experts in the field, making this an essential research companion.
CRIS-Team Scopus Importer:2019-10-29

Hemophagocytic lymphohistiocytosis in imported pediatric visceral leishmaniasis in a nonendemic area - Bode, Sebastian F. N.; Bogdan, Christian; Beutel, Karin; Behnisch, Wolfgang; Greiner, Jeanette; Henning, Stephan; Jorch, Norbert; Jankofsky, Martin; Jakob, Marcus; Schmid, Irene; Veelken, Norbert; Vraetz, Thomas; et al. (Journal of Pediatrics, 2014)
To describe characteristics of visceral leishmaniasis-associated hemophagocytic lymphohistiocytosis (HLH) with focus on diagnostic clues and pitfalls, including the frequency of central nervous system (CNS) involvement, and to determine the efficacy of liposomal amphotericin B (L-AmB).We retrospectively analyzed clinical and laboratory features, diagnostic procedures, and treatment of 13 patients with HLH with imported visceral leishmaniasis, reported to the German HLH reference center (1999-2012).The spectrum of presentations was indistinguishable from patients with hereditary HLH or with acquired HLH because of infections with other pathogens. In 8 patients, disease onset occurred before the age of 2 years, coinciding with the typical age of manifestation of primary HLH. Two patients had mild nonspecific CNS findings. Misleading antiviral IgM (n = 6) and autoantibodies (n = 2) led to inaccurate interpretation of the etiology of HLH, sometimes with inappropriate therapeutic consequences. False negative results for Leishmania were obtained by initial bone marrow microscopy in 6/13, serology in 1/12, bone marrow culture in 2/5, and polymerase chain reaction of peripheral blood in 1/3 patients, and all bone marrow samples tested were Leishmania-positive by polymerase chain reaction (n = 7). L-AmB was administered to 12 patients, 5 of whom had no prior HLH-directed immunosuppressive therapy; sodium stibogluconate was administered to 1 patient. Persistent remission was achieved in 11 cases. Two patients required repeated or prolonged L-AmB therapy.Awareness of diagnostic pitfalls may save patients from unnecessary toxic treatment. CNS involvement is rare. L-AmB shows efficacy in visceral leishmaniasis-associated HLH.
EVALuna2:7654

Heterologous prime–boost vaccination with ChAdOx1 nCoV-19 and BNT162b2 - Tenbusch, Matthias; Schumacher, Sofie; Vogel, Emanuel; Priller, Alina; Held, Jürgen; Steininger, Philipp; Beileke, Stephanie; Irrgang, Pascal; Brockhoff, Ronja; Salmanton-García, Jon; Tinnefeld, Kathrin; Mijocevic, Hrvoje; et al. (Lancet Infectious Diseases, 2021)
CRIS-Team Scopus Importer:2021-09-10

High frequency of Tropheryma whipplei in culture-negative endocarditis - Geißdörfer, Walter; Moos, Verena; Moter, Annette; Loddenkemper, Christoph; Jansen, Andreas; Tandler, Rene; Morguet, Andreas J.; Fenollar, Florence; Raoult, Didier; Bogdan, Christian; Schneider, Thomas (Journal of Clinical Microbiology, 2012)
"Classical" Whipple's disease (cWD) is caused by Tropheryma whipplei and is characterized by arthropathy, weight loss, and diarrhea. T. whipplei infectious endocarditis (TWIE) is rarely reported, either in the context of cWD or as isolated TWIE without signs of systemic infection. The frequency of TWIE is unknown, and systematic studies are lacking. Here, we performed an observational cohort study on the incidence of T. whipplei infection in explanted heart valves in two German university centers. Cardiac valves from 1,135 patients were analyzed for bacterial infection using conventional culture techniques, PCR amplification of the bacterial 16S rRNA gene, and subsequent sequencing. T. whipplei-positive heart valves were confirmed by specific PCR, fluorescence in situ hybridization, immunohistochemistry, histological examination, and culture for T. whipplei. Bacterial endocarditis was diagnosed in 255 patients, with streptococci, staphylococci, and enterococci being the main pathogens. T. whipplei was the fourth most frequent pathogen, found in 16 (6.3%) cases, and clearly outnumbered Bartonella quintana, Coxiella burnetii, and members of the HACEK group (Haemophilus species, Actinobacillus actinomycetemcomitans, Cardiobacterium hominis, Eikenella corrodens, and Kingella kingae). In this cohort, T. whipplei was the most commonly found pathogen associated with culture-negative infective endocarditis. Copyright © 2012, American Society for Microbiology. All Rights Reserved.
CRIS-Team Scopus Importer:2024-02-26

High prevalence of the recently identified clonal lineage ST1299/CT3109 vanA among vancomycin-resistant Enterococcus faecium strains isolated from municipal wastewater - Valenza, Giuseppe; Eisenberger, David; Esse, Jan; Held, Jürgen; Lehner-Reindl, Verena; Plaumann, Peter Louis; Ziegler, Tobias; Knauer, Max; Bogdan, Christian; Dudler, Patrick (mSphere, 2024)
Previously, we demonstrated that the majority of vancomycin-resistant Enterococcus faecium (VREfm) strains from in-patients of the University Hospital Erlangen, Germany, belonged to only three clonal lineages, namely ST117/CT71 vanB and two novel ST1299 vanA lineages classified as CT3109 and CT1903. The goal of the current study was (i) to investigate whether VREfm is also detectable in wastewater of the city of Erlangen, (ii) to identify their molecular features, and (iii) to clarify whether VREfm could arise from the community of the city of Erlangen or can be (directly) connected to nosocomial infections in the hospital setting. From April to May 2023, a total of 244 VREfm strains from raw wastewater of the city of Erlangen were analyzed by core genome multilocus sequence typing (cgMLST). Moreover, 20 of them were further investigated for single nucleotide polymorphisms (SNPs). The molecular characterization of the wastewater VREfm strains revealed a high prevalence (27.9%) of the recently identified clonal lineage ST1299/CT3109 vanA, which is mainly characterized by the presence of the tetracycline-resistance determinant tet(M) and the virulence genes pilA and prpA. The SNPs analysis revealed the presence of two major clusters, namely cluster I (≤65 SNPs), which included well-known hospital-adapted vanB clonal lineages such as ST117/CT71 and ST80/CT1065 and cluster II (≤70 SNPs), which were mainly characterized by the lineage ST1299/CT3109 vanA. Based on the concomitant resistance to vancomycin and tetracycline, we propose that ST1299/CT3109 vanA primarily originated and spread outside of hospital settings.IMPORTANCEThis study provides a detailed genomic analysis of vancomycin-resistant Enterococcus faecium (VREfm) strains isolated from municipal wastewater with a particular focus on clonal lineages, antimicrobial resistance, and the presence of virulence genes. The high wastewater prevalence of the recently identified clonal lineage ST1299/CT3109 vanA, which has been previously detected in hospitals, suggests an enormous potential for future spread in Germany.
CRIS-Team Scopus Importer:2024-10-04
Keywords: core genome multilocus sequence typing; Enterococcus faecium; single nucleotide polymorphisms; ST117/CT71; ST1299/CT3109; vancomycin-resistance; wastewater

Homologous COVID-19 BNT162b2 mRNA Vaccination at a German Tertiary Care University Hospital: A Survey-Based Analysis of Reactogenicity, Safety, and Inability to Work among Healthcare Workers - Niekrens, Valentin; Esse, Jan; Held, Jürgen; Knobloch, Carina; Steininger, Philipp; Kunz, Bernd; Seggewies, Christof; Bogdan, Christian (Vaccines, 2022)
At the start of the SARS-CoV-2 pandemic, healthcare workers had an increased risk of acquiring coronavirus disease (COVID)-19. As tertiary care hospitals are critical for the treatment of severely ill patients, the University Hospital Erlangen offered BNT162b2 mRNA vaccination against COVID-19 to all employees when the vaccine became available in Germany. Here, we performed a survey to assess the age- and sex-dependent reactogenicity and safety of BNT162b2 in a real-life setting with a special emphasis on the rate of vaccine-related incapacity to work amongst the employees. All vaccinated employees were invited to participate in the survey and received access to an electronic questionnaire between 31 March and 14 June 2021, which allowed them to report local and systemic adverse effects after the first or second vaccine dose. A total of 2372 employees completed the survey. After both the first and second dose, women had a higher risk than men for vaccine-related systemic side effects (odds ratio (OR) 1.48 (1.24-1.77) and 1.49 (1.23-1.81), respectively) and for inability to work (OR 1.63 (1.14-2.34) and 1.85 (1.52-2.25), respectively). Compared to employees >= 56 years of age, younger vaccinated participants had a higher risk of systemic reactions after the first (OR 1.35 (1.07-1.70)) and second vaccination (OR 2.08 (1.64-2.63)) and were more often unable to work after dose 2 (OR 2.20 (1.67-2.88)). We also recorded four anaphylactic reactions and received two reports of severe adverse effects indicative of vaccine complications. After the first and second vaccination, 7.9% and 34.7% of the survey participants, respectively, were temporarily unable to work, which added up to 1700 days of sick leave in this cohort. These real-life data extend previous results on the reactogenicity and safety of BNT162b2. Loss of working time due to vaccine-related adverse effects was substantial, but was outweighed by the potential benefit of prevented cases of COVID-19.
CRIS-Team WoS Importer:2022-06-10

Host-parasite interactions - Körner, Heinrich; Hu, Shanshan; Bogdan, Christian (Springer-Verlag Wien, 2016)
Ontogeny and differentiation of cells of the monocyte/macrophage lineage are currently subjects of intense research. The concept of the macrophage as “simple” phagocytic cell has undergone profound changes. It has now been established that this myeloid lineage of cells is phenotypically and functionally much more diverse and exerts a much wider influence on the immune response than previously thought. How have these new findings changed our perception of the role of monocytes and macrophages in parasitic diseases? There is now strong evidence that macrophages fulfill organ-specific differential functions, exert activating as well as inhibitory effects on the adaptive immune response, and exist in a whole range of different activation statuses which show a high degree of plasticity. In the present chapter, we will not only review the pertinent literature on these new developments but also bring it into relation to the anti-infectious immune response, focusing on four parasitic diseases (trypanosomiasis, toxoplasmosis, malaria, and leishmaniasis) as examples.
CRIS-Team Scopus Importer:2024-02-26

Hypoxia in Leishmania major skin lesions impairs the NO-dependent leishmanicidal activity of macrophages - Mahnke, Alexander; Meier, Robert J.; Schatz, Valentin; Hofmann, Julian; Castiglione, Kirstin; Schleicher, Ulrike; Wolfbeis, Otto S.; Bogdan, Christian; Jantsch, Jonathan (Journal of Investigative Dermatology, 2014)
Cure of infections with Leishmania major is critically dependent on the ability of macrophages to induce the type 2 nitic oxide (NO) synthase (NOS2) that produces high levels of NO in the presence of ample oxygen. Therefore, we analyzed the oxygen levels found in leishmanial skin lesions and their effect on the NOS2-dependent leishmanicidal activity of macrophages (M?). When L. major skin lesions of self-healing C57BL/6 mice reached their maximum size, the infected tissue displayed low oxygen levels (pO2 21 Torr). M? activated under these oxygen tensions failed to produce sufficient amounts of NO to clear L. major. Nos2-deficient and hypoxic wild-type macrophages displayed a similar phenotype. Killing was restored when M? were reoxygenated or exposed to a NO donor. The resolution of the lesion in C57BL/6 mice was paralleled by an increase of lesional pO2. When mice were kept under normobaric hypoxia, this caused a persistent suppression of the lesional pO2 and a concurrent increase of the parasite load. In Nos2-deficient mice, there was no effect of atmospheric hypoxia. Low oxygen levels found at leishmanial skin lesions impaired the NOS2-dependent leishmanicidal activity of M?. Hence, tissue oxygenation represents an underestimated local milieu factor that participates in the persistence of Leishmania.
EVALuna2:7645

IL-33/ST2 immune responses to respiratory bacteria in pediatric asthma - Hentschke, Isabell; Graser, Anna; Melichar, Volker O.; Kiefer, Alexander; Zimmermann, Theodor; Kross, Bettina; Haag, Patricia; Xepapadaki, Paraskevi; Papadopoulos, Nikolaos G.; Bogdan, Christian; Finotto, Susetta (Scientific Reports, 2017)
Here we investigated the relationship between local bacterial colonization and anti-bacterial immune responses in pre-school asthmatic and control children within the EU-wide study PreDicta. In this cohort of pre-school asthmatic children, nasopharyngeal colonization with Gram-negative bacteria such as Haemophilus influenzae and Moraxella catarrhalis was found to be associated with the highest interferon beta (IFN?) and IL-33 levels in the nasal pharyngeal fluids (NPF). IL33R-ST2 was found induced in the blood of asthmatic children with additional Gram + bacteria in the nasopharynx (Gr+/-). Furthermore, asthmatic children had more episodes of infection that required antibiotic therapy than the control group. Treatment with antibiotics associated with reduced ST2 in blood cells of both asthmatic and control children and reduced IL-33 levels in the airways of asthmatic children. In the absence of Staphylococcus (S.) aureus in NPF, antibiotic therapy associated with decreased IL-33 levels in the NPF and lower ST2 values in the blood of control children but not of asthmatic children. These data suggest that, in asthmatic children, Gram- bacteria, which persist after antibiotic therapy, contributes to IL-33 locally and associated with Gr + bacteria colonization in the airways, inhibited IFN-? and in the absence of Staphylococcus (S.) aureus, induced ST2 bearing cells in their blood.
EVALuna2:7728

Images in clinical tropical medicine rhinophyma-like cutaneous leishmaniasis due to leishmania aethiopica treated successfully with liposomal Amphotericin B - Kirchberger, Michael Constantin; Schliep, Stefan; Bogdan, Christian (American Journal of Tropical Medicine and Hygiene, 2019)
CRIS-Team Scopus Importer:2019-05-02

Immunogenicity and diagnostic potential of synthetic antigenic cell surface glycans of leishmania - Anish, Chakkumkal; Martin, Christopher E.; Wahlbrink, Annette; Bogdan, Christian; Ntais, Pantelis; Antoniou, Maria; Seeberger, Peter H. (ACS Chemical Biology, 2013)
Detection and quantification of pathogen-derived antigenic structures is a key method for the initial diagnosis and follow-up of various infectious diseases. Complex parasitic diseases such as leishmaniasis require highly sensitive and specific tests prior to treatment with potentially toxic drugs. To investigate the diagnostic potential of cell surface glycans found on Leishmania parasites, we identified diagnostically relevant glycan epitopes and used synthetic glycan microarrays to screen sera from infected humans and dogs. On the basis of the screening results, we selected a tetrasaccharide to generate anti-glycan antibodies. The corresponding tetrasaccharide-carrier protein conjugate was immunogenic in mice, and sera obtained from immunized mice specifically detected the Leishmania parasite. These results demonstrate how synthetic glycan arrays, in combination with immunological methods, help to identify promising carbohydrate antigens for pathogen detection. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2024-02-26

Immunologie und klinische Wirksamkeit der Pneumokokken-Impfung im Alter - Bogdan, Christian; Falkenhorst, G. (Internistische Praxis, 2018)
Streptococcus pneumoniae is a frequent cause of local and systemic infections in humans. The polysaccharide capsule, of which so far 97 different serotypes have been described, is its most important virulence factor. Elderly people show an increased susceptibility to pneumococcal infections, even in the absence of additional risk factors. In Germany two different pneumococcal vaccines are available for prophylaxis: the 13-valent polysaccharideprotein- conjugate vaccine (PCV13) and the 23-valent polysaccharide vaccine (PPSV23). Today, following the widespread use of PCV13 in infants and small children, only 30 % of invasive pneumococcal disease (IPD) episodes in elderly people (>60 yrs) are caused by pneumococcal serotypes contained in the PCV13 vaccine, whereas roughly 70 % of the IPD cases are due to serotypes covered by the PPSV23 vaccine. As in immunocompetent adults and elderly people both vaccines showed a comparable efficacy against pneumococcal disease with vaccine serotypes, the Standing Committee on Vaccination in Germany (STIKO) recommends the use of PPSV23 as the standard anti-pneumococcal vaccine in people >60 yrs of age. In the presence of certain underlying diseases the sole application of PPSV23 or the sequential vaccination with PCV13 followed by PPSV23 after a minimum of 2 (better 6-12) months is indicated. This review will discuss the principal immunological differences between both vaccines and the considerations that led to the recommendation by the STIKO.
CRIS-Team Scopus Importer:2024-02-26
Keywords: 13-valent pneumococcal conjugate vaccine; 23-valent pneumococcal polysaccharide vaccine; Indications for vaccination; Standing Committee on Vaccination (STIKO); Streptococcus pneumoniae (pneumococci)

Impfempfehlungen der Ständigen Impfkommission (STIKO): Impfungen bei Immundefizienz und Impfung gegen COVID-19 - Bogdan, Christian (Hautarzt, 2021)
Background: The working methods of the Standing Committee on Vaccination (STIKO) and its recommendations are only partially known by medical professionals and the public. Objectives: Methodology of the standard operating procedure of the STIKO, annual vaccination recommendations, normal vaccination reaction versus vaccination side effects, instructions for vaccination in case of immunodeficiency, and recommendation for COVID-19 vaccination are presented. Materials and methods: Presentation of the path to a vaccination recommendation, differences between recommendations and instructions for action, key statements on vaccination in immunodeficiency, and summary of the data situation on COVID-19 mRNA vaccination. Results: The STIKO works purely on an evidence-based basis by systematically evaluating the existing preclinical and clinical studies results for a vaccine using the GRADE method. Only vaccination complications and vaccination injuries are notifiable. Immunodeficient patients can receive inactivated vaccines at any time, but generally not live vaccines. Based on current knowledge, the COVID-19 mRNA vaccination can be described as safe and effective. Conclusions: The STIKO vaccination recommendations are considered as the medical standard. The published current instructions for vaccination of immunodeficient patients and the recently published recommendation for COVID-19 vaccination, together with their scientific backgrounds and reasons, represent a valuable basis for medical action in the field of vaccination against infectious diseases.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Adverse effects of vaccines; mRNA vaccine; Normal vaccine response; Vaccine complication; Vaccine injury

Impfen bei Immundefizienz : Anwendungshinweise zu den von der Ständigen Impfkommission empfohlenen Impfungen(I) Grundlagenpapier - Niehues, Tim; Bogdan, Christian; Hecht, Jane; Mertens, Thomas; Wiese-Posselt, Miriam; Zepp, Fred (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2017)
EVALuna2:7758

Impfen bei Immundefizienz: Anwendungshinweise zu den von der Ständigen Impfkommission empfohlenen Impfungen. (III) Impfen bei hämatologischen und onkologischen Erkrankungen (antineoplastische Therapie, Stammzelltransplantation), Organtransplantation und Asplenie - Laws, Hans-Juergen; Baumann, Ulrich; Bogdan, Christian; Burchard, Gerd; Christopeit, Maximilian; Hecht, Jane; Heininger, Ulrich; Hilgendorf, Inken; Kern, Winfried; Kling, Kerstin; Kobbe, Guido; Kuelper, Wiebe; et al. (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2020)
CRIS-Team Scopus Importer:2020-05-15

Impfen bei Immundefizienz : Anwendungshinweise zu den von der Ständigen Impfkommission empfohlenen Impfungen. (IV) Impfen bei Autoimmunkrankheiten, bei anderen chronisch-entzündlichen Erkrankungen und unter immunmodulatorischer Therapie - Wagner, Norbert; Assmus, Frauke; Arendt, Gabriele; Baum, Erika; Baumann, Ulrich; Bogdan, Christian; Burchard, Gerd; Foell, Dirk; Garbe, Edeltraut; Hecht, Jane; Mueller-Ladner, Ulf; Niehues, Tim; et al. (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2019)
CRIS-Team Scopus Importer:2019-05-02

Incidence of invasive pneumococcal disease in 5-15 year old children with and without comorbidities in Germany after the introduction of PCV13: Implications for vaccinating children with comorbidities - Weinberger, Raphael; Falkenhorst, Gerhard; Bogdan, Christian; Van Der Linden, Mark; Imoehl, Matthias; Von Kries, Rildiger (Vaccine, 2015)
To describe the burden of suffering from IPD in children aged 5-15 years with and without comorbidities up to 5 years after the introduction of PCV13 in Germany and to identify the potential benefit for PCV13 and PPV23 vaccination.The surveillance of IPD for children <16 years was based on two independently reporting sources: active surveillance in pediatric hospitals and a laboratory-based sentinel surveillance system.IPD with cultural detection of pneumococci at a physiologically sterile site in children from 2010 to 2014 in Germany. Incidence was estimated by capture-recapture analysis with stratification by absence/presence of comorbidities. Coverage of the observed serotypes by different vaccines was assessed.142 (Capture recapture-corrected: 437) cases were reported: 72.5% were healthy children and 27.5% had a comorbidity. The incidence of IPD related to children with comorbidities was 0.2 per 100,000. One third of these cases had serotypes not included in either vaccine. The remaining cases might benefit from pneumococcal vaccination but one third of all cases was not vaccinated. The additional potential benefit of PPV23 compared to PCV13 with respect to coverage was 10%.The incidence of IPD in children with comorbidities in Germany is low. Pneumococcal vaccination uptake in children with comorbidities should be increased, although only about two-thirds of the cases might be preventable by presently available vaccines.
EVALuna2:7678

Incidence of invasive pneumococcal disease in 5-15 year old children with and without comorbidities in Germany after the introduction of PCV13: Implications for vaccinating children with comorbidities (vol 33, pg 6617, 2015) - Weinberger, Raphael; Falkenhorst, Gerhard; Bogdan, Christian; Van Der Linden, Mark; Imoehl, Matthias; Von Kries, Ruediger (Vaccine, 2016)
EVALuna2:33312

Infections with the tick-borne bacterium "Candidatus Neoehrlichia mikurensis" mimic noninfectious conditions in patients with B cell malignancies or autoimmune diseases - Grankvist, Anna; Andersson, Per-Ola; Mattsson, Mattias; Sender, Monica; Vaht, Krista; Hoper, Linnea; Sakiniene, Egidija; Trysberg, Estelle; Stenson, Martin; Fehr, Jan; Pekova, Sona; Bogdan, Christian; et al. (Clinical Infectious Diseases, 2014)
Candidatus Neoehrlichia mikurensis is a newly discovered noncultivatable bacterium spread among ticks and rodents in Europe and Asia that can infect humans, particularly immunocompromised patients.We compiled clinical and laboratory data from 11 patients with hematological malignances or autoimmune diseases who were diagnosed with Candidatus N. mikurensis infection in Europe 2010-2013. Both published (6) and unpublished cases (5) were included.The patients had a median age of 67, were mostly male (8/11), and resided in Sweden, Switzerland, Germany, and the Czech Republic. All but one had ongoing or recent immune suppressive treatment and a majority were splenectomized (8/11). Less than half of them recalled tick exposure. The most frequent symptoms were fever (11/11), localized pain afflicting muscles and/or joints (8/11), vascular and thromboembolic events (6/11), that is, deep vein thrombosis (4), transitory ischemic attacks (2), pulmonary embolism (1), and arterial aneurysm (1). Typical laboratory findings were elevated C-reactive protein, leukocytosis with neutrophilia, and anemia. Median time from onset of symptoms to correct diagnosis was 2 months. In at least 4 cases, the condition was interpreted to be due to the underlying disease, and immunosuppressive therapy was scheduled. All patients recovered completely when doxycycline was administered.Candidatus N. mikurensis is an emerging tick-borne pathogen that may give rise to a systemic inflammatory syndrome in persons with hematologic or autoimmune diseases that could be mistaken for recurrence of the underlying disease and/or unrelated arteriosclerotic vascular events. Awareness of this new pathogen is warranted among rheumatologists, hematologists, oncologists, and infectious disease specialists.
EVALuna2:7651

Influence of different treatment conditions on the filtration performance of conventional electret melt blown non-woven and novel nano FFP2 masks - Halamicek, Robin; Wiesmann, Carolin; Kröner, Richard; Eber, Matthias; Bogdan, Christian; Schubert, Dirk W. (PLoS ONE, 2023)
To allow an efficient protection against viruses like the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2), it is important to avoid their spreading by using filtering face pieces (FFP), which are categorized by different standards according to their filtration efficiency. In this study, we subjected six brands of FFP2 standard masks to three different conditions and subsequently analysed them for their filtration performance to evaluate potentials for reusability. The conditions comprised changes of temperature and air humidity, an exposure to isopropyl alcohol (IPA) and an autoclave sterilization. While four of six masks consisted of electrostatically treated melt blown non-wovens, two masks were fabricated using a nanofibrous multilayer system. Due to the absence of prior electrostatic treatment, the nano-masks did not show a significant change in filtration efficiency when discharged by IPA, unlike the melt blown nonwoven masks showing a significant decrease of filtration efficiency down to around 50% at a particle size of 0.3 μm. However, most melt blown masks maintained a sufficient filtration efficiency after all other treatments with even better results than the nanofibrous masks. This was particularly the case for the capacity to filter smallest particles/droplets with a size of around 0.1 μm, which is below the range of typical filtering standards and important for the retention of virally contaminated nano-aerosols or unattached viruses. After temperature/humidity variation and autoclave sterilization, melt blown masks were able to retain a filtration efficiency up to over 90% at 0.1 μm contrary to nano-masks showing a decrease down to around 70%. Based on their better filtration performance, lower price and potential reusability, we conclude that electret melt blown masks are the preferable type of FFP2 masks.
CRIS-Team Scopus Importer:2023-09-29

Influence of probiotics on the periodontium, the oral microbiota and the immune response during orthodontic treatment in adolescent and adult patients (ProMB Trial): study protocol for a prospective, double-blind, controlled, randomized clinical trial - Seidel, Corinna Lesley; Gerlach, Roman; Weider, Matthias; Woelfel, Theresa; Schwarz, Vincent; Stroebel, Armin; Schmetzer, Helga; Bogdan, Christian; Gölz, Lina (BMC Oral Health, 2022)
Background Orthodontic treatment with fixed appliances is often necessary to correct malocclusions in adolescence or adulthood. However, oral hygiene is complicated by appliances, and prior studies indicate that they may trigger oral inflammation and dysbiosis of the oral microbiota, especially during the first 3 months after insertion, and, thus, may present a risk for inflammatory oral diseases. In recent periodontal therapeutic studies, probiotics have been applied to improve clinical parameters and reduce local inflammation. However, limited knowledge exists concerning the effects of probiotics in orthodontics. Therefore, the aim of our study is to evaluate the impact of probiotics during orthodontic treatment. Methods This study is a monocentric, randomized, double blind, controlled clinical study to investigate the effectiveness of daily adjuvant use of Limosilactobacillus reuteri (Prodentis (R)-lozenges, DSM 17938, ATCC PTA 5289) versus control lozenges during the first three months of orthodontic treatment with fixed appliances. Following power analysis, a total of 34 adolescent patients (age 12-17) and 34 adult patients (18 years and older) undergoing orthodontic treatment at the University Hospital Erlangen will be assigned into 2 parallel groups using a randomization plan for each age group. The primary outcome measure is the change of the gingival index after 4 weeks. Secondary outcomes include the probing pocket depth, the modified plaque index, the composition of the oral microbiota, the local cytokine expression and-only for adults-serum cytokine levels and the frequencies of cells of the innate and adaptive immune system in peripheral blood. Discussion Preventive strategies in everyday orthodontic practice include oral hygiene instructions and regular dental cleaning. Innovative methods, like adjuvant use of oral probiotics, are missing. The aim of this study is to analyse, whether probiotics can improve clinical parameters, reduce inflammation and prevent dysbiosis of the oral microbiota during orthodontic treatment. If successful, this study will provide the basis for a new strategy of prophylaxis of oral dysbiosis-related diseases during treatment with fixed appliances.
CRIS-Team WoS Importer:2022-05-13
Keywords: Probiotics; Lactobacillus reuteri; Limosilactobacillus reuteri; Oral microbiota; Cytokines; Inflammation; Orthodontic treatment; Oral health; Prevention; Study protocol

Inhibited Arginase-1 Expression by Fra-1 in Myeloid Cells Enhance Rheumatoid Arthritis Inflammation - Hannemann, Nicole; Schnelzer, A.; Jordan, J.; Eberhardt, Martin; Schleicher, Ulrike; Uebe, Steffen; Ekici, Arif Bülent; Reid, Stephen; Sonnewald, Sophia; Bäuerle, Tobias; Bogdan, Christian; Vera, Julio; et al. (2017)
EVALuna2:33310

INHIBITION OF ARGINASE-1 EXPRESSION BY THE TRANSCRIPTION FACTOR FRA-1 IN MACROPHAGES EXACERBATES RHEUMATOID ARTHRITIS INFLAMMATION - Hannemann, Nicole; Cao, Shan; Schnelzer, A.; Jordan, J.; Eberhardt, Martin; Schleicher, Ulrike; Uebe, Steffen; Ekici, Arif Bülent; Rech, Jürgen; Bäuerle, Tobias; Bogdan, Christian; Vera, Julio; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-05-17

Innate immune tissue injury and murine HGA: tissue injury in the murine model of granulocytic anaplasmosis relates to host innate immune response and not pathogen load. - Scorpio, Diana G.; Von Loewenich, Friederike D.; Bogdan, Christian; Dumler, J. Stephen (Annals of the New York Academy of Sciences, 2005)
Anaplasma phagocytophilum is an obligate intracellular tick-borne bacterium that propagates within neutrophils and causes human and animal granulocytic anaplasmosis (HGA). In the murine model of HGA, host immune response plays a more important role in histopathologic lesions than does pathogen load. We examined the role of CYBB, NOS2, and TNFalpha as effectors of innate immune-related injury. Our hypothesis is that the innate immune response to A. phagocytophilum results in inflammatory histopathology, but does not control the pathogen.
CRIS-Team Scopus Importer:2024-02-26

Integrative bioinformatic analyses of global transcriptome data decipher novel molecular insights into cardiac anti-fibrotic therapies - Fuchs, Maximilian; Kreutzer, Fabian Philipp; Kapsner, Lorenz; Mitzka, Saskia; Just, Annette; Perbellini, Filippo; Terracciano, Cesare M.; Xiao, Ke; Geffers, Robert; Bogdan, Christian; Prokosch, Hans-Ulrich; Fiedler, Jan; et al. (International Journal of Molecular Sciences, 2020)
Integrative bioinformatics is an emerging field in the big data era, offering a steadily increasing number of algorithms and analysis tools. However, for researchers in experimental life sciences it is often difficult to follow and properly apply the bioinformatical methods in order to unravel the complexity and systemic effects of omics data. Here, we present an integrative bioinformatics pipeline to decipher crucial biological insights from global transcriptome profiling data to validate innovative therapeutics. It is available as a web application for an interactive and simplified analysis without the need for programming skills or deep bioinformatics backgroundThe approach was applied to an ex vivo cardiac model treated with natural anti-fibrotic compounds and we obtained new mechanistic insights into their anti-fibrotic action and molecular interplay with miRNAs in cardiac fibrosis. Several gene pathways associated with proliferation, extracellular matrix processes and wound healing were altered, and we could identify micro (mi) RNA-21-5p and miRNA-223-3p as key molecular components related to the anti-fibrotic treatment. Importantlyour pipeline is not restricted to a specific cell type or disease and can be broadly applied to better understand the unprecedented level of complexity in big data research.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Algorithm; Big data; Cardiac fibrosis; Integrative bioinformatics; MiRNAs; Natural compounds; Transcriptomics; Web application

Interdisciplinary symposium on challenges and opportunities for vaccines: A comprehensive approach of current and future vaccine strategies to improve vaccine effectiveness in complex chronic infectious contexts - Siebner, Alex S.; Habib, Marrium; Osmani, Vanesa; Adegnika, Ayola Akim; Bogdan, Christian; Breloer, Minka; Elliott, Alison; Fathi, Anahita; Hendrickx, Greet; Nono, Justin Komguep; Lang, Roland; Mayer, Johannes U.; et al. (Vaccine: X, 2025)
Vaccination is a key public health intervention, but vaccine immunogenicity, efficacy, and effectiveness vary geographically. These variations are not yet fully understood but are likely influenced by factors such as chronic infections, environmental and genetic differences, social and behavioral factors, and operational challenges, particularly in low- and middle-income countries (LMICs). To address these issues, the “International Symposium on Global Challenges and Opportunities for Vaccines” was held in Kloster Bernried, Germany, bringing together international scientists and stakeholders. Key discussions included: (1) Compromised vaccine immunogenicity due to helminth infections, (2) new vaccine approaches in vaccine development, (3) new frontiers in therapeutic vaccination, (4) challenges of vaccine trials, especially in low-resource settings, and (5) conceptualizing vaccine confidence in low and high resource contexts. The symposium highlighted the challenges of conducting vaccine trials in LMICs, such as participant follow-up, logistics, resources, and building trust. The main recommendation was to improve future vaccine trial designs through a comprehensive, interdisciplinary approach, including tools to evaluate vaccine immunogenicity, efficacy, and effectiveness.
CRIS-Team Scopus Importer:2025-03-14

Kutane Leishmaniasis als Reisedermatose. Klinik, Diagnostik und Therapie - Von Stebut, E.; Schleicher, Ulrike; Bogdan, Christian (Hautarzt, 2012)
Leishmaniasis is a disease with worldwide increasing incidence, which in Germany is almost exclusively observed in patients who have travelled to classical endemic regions such as the Mediterranean basin. Cause of the disease is an infection with protozoan parasites of the genus Leishmania, which are transmitted by sand flies and replicate intracellularly within mammalian hosts. Depending on the inoculated parasite (sub-) species and the immune status of the host, a local cutaneous, diffuse cutaneous, mucocutaneous or visceral form of leishmaniasis will develop. Cutaneous leishmaniasis, which frequently appears only weeks after the bite of a sand fly, starts with the formation of a papule, which subsequently can turn into a skin ulcer. The latter may heal spontaneously after months leaving behind a scar or persist as chronic, non-healing cutaneous leishmaniasis. If cutaneous leishmaniasis is suspected, a sterile skin biopsy followed by appropriate diagnostic measures in a specialized laboratory to identify the pathogen should be performed. For the decision on the type of therapy, several clinical parameters (e.g. number and localization of lesions, immune status) and, most importantly, the underlying parasite (sub-) species need to be considered. Therapy can consist of a variety of topical measures or systemic drug treatment. A modern and safe vaccine does not yet exist. © 2012 Springer-Verlag.
CRIS-Team Scopus Importer:2024-02-26
Keywords: Cutaneous leishmaniasis; Leishmaniasis; Mucocutaneous leishmaniasis; Oriental sore; Therapy

LDHA-Associated Lactic Acid Production Blunts Tumor Immunosurveillance by T and NK Cells - Brand, Almut; Singer, Katrin; Koehl, Gudrun E.; Kolitzus, Marlene; Schoenhammer, Gabriele; Thiel, Annette; Matos, Carina; Bruss, Christina; Klobuch, Sebastian; Peter, Katrin; Kastenberger, Michael; Bogdan, Christian; et al. (Cell Metabolism, 2016)
Elevated lactate dehydrogenase A (LDHA) expression is associated with poor outcome in tumor patients. Here we show that LDHA-associated lactic acid accumulation in melanomas inhibits tumor surveillance by T and NK cells. In immunocompetent C57BL/6 mice, tumors with reduced lactic acid production (Ldha(low)) developed significantly slower than control tumors and showed increased infiltration with IFN-?-producing T and NK cells. However, in Rag2(-/-)?c(-/-) mice, lacking lymphocytes and NK cells, and in Ifng(-/-) mice, Ldha(low) and control cells formed tumors at similar rates. Pathophysiological concentrations of lactic acid prevented upregulation of nuclear factor of activated T cells (NFAT) in T and NK cells, resulting in diminished IFN-? production. Database analyses revealed negative correlations between LDHA expression and T cell activation markers in human melanoma patients. Our results demonstrate that lactic acid is a potent inhibitor of function and survival of T and NK cells leading to tumor immune escape.
EVALuna2:7715

Listeria monocytogenes: No Spreading without NO - Bogdan, Christian (Immunity, 2012)
In infectious disease immunology, inducible nitric oxide (NO) synthase-derived NO is believed to function primarily as an antimicrobial and immunoregulatory molecule. In this issue of Immunity, Cole et al. (2012) show that NO helps the intracellular bacteria Listeria monocytogenes to spread. © 2012 Elsevier Inc.
CRIS-Team Scopus Importer:2024-02-26

Lymphadenopathy in a novel mouse model of Bartonella-induced cat scratch disease results from lymphocyte immigration and proliferation and is regulated by interferon-α/β - Kunz, Stefanie; Oberle, Karin; Sander, Anna; Bogdan, Christian; Schleicher, Ulrike (American Journal of Pathology, 2008)
In immunocompetent humans, cat scratch disease (CSD) is elicited by the Gram-negative bacterium Bartonella henselae and is characterized by a benign regional lymphadenopathy, the pathogenesis of which is poorly understood. Here, we describe a novel mouse model of Bartonella-induced CSD-like disease that allowed us to investigate the mechanisms leading to lymphadenopathy in vivo. In wild-type mice, a subcutaneous inoculation of either viable or inactivated B. henselae led to a strong swelling of the draining lymph node, which was long-lasting despite the rapid elimination of the bacteria. Carboxyfluoresceinand bromodesoxyuridine-labeling experiments showed that lymph node enlargement resulted from modified immigration and enhanced proliferation of lymphocytes, preferentially of B cells. A comparative analysis of B. henselae and the rodent pathogen B. grahamii in wild-type versus interferon-α/ β-receptor I chain-deficient mice revealed that interferon-α/β is not only differentially induced by these two Bartonella species but also exerts an inhibitory effect on the development of lymphadenopathy both in vitro and in vivo. These data demonstrate that the lymphadenopathy of human CSD can be reproduced and studied in a mouse model and provide the first insights into the underlying immunological mechanisms. Copyright © American Society for Investigative Pathology.
CRIS-Team Scopus Importer:2024-02-26

Macrophage-derived nitric oxide initiates T-cell diapedesis and tumor rejection - Sektioglu, Ibrahim M.; Carretero, Rafael; Bender, Noemi; Bogdan, Christian; Garbi, Natalio; Umansky, Viktor; Umansky, Ludmila; Urban, Katharina; Von Knebel-Doeberitz, Magnus; Somasundaram, Veena; Wink, David; Beckhove, Philipp; et al. (OncoImmunology, 2016)
In tumor biology, nitric oxide (NO) is generally regarded as an immunosuppressive molecule that impedes T-cell functions and activation of endothelial cells. Contrasting with this view, we here describe a critical role for NO derived from inducible nitric oxide (iNOS)-expressing tumor macrophages in T-cell infiltration and tumor rejection as shown by iNOS gene deletion, inhibition of iNOS, or NO donors. Specifically, macrophage-derived NO was found to induce on tumor vessels adhesion molecules that were required for T-cell extravasation. Experiments with human endothelial cells revealed a bimodal dose-dependent effect of NO. High doses of NO donors were indeed suppressive but lower, more physiological concentrations, induced adhesion molecules in an NFkB-dependent pathway and preferentially activated transcription of genes involved in lymphocyte diapedesis. iNOS(+) macrophages in tumors appear to generate precisely the amount of NO that promotes endothelial activation and T-cell infiltration. These results will be valuable for the development of strategies designed to overcome the paucity of T-cell infiltration into tumors that is a major obstacle in clinical cancer immunotherapy.
EVALuna2:7726

Macrophages as host, effector and immunoregulatory cells in leishmaniasis: Impact of tissue micro-environment and metabolism - Bogdan, Christian (Cytokine: X, 2020)
Leishmania are protozoan parasites that predominantly reside in myeloid cells within their mammalian hosts. Monocytes and macrophages play a central role in the pathogenesis of all forms of leishmaniasis, including cutaneous and visceral leishmaniasis. The present review will highlight the diverse roles of macrophages in leishmaniasis as initial replicative niche, antimicrobial effectors, immunoregulators and as safe hideaway for parasites persisting after clinical cure. These multiplex activities are either ascribed to defined subpopulations of macrophages (e.g., Ly6ChighCCR2+ inflammatory monocytes/monocyte-derived dendritic cells) or result from different activation statuses of tissue macrophages (e.g., macrophages carrying markers of of classical [M1] or alternative activation [M2]). The latter are shaped by immune- and stromal cell-derived cytokines (e.g., IFN-γ, IL-4, IL-10, TGF-β), micro milieu factors (e.g., hypoxia, tonicity, amino acid availability), host cell-derived enzymes, secretory products and metabolites (e.g., heme oxygenase-1, arginase 1, indoleamine 2,3-dioxygenase, NOS2/NO, NOX2/ROS, lipids) as well as by parasite products (e.g., leishmanolysin/gp63, lipophosphoglycan). Exciting avenues of current research address the transcriptional, epigenetic and translational reprogramming of macrophages in a Leishmania species- and tissue context-dependent manner.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Arginase; Hypoxia; Interferon-α/β; Interferon-γ; Leishmaniasis; Macrophages; Metabolism; Nitric oxide; Phagocyte NADPH oxidase; Tonicity

Macrophages inhibit Coxiella burnetii by the ACOD1-itaconate pathway for containment of Q fever - Kohl, Lisa; Siddique, Md Nur A Alam; Bodendorfer, Barbara; Berger, Raffaela; Preikschat, Annica; Daniel, Christoph; Ölke, Martha; Liebler-Tenorio, Elisabeth; Schulze-Lührmann, Jan; Mauermeir, Michael; Yang, Kai-Ting; Hayek, Inaya; et al. (Embo Molecular Medicine, 2022)
Infection with the intracellular bacterium Coxiella (C.) burnetii can cause chronic Q fever with severe complications and limited treatment options. Here, we identify the enzyme cis-aconitate decarboxylase 1 (ACOD1 or IRG1) and its product itaconate as protective host immune pathway in Q fever. Infection of mice with C. burnetii induced expression of several anti-microbial candidate genes, including Acod1. In macrophages, Acod1 was essential for restricting C. burnetii replication, while other antimicrobial pathways were dispensable. Intratracheal or intraperitoneal infection of Acod1−/− mice caused increased C. burnetii burden, weight loss and stronger inflammatory gene expression. Exogenously added itaconate restored pathogen control in Acod1−/− mouse macrophages and blocked replication in human macrophages. In axenic cultures, itaconate directly inhibited growth of C. burnetii. Finally, treatment of infected Acod1−/− mice with itaconate efficiently reduced the tissue pathogen load. Thus, ACOD1-derived itaconate is a key factor in the macrophage-mediated defense against C. burnetii and may be exploited for novel therapeutic approaches in chronic Q fever.
CRIS-Team Scopus Importer:2022-12-16
Keywords: Cis-aconitate decarboxylase 1; Coxiella burnetii; Immune responsive gene 1; immunometabolism; itaconate

Management of chronic osteomyelitis of the tibia with life-threatening complications under negative pressure wound therapy and isolation of Helcococcus kunzii - Stanger, Katrin M.; Albert, Frauke; Kneser, Ulrich; Bogdan, Christian; Horch, Raymund E. (International Wound Journal, 2015)
We report the case of an 86-year-old man with severe wound infection originating from a chronic crural ulcer of the lower limb, which under negative pressure wound therapy led to excessive tissue necrosis and perforation of the anterior tibial artery. A swab taken 10 and 7 days preoperatively was positive for Helcococcus kunzii. H. kunzii has been described as a potentially pathogenic organism. The questions whether the negative pressure wound therapy itself caused the bleeding or the negative pressure wound therapy, which generates an anaerobic atmosphere, has triggered the growth and invasion of the facultative anaerobic bacterium H. kunzii and owing to the infection the artery perforated or whether the bacteria has no influence at all remain currently unanswered. After surgical debridement the signs of infection were completely eliminated, and a free musculocutaneous flap led to rapid healing of the wound. Following which H. kunzii was no longer detectable.
EVALuna2:7649

Mechanisms controlling bacterial infection in myeloid cells under hypoxic conditions - Hayek, Inaya; Schatz, Valentin; Bogdan, Christian; Jantsch, Jonathan; Lührmann, Anja (Cellular and Molecular Life Sciences, 2020)
Various factors of the tissue microenvironment such as the oxygen concentration influence the host–pathogen interaction. During the past decade, hypoxia-driven signaling via hypoxia-inducible factors (HIF) has emerged as an important factor that affects both the pathogen and the host. In this chapter, we will review the current knowledge of this complex interplay, with a particular emphasis given to the impact of hypoxia and HIF on the inflammatory and antimicrobial activity of myeloid cells, the bacterial responses to hypoxia and the containment of bacterial infections under oxygen-limited conditions. We will also summarize how low oxygen concentrations influence the metabolism of neutrophils, macrophages and dendritic cells. Finally, we will discuss the consequences of hypoxia and HIFα activation for the invading pathogen, with a focus on Pseudomonas aeruginosa, Mycobacterium tuberculosis, Coxiella burnetii, Salmonella enterica and Staphylococcus aureus. This includes a description of the mechanisms and microbial factors, which the pathogens use to sense and react to hypoxic conditions.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Bacteria; Dendritic cells; HIF1α; Hypoxia; Infection; Macrophages; Metabolism; Neutrophils

Mechanisms of immunological control of Anaplasma phagocytophilum in mice. - Rinkler, Christina; Kern, Yvonne; Bogdan, Christian; Von Loewenich, Friederike D. (Annals of the New York Academy of Sciences, 2005)
CRIS-Team Scopus Importer:2024-02-26

Medical Student Self-Assessment of Knowledge About Vaccinations and the Quality of Vaccination Training - Roberts, Kimberly; Streng, Andrea; Göttler, David; Hartmann, Katrin; Peter-Kern, Martina; Roggendorf, Hedwig; Bogdan, Christian; Jilg, Wolfgang; Plentz, Annelie; Hübner, Johannes; Schober, Tilmann; Liese, Johannes (Deutsches Ärzteblatt international, 2022)
CRIS-Team Scopus Importer:2022-12-02

M-EndoL: MRSA in der Versorgung am Lebensende - Untersuchung der Auswirkungen von MRSA- (oder andere multiresistente Keim-) Kolonisation oder Infektion auf Patienten am Lebensende, deren Angehörige, Teammitglieder und Einrichtungen - Ostgathe, Christoph; Lang, Frieder; Bogdan, Christian; Sieber, Cornel; Schöffski, Oliver; Stiel, Stephanie; Heckel, Maria; Tiedtke, Johanna; Sturm, Alexander; Adelhardt, Thomas (Zeitschrift für Palliativmedizin, 2014)

Meningokokken-Meningitis - Esse, Jan; Träger, Johannes; Bogdan, Christian (TumorDiagnostik & Therapie, 2024)
CRIS-Team Scopus Importer:2024-05-24

Molecular diagnosis of skin infections using paraffin-embedded tissue - review and interdisciplinary consensus - Sunderkoetter, Cord; Becker, Karsten; Kutzner, Heinz; Meyer, Thomas; Bloedorn-Schlicht, Norbert; Reischl, Udo; Nenoff, Pietro; Geissdoerfer, Walter; Graeser, Yvonne; Herrmann, Mathias; Kuehn, Joachim; Bogdan, Christian (Journal der Deutschen Dermatologischen Gesellschaft, 2018)
Nucleic acid amplification techniques (NATs), such as PCR, are highly sensitive and specific methods that have become valuable supplements to culture and serology in the diagnosis of infectious disorders. However, especially when using formalin-fixed and paraffin-embedded tissue, these techniques are associated with both false-negative and false-positive results, a pitfall that is frequently misjudged. Representatives of the German Society of Hygiene and Microbiology (DGHM) and the German Society of Dermatology (DDG) therefore set out to develop a consensus - in the form of a review article - on the appropriate indications for NATs using paraffin-embedded tissue, its contraindications, and the key points to be considered in the pre- and post-analytical phase. Given that fresh, naive tissue is preferably to be used in the workup of a suspected infection, PCR analysis on paraffin sections represents an exception. The latter may be considered if an infection is suspected at a later point in time and fresh tissue has not been preserved or can no longer be obtained. Potential indications include confirmation of histologically suspected infections with Leishmania spp., Bartonella spp., Rickettsia spp., or in case of ecthyma contagiosum. Infections with, for example, mycobacteria or RNA viruses, on the other hand, are not considered useful indications for NATs using paraffin sections. In order to avoid misinterpretation of test results, it is essential that laboratory reports on NATs using paraffin-embedded tissue contain information on the indication/diagnostic circumstances, the required and chosen pre-analytical steps, the limitations of the method, and on diagnostic alternatives.
EVALuna2:33303

Monocyte-Derived signals activate human natural Killer cells in response to Leishmania Parasites - Messlinger, Helena; Sebald, Heidi; Heger, Lukas; Dudziak, Diana; Bogdan, Christian; Schleicher, Ulrike (Frontiers in Immunology, 2018)
Activated natural killer (NK) cells release interferon (IFN)-gamma, which is crucial for the control of intracellular pathogens such as Leishmania. In contrast to experimental murine leishmaniasis, the human NK cell response to Leishmania is still poorly characterized. Here, we investigated the interaction of human blood NK cells with promastigotes of different Leishmania species (Leishmania major, Leishmania mexicana, Leishmania infantum, and Leishmania donovani). When peripheral blood mononuclear cells or purified NK cells and monocytes (all derived from healthy blood donors from Germany without a history of leishmaniasis) were exposed to promastigotes, NK cells showed increased surface expression of the activation marker CD69. The extent of this effect varied depending on the Leishmania species; differences between dermotropic and viscerotropic L. infantum strains were not observed. Upregulation of CD69 required direct contact between monocytes and Leishmania and was partly inhibitable by anti-interleukin (IL)-18. Unexpectedly, IL-18 was undetectable in most of the supernatants (SNs) of monocyte/parasite cocultures. Confocal fluorescence microscopy of non-permeabilized cells revealed that Leishmania-infected monocytes trans-presented IL-18 to NK cells. Native, but not heat-treated SNs of monocyte/Leishmania cocultures also induced CD69 on NK cells, indicating the involvement of a soluble heat-labile factor other than IL-18. A role for the NK cell-activating cytokines IL-1 beta, IL-2, IL-12, IL-15, IL-21, and IFN-alpha/beta was excluded. The increase of CD69 was not paralleled by NK cell IFN-gamma production or enhanced cytotoxicity. However, prior exposure of NK cells to Leishmania parasites synergistically increased their IFN-gamma release in response to IL-12, which was dependent on endogenous IL-18. CD1c(+) dendritic cells were identified as possible source of Leishmania-induced IL-12. Finally, we observed that direct contact between Leishmania and NK cells reduced the expression of CD56 mRNA and protein on NK cells. We conclude that Leishmania activate NK cells via trans-presentation of IL-18 by monocytes and by a monocyte-derived soluble factor. IL-12 is needed to elicit the IFN-gamma-response of NK cells, which is likely to be an important component of the innate control of the parasite.
EVALuna2:33305

Mucocutaneous Leishmaniasis due to Leishmania infantum Infection - Linse, Kai Philipp; Bogdan, Christian; Haenssle, Holger A.; Toberer, Ferdinand (Acta Dermato-Venereologica, 2022)
CRIS-Team Scopus Importer:2022-08-05

Multidrug-resistant bacterial microorganisms (MDRO) in end-of-life care: development of recommendations for hospitalized patients using a mixed-methods approach - Heckel, Maria; Stiel, Stephanie; Herbst, Franziska A.; Tiedtke, Johanna; Sturm, Alexander; Adelhardt, Thomas; Bogdan, Christian; Sieber, Cornel; Schöffski, Oliver; Lang, Frieder; Ostgathe, Christoph (Supportive Care in Cancer, 2018)
Purpose Palliative care professionals are frequently confronted with patients colonized or infected with MDRO. One major challenge is how to balance necessary isolation measures and social inclusion as one of the main principles of palliative and end-of-life care. To date, MDRO-specific policies and protocols vary widely between institutions. Aim: provide empirical recommendations on how to deal with hospitalized MDRO patients in end-of-life care.Methods Recommendations were developed based on (i) initial results of face-to-face interviews and focus groups, (ii) impartial experts' comments and consensus on the draft via online survey and (iii) a face-to-face meeting with consortium members to finalize recommendations. Findings of 158 interviews and six focus groups (39 participants) with patients, family caregivers, staff members and institutional stakeholders contributed to the recommendations. The assessments of 17 experts were considered.Results In total, 21 recommendations were approved. The recommended strategy in dealing with MDRO at the end of life allows case-based application of protection and isolation measures. MDRO diagnostics and therapy involve screening at admission. The recommendations suggest consideration of required accommodation facilities, provided material as well as staff and time resources. The recommendations further highlight the importance of providing for strategies enabling the patient's social inclusion and provision of verbal and written information about MDRO for patients and family caregivers, transparent medical documentation, and staff member training.Conclusion The recommendations summarize the perspectives of individuals and groups affected by MDRO at the end of life and provide practical guidance for clinical routine. Further dissemination and implementation requirements are discussed and should contain the evaluation of the knowledge, views, worries, and anxieties of the target groups.
Keywords: Palliative care; Terminal care; Drug resistance; Multiple; Practice guideline; Methicillin-resistant Staphylococcus aureus; Empirical research

Multilocus Sequence Analysis of Clinical "Candidatus Neoehrlichia mikurensis" Strains from Europe - Grankvist, Anna; Moore, Edward R. B.; Stadler, Liselott Svensson; Pekova, Sona; Bogdan, Christian; Geißdörfer, Walter; Grip-Linden, Jenny; Brandstrom, Kenny; Marsal, Jan; Andreasson, Kristofer; Lewerin, Catharina; Welinder-Olsson, Christina; et al. (Journal of Clinical Microbiology, 2015)
"Candidatus Neoehrlichia mikurensis" is the tick-borne agent of neoehrlichiosis, an infectious disease that primarily affects immunocompromised patients. So far, the genetic variability of "Ca. Neoehrlichia" has been studied only by comparing 16S rRNA genes and groEL operon sequences. We describe the development and use of a multilocus sequence analysis (MLSA) protocol to characterize the genetic diversity of clinical "Ca. Neoehrlichia" strains in Europe and their relatedness to other species within the Anaplasmataceae family. Six genes were selected: ftsZ, clpB, gatB, lipA, groEL, and 16S rRNA. Each MLSA locus was amplified by real-time PCR, and the PCR products were sequenced. Phylogenetic trees of MLSA locus relatedness were constructed from aligned sequences. Blood samples from 12 patients with confirmed "Ca. Neoehrlichia" infection from Sweden (n = 9), the Czech Republic (n = 2), and Germany (n = 1) were analyzed with the MLSA protocol. Three of the Swedish strains exhibited identical lipA sequences, while the lipA sequences of the strains from the other nine patients were identical to each other. One of the Czech strains had one differing nucleotide in the clpB sequence from the sequences of the other 11 strains. All 12 strains had identical sequences for the genes 16S rRNA, ftsZ, gatB, and groEL. According to the MLSA, among the Anaplasmataceae, "Ca. Neoehrlichia" is most closely related to Ehrlichia ruminantium, less so to Anaplasma phagocytophilum, and least to Wolbachia endosymbionts. To conclude, three sequence types of infectious "Ca. Neoehrlichia" were identified: one in the west of Sweden, one in the Czech Republic, and one spread throughout Europe.
EVALuna2:7679

Myeloid Cell-Derived HIF-1? Promotes Control of Leishmania major - Schatz, Valentin; Strussmann, Yannic; Mahnke, Alexander; Schley, Gunnar; Waldner, Maximilian; Ritter, Uwe; Wild, Jens; Willam, Carsten; Dehne, Nathalie; Brune, Bernhard; Mcniff, Jennifer M.; Colegio, Oscar R.; et al. (Journal of Immunology, 2016)
Hypoxia-inducible factor-1? (HIF-1?), which accumulates in mammalian host organisms during infection, supports the defense against microbial pathogens. However, whether and to what extent HIF-1? expressed by myeloid cells contributes to the innate immune response against Leishmania major parasites is unknown. We observed that Leishmania-infected humans and L. major-infected C57BL/6 mice exhibited substantial amounts of HIF-1? in acute cutaneous lesions. In vitro, HIF-1? was required for leishmanicidal activity and high-level NO production by IFN-?/LPS-activated macrophages. Mice deficient for HIF-1? in their myeloid cell compartment had a more severe clinical course of infection and increased parasite burden in the skin lesions compared with wild-type controls. These findings were paralleled by reduced expression of type 2 NO synthase by lesional CD11b(+) cells. Together, these data illustrate that HIF-1? is required for optimal innate leishmanicidal immune responses and, thereby, contributes to the cure of cutaneous leishmaniasis.
EVALuna2:2181

Myeloid cells and the microenvironment, microorganisms and metabolism - Bogdan, Christian; Steinkasserer, Alexander (Immunobiology, 2015)
EVALuna2:7673

Nasal carriage of methicillin-resistant Staphylococcus aureus (MRSA) at a palliative care unit: A prospective single service analysis - Heckel, Maria; Geißdörfer, Walter; Herbst, Franziska A.; Stiel, Stephanie; Ostgathe, Christoph; Bogdan, Christian (PLoS ONE, 2017)
BACKGROUND: The emergence of multidrug-resistant bacterial microorganisms is a particular challenge for the health care systems. Little is known about the occurrence of methicillin-resistant Staphylococcus aureus (MRSA) and multidrug-resistant Gram-negative bacteria (MDRGNB) in patients of palliative care units (PCU). AIM: The primary aim of this study was to determine the carriage of MRSA among patients of a PCU at a German University Hospital and to assess whether the positive cases would have been detected by a risk-factor-based screening-approach. DESIGN: Between February 2014 and January 2015 patients from our PCU were tested for MRSA carriage within 48 hours following admission irrespective of pre-existing risk factors. In addition, risk factors for MRSA colonization were assessed. Samples from the nostrils and, if applicable, from pre-existing wounds were analysed by standardized culture-based laboratory techniques for the presence of MRSA and of other bacteria and fungi. Results from swabs taken prior to admission were also recorded if available. RESULTS: 297 out of 317 patients (93.7%) fulfilled one or more MRSA screening criteria. Swabs from 299 patients were tested. The detection rate was 2.1% for MRSA. All MRSA cases would have been detected by a risk-factor-based screening-approach. Considering the detected cases and the results from swabs taken prior to admission, 4.1% of the patients (n = 13) were diagnosed with MRSA and 4.1% with MDRGNB (n = 13), including two patients with MRSA and MDRGNB (0.6%). The rate of MRSA carriage in PCU patients (4.1%) was elevated compared to the rate seen in the general cohort of patients admitted to our University Hospital (2.7%). CONCLUSIONS: PCU patients have an increased risk to carry MRSA compared to other hospitalized patients. Although a risk factor-based screening is likely to detect all MRSA carriers amongst PCU patients, we rather recommend a universal screening to avoid the extra effort to identify the few risk factor-negative patients (<7%). As we did not perform a systematic MDRGNB screening, further studies are needed to determine the true prevalence of MDRGNB amongst PCU patients.
EVALuna2:33307

Natural killer cells in experimental and human leishmaniasis. - Bogdan, Christian (Frontiers in Cellular and Infection Microbiology, 2012)
Infections with parasites of the genus Leishmania lead to a rapid, but transient activation of natural killer (NK) cells. In mice activation of NK cells requires a toll-like-receptor 9-dependent stimulation of dendritic cells (DC) which is followed by the production of IL-12. Although NK cells appear to be non-essential for the ultimate control of cutaneous and visceral leishmaniasis (VL) and can exhibit immunosuppressive functions, they form an important source of interferon (IFN)-γ, which elicits antileishmanial activity in macrophages and helps to pave a protective T helper cell response. In contrast, the cytotoxic activity of NK cells is dispensable, because Leishmania-infected myeloid cells are largely resistant to NK-mediated lysis. In human cutaneous and VL, the functional importance of NK cells is suggested by reports that demonstrate (1) a direct activation or inhibition of NK cells by Leishmania promastigotes, (2) the suppression of NK cell numbers or activity during chronic, non-healing infections, and (3) the recovery of NK cell activity following treatment. This review aims to provide an integrated view on the migration, activation, inhibition, function, and therapeutic modulation of NK cells in experimental and human leishmaniasis.
CRIS-Team Scopus Importer:2024-02-26

Neuerungen in den aktuellen STIKO-Empfehlungen 2018/2019 - Bogdan, Christian (Pädiatrische Praxis, 2019)
The latest recommendations of the German Standing Committee on Vaccination (STIKO), which have been in force since August 23, 2018, include the following major amendments: • Universal use of a quadrivalent influenza vaccine, which in addition to the two influenza A virus types (H1N1, H3N2) contains two influenza B lines. • Routine human papilloma virus vaccination for all children at the age of 9 to 14. • Simultaneous active and passive immunization against tetanus also in patients with minor or clean wounds if immunity to tetanus is not existing or documented.
CRIS-Team Scopus Importer:2021-04-20

Nitric oxide-mediated regulation of ferroportin-1 controls macrophage iron homeostasis and immune function in Salmonella infection - Nairz, Manfred; Schleicher, Ulrike; Schroll, Andrea; Sonnweber, Thomas; Theurl, Igor; Ludwiczek, Susanne; Talasz, Heribert; Brandacher, Gerald; Moser, Patrizia L.; Muckenthaler, Martina U.; Fang, Ferric C.; Bogdan, Christian; et al. (Journal of Experimental Medicine, 2013)
Nitric oxide (NO) generated by inducible NO synthase 2 (NOS2) affects cellular iron homeostasis, but the underlying molecular mechanisms and implications for NOS2-dependent pathogen control are incompletely understood. In this study, we found that NO up-regulated the expression of ferroportin-1 (Fpn1), the major cellular iron exporter, in mouse and human cells. Nos2-/- macrophages displayed increased iron content due to reduced Fpn1 expression and allowed for an enhanced iron acquisition by the intracellular bacterium Salmonella typhimurium. Nos2 gene disruption or inhibition of NOS2 activity led to an accumulation of iron in the spleen and splenic macrophages. Lack of NO formation resulted in impaired nuclear factor erythroid 2-related factor-2 (Nrf2) expression, resulting in reduced Fpn1 transcription and diminished cellular iron egress. After infection of Nos2-/- macrophages or mice with S. typhimurium, the increased iron accumulation was paralleled by a reduced cytokine (TNF, IL-12, and IFN-γ) expression and impaired pathogen control, all of which were restored upon administration of the iron chelator deferasirox or hyperexpression of Fpn1 or Nrf2. Thus, the accumulation of iron in Nos2-/- macrophages counteracts a proinflammatory host immune response, and the protective effect of NO appears to partially result from its ability to prevent iron overload in macrophages. ©2013 Nairz et al.
CRIS-Team Scopus Importer:2024-02-26

Nitric oxide synthase in innate and adaptive immunity: an update - Bogdan, Christian (Trends in Immunology, 2015)
Thirty years after the discovery of its production by activated macrophages, our appreciation of the diverse roles of nitric oxide (NO) continues to grow. Recent findings have not only expanded our understanding of the mechanisms controlling the expression of NO synthases (NOS) in innate and adaptive immune cells, but have also revealed new functions and modes of action of NO in the control and escape of infectious pathogens, in T and B cell differentiation, and in tumor defense. I discuss these findings, in the context of a comprehensive overview of the various sources and multiple reaction partners of NO, and of the regulation of NOS2 by micromilieu factors, antisense RNAs, and 'unexpected' cytokines.
EVALuna2:7675

Novel GM-CSF signals via IFN-γR/IRF-1 and AKT/mTOR license monocytes for suppressor function - Ribechini, Eliana; Hutchinson, James A.; Hergovits, Sabine; Heuer, Marion; Lucas, Jorg; Schleicher, Ulrike; Garrote, Ana-Laura Jordan; Potter, Sarah J.; Riquelme, Paloma; Brackmann, Heike; Muller, Nora; Raifer, Hartmann; et al. (Blood Advances, 2017)
Granulocyte-macrophage colony-stimulating factor (GM-CSF) controls proliferation and survival of myeloid cells including monocytes. Here, we describe a time-dependent licensing process driven by GM-CSF in murine Ly6Chigh and human CD14+ monocytes that disables their inflammatory functions and promotes their conversion into suppressor cells. This 2-step licensing of monocytes requires activation of the AKT/mTOR/mTORC1 signaling cascade by GM-CSF followed by signaling through the interferon-γ receptor (IFN-γR)/interferon regulatory factor-1 (IRF-1) pathway. Only licensing-dependent adaptations in Toll-like receptor/inflammasome, IFN-γR, and phosphatidylinositol 3-kinase/AKT/mTOR signaling lead to stabilized expression of inducible nitric oxide synthase by mouse and indoleamine 2,3-dioxygenase (IDO) by human monocytes, which accounts for their suppressor activity. This study suggests various myeloid cells with characteristics similar to those described for monocytic myeloid-derived suppressor cells, Mreg, or suppressor macrophages may arise from licensed monocytes. Markers of GM-CSF-driven monocyte licensing, including p-Akt, p-mTOR, and p-S6, distinguish inflammatory monocytes from potentially suppressive monocytes in peripheral blood of patients with high-grade glioma.
EVALuna2:36433

Obituary Prof. Victoria Kolb-Bachofen - Foerstermann, Ulrich; Bogdan, Christian; Pfeilschifter, Josef M.; Mayer, Bernd M. (Nitric Oxide-Biology and Chemistry, 2014)
EVALuna2:7658

Orofacial clefts alter early life oral microbiome maturation towards higher levels of potentially pathogenic species: A prospective observational study - Seidel, Corinna Lesley; Strobel, Karin; Weider, Matthias; Tschaftari, Marco; Unertl, Christoph; Willershausen, Ines; Weber, Manuel; Hörning, André; Morhart, Patrick; Schneider, Michael; Beckmann, Matthias; Bogdan, Christian; et al. (Journal of Oral Microbiology, 2023)
Orofacial clefts (OFC) present different phenotypes with a postnatal challenge for oral microbiota development. In order to investigate the impact of OFC on oral microbiota, smear samples from 15 neonates with OFC and 17 neonates without OFC were collected from two oral niches (tongue, cheek) at two time points, i.e. after birth (T0: Ø3d OFC group; Ø2d control group) and 4–5 weeks later (T1: Ø32d OFC group; Ø31d control group). Subsequently, the samples were analyzed using next-generation sequencing. We detected a significant increase of alpha diversity and anaerobic and Gram-negative species from T0 to T1 in both groups. Further, we found that at T1 OFC neonates presented a significantly lower alpha diversity (lowest values for high cleft severity) and significantly higher levels of Enterobacteriaceae (Citrobacter, Enterobacter, Escherichia-Shigella, Klebsiella), Enterococcus, Bifidobacterium, Corynebacterium, Lactocaseibacillus, Staphylococcus, Acinetobacter and Lawsonella compared to controls. Notably, neonates with unilateral and bilateral cleft lip and palate (UCLP/BCLP) presented similarities in beta diversity and a mixture with skin microbiota. However, significant differences were seen in neonates with cleft palate only compared to UCLP/BCLP with higher levels of anaerobic species. Our findings revealed an influence of OFC as well as cleft phenotype and severity on postnatal oral microbiota maturation.
CRIS-Team Scopus Importer:2023-01-20
Keywords: early life dysbiosis; microbiome maturation; neonates; oral microbiome; Orofacial clefts

Patients' views on the impact of multi-drug-resistant bacterial microorganisms (MDRO) in end-of-life care - A qualitative study using principles of Grounded Theory. - Sturm, Alexander; Ostgathe, Christoph; Stiel, Stephanie; Heckel, Maria; Herbst, Franziska A.; Adelhardt, Thomas; Schöffski, Oliver; Bogdan, Christian; Tiedtke, Johanna; Lang, Frieder; Sieber, Cornel (SPRINGER, 2018)

Pneumococcal vaccination (2): Plea for the recommendations of the Standing Committee on Vaccination (STIKO) Plädoyer für STIKO-Empfehlungen - Falkenhorst, Gerhard; Leidel, Jan; Bogdan, Christian (Deutsches Ärzteblatt international, 2017)
CRIS-Team Scopus Importer:2024-02-26

Pneumokokkenimpfung im Säuglings- und im Kleinkindalter: Epidemiologische und immunologische Basis der pädiatrischen Pneumokokkenimpfung - Vygen-Bonnet, Sabine; Schlaberg, Johanna; Kremer-Flach, Katrin; Perriat, Delphine; Bogdan, Christian (Monatsschrift Kinderheilkunde, 2024)
Streptococcus pneumoniae causes various childhood diseases. Invasive pneumococcal diseases (IPD) are rare. They mainly affect infants and toddlers and can have a severe or fatal course. Pneumococcal vaccines are the most effective form of prevention. This article provides an overview of the current epidemiological situation of IPD in childhood in Germany, the available vaccines and the immunological basis of pediatric pneumococcal vaccination. Data from the German Paediatric Surveillance Unit (GPSU) on IPD in children and adolescents under 16 years of age were analyzed. In addition, published data on the serotype distribution, the safety and effectiveness of pneumococcal conjugate vaccines (PCV) and vaccination coverage in Germany are presented. The pneumococcal immune defence and the mode of action of conjugate vaccines as well as the current recommendations of the Standing Committee on Vaccination (STIKO) at the Robert Koch Institute and aspects of its implementation are explained. As the main disease burden of IPD is in infancy, the STIKO recommends early pneumococcal vaccination for all infants as well as for children and adolescents with certain underlying diseases. Nevertheless, in Germany currently around 25% of all children up to their 2nd birthday are not or not fully immunized against pneumococci.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Conjugate vaccine; Infants; Invasive pneumococcal disease; Meningitis; pneumococcal; Sepsis

Practicability of hygienic wrapping of touchscreen operated mobile devices in a clinical setting - Hammon, Matthias; Kunz, Hans Bernd; Dinzl, Veronika; Kammerer, Ferdinand J.; Schwab, Siegfried; Bogdan, Christian; Uder, Michael; Schlechtweg, Philipp (PLoS ONE, 2014)
To prove effectiveness of wrapping tablet computers in order to reduce microbiological contamination and to evaluate whether a plastic bag-covered tablet leads to impaired user satisfaction or touchscreen functionality.Within a period of 11 days 115 patients were provided with a tablet computer while waiting for their magnetic resonance imaging examination. Every day the contamination of the surface of the tablet was determined before the first and after the final use. Before the device was handed over to a patient, it was enclosed in a customized single-use plastic bag, which was analyzed for bacterial contamination after each use. A questionnaire was applied to determine whether the plastic bag impairs the user satisfaction and the functionality of the touchscreen.Following the use by patients the outside of the plastic bags was found to be contaminated with various bacteria (657.5 ± 368.5 colony forming units/day); some of them were potentially pathogenic. In contrast, the plastic bag covered surface of the tablet was significantly less contaminated (1.7 ± 1.9 colony forming units/day). Likewise, unused plastic bags did not show any contamination. 11% of the patients reported problems with the functionality of the touchscreen. These patients admitted that they had never used a tablet or a smartphone before.Tablets get severely contaminated during usage in a clinical setting. Wrapping with a customized single-use plastic bag significantly reduces microbiological contamination of the device, protects patients from the acquisition of potentially pathogenic bacteria and hardly impairs the user satisfaction and the functionality of the touchscreen.
EVALuna2:7657

Presence of Infected Gr-1intCD11bhiCD11cint Monocytic Myeloid Derived Suppressor Cells Subverts T Cell Response and Is Associated With Impaired Dendritic Cell Function in Mycobacterium avium-Infected Mice - Abdissa, Ketema; Nerlich, Andreas; Beineke, Andreas; Ruangkiattikul, Nanthapon; Pawar, Vinay; Heise, Ulrike; Janze, Nina; Falk, Christine; Bruder, Dunja; Schleicher, Ulrike; Bogdan, Christian; Weiss, Siegfried; et al. (Frontiers in Immunology, 2018)
Myeloid-derived suppressor cells (MDSC) are immature myeloid cells with immunomodulatory function. To study the mechanism by which MDSC affect antimicrobial immunity, we infected mice with two M. avium strains of differential virulence, highly virulent Mycobacterium avium subsp. avium strain 25291 (MAA) and low virulent Mycobacterium avium subsp. hominissuis strain 104 (MAH). Intraperitoneal infection with MAA, but not MAH, caused severe disease and massive splenic infiltration of monocytic MDSC (M-MDSC; Gr-1intCD11bhiCD11cint) expressing inducible NO synthase (Nos2) and bearing high numbers of mycobacteria. Depletion experiments demonstrated that M-MDSC were essential for disease progression. NO production by M-MDSC influenced antigen-uptake and processing by dendritic cells and proliferation of CD4+ T cells. M-MDSC were also induced in MAA-infected mice lacking Nos2. In these mice CD4+ T cell expansion and control of infection were restored. However, T cell inhibition was only partially relieved and arginase (Arg) 1-expressing M-MDSC were accumulated. Likewise, inhibition of Arg1 also partially rescued T cell proliferation. Thus, mycobacterial virulence results in the induction of M-MDSC that block the T cell response in a Nos2- and Arg1-dependent manner.
EVALuna2:36424

Processing and secretion of guanylate binding protein-1 depend on inflammatory caspase activity - Naschberger, Elisabeth; Geissdorfer, Walter; Bogdan, Christian; Tripal, Philipp; Kremmer, Elisabeth; Stürzl, Michael; Britzen-Laurent, Nathalie (Journal of Cellular and Molecular Medicine, 2017)
Human guanylate binding protein-1 (GBP-1) belongs to the family of large GTPases. The expression of GBP-1 is inducible by inflammatory cytokines, and the protein is involved in inflammatory processes and host defence against cellular pathogens. GBP-1 is the first GTPase which was described to be secreted by eukaryotic cells. Here, we report that precipitation of GBP-1 with GMP-agarose from cell culture supernatants co-purified a 47-kD fragment of GBP-1 (p47-GBP-1) in addition to the 67-kD full-length form. MALDI-TOF sequencing revealed that p47-GBP-1 corresponds to the C-terminal helical part of GBP-1 and lacks most of the globular GTPase domain. In silico analyses of protease target sites, together with cleavage experiments in vitro and in vivo, showed that p67-GBP-1 is cleaved by the inflammatory caspases 1 and 5, leading to the formation of p47-GBP-1. Furthermore, the secretion of p47-GBP-1 was found to occur via a non-classical secretion pathway and to be dependent on caspase-1 activity but independent of inflammasome activation. Finally, we showed that p47-GBP-1 represents the predominant form of secreted GBP-1, both in cell culture supernatants and, in vivo, in the cerebrospinal fluid of patients with bacterial meningitis, indicating that it may represent the biologically active form of extracellular GBP-1. These findings confirm the involvement of caspase-1 in non-classical secretion mechanisms and open novel perspectives for the extracellular function of secreted GBP-1.
EVALuna2:7752

Proliferation-independent GM-CSF and M-CSF signals control monocyte conversion into monocytic myeloid-derived suppressor cells - Ribechini, E.; Hutchinson, J. A.; Hergovits, S.; Heuer, M.; Lucas, J.; Schleicher, Ulrike; Garrote, A. L. Jordan; Potter, S. J.; Riquelme, P.; Brackmann, H.; Mueller, N.; Raifer, H.; et al. (2017)
EVALuna2:33309

Protection against RNA-induced liver damage by myeloid cells requires type I interferon and IL-1 receptor antagonist in mice - Conrad, Elea; Resch, Theresa K.; Gogesch, Patricia; Kalinke, Ulrich; Bechmann, Ingo; Bogdan, Christian; Waibler, Zoe (Hepatology, 2014)
Cell types and mechanisms involved in type I interferon (IFN)-mediated anti-inflammatory effects are poorly understood. Upon injection of artificial double-stranded RNA (poly(I:C)), we observed severe liver damage in type I IFN-receptor (IFNAR) chain 1-deficient mice, but not in wild-type (WT) controls. Studying mice with conditional IFNAR ablations revealed that IFNAR triggering of myeloid cells is essential to protect mice from poly(I:C)-induced liver damage. Accordingly, in poly(I:C)-treated WT, but not IFNAR-deficient mice, monocytic myeloid-derived suppressor cells (MDSCs) were recruited to the liver. Comparing WT and IFNAR-deficient mice with animals deficient for the IFNAR on myeloid cells only revealed a direct IFNAR-dependent production of the anti-inflammatory cytokine interleukin-1 receptor antagonist (IL-1RA) that could be assigned to liver-infiltrating cells. Upon poly(I:C) treatment, IFNAR-deficient mice displayed both a severe lack of IL-1RA production and an increased production of proinflammatory IL-1?, indicating a severely imbalanced cytokine milieu in the liver in absence of a functional type I IFN system. Depletion of IL-1? or treatment with recombinant IL-1RA both rescued IFNAR-deficient mice from poly(I:C)-induced liver damage, directly linking the deregulated IL-1? and IL-1RA production to liver pathology. Conclusion: Type I IFN signaling protects from severe liver damage by recruitment of monocytic MDSCs and maintaining a balance between IL-1? and IL-1RA production.
EVALuna2:7653

Rapid Healing of Cutaneous Leishmaniasis by High-Frequency Electrocauterization and Hydrogel Wound Care with or without DAC N-055: A Randomized Controlled Phase IIa Trial in Kabul - Jebran, Ahmad Fawad; Schleicher, Ulrike; Steiner, Reto; Wentker, Pia; Mahfuz, Farouq; Stahl, Hans-Christian; Amin, Faquir Mohammad; Bogdan, Christian; Stahl, Kurt-Wilhelm (Plos Neglected Tropical Diseases, 2014)
Anthroponotic cutaneous leishmaniasis (CL) due to Leishmania (L.) tropica infection is a chronic, frequently disfiguring skin disease with limited therapeutic options. In endemic countries healing of ulcerative lesions is often delayed by bacterial and/or fungal infections. Here, we studied a novel therapeutic concept to prevent superinfections, accelerate wound closure, and improve the cosmetic outcome of ACL.From 2004 to 2008 we performed a two-armed, randomized, double-blinded, phase IIa trial in Kabul, Afghanistan, with patients suffering from L. tropica CL. The skin lesions were treated with bipolar high-frequency electrocauterization (EC) followed by daily moist-wound-treatment (MWT) with polyacrylate hydrogel with (group I) or without (group II) pharmaceutical sodium chlorite (DAC N-055). Patients below age 5, with facial lesions, pregnancy, or serious comorbidities were excluded. The primary, photodocumented outcome was the time needed for complete lesion epithelialization. Biopsies for parasitological and (immuno)histopathological analyses were taken prior to EC (1(st)), after wound closure (2(nd)) and after 6 months (3(rd)). The mean duration for complete wound closure was short and indifferent in group I (59 patients, 43.1 d) and II (54 patients, 42 d; p = 0.83). In patients with Leishmania-positive 2(nd) biopsies DAC N-055 caused a more rapid wound epithelialization (37.2 d vs. 58.3 d; p = 0.08). Superinfections occurred in both groups at the same rate (8.8%). Except for one patient, reulcerations (10.2% in group I, 18.5% in group II; p = 0.158) were confined to cases with persistent high parasite loads after healing. In vitro, DAC N-055 showed a leishmanicidal effect on pro- and amastigotes.Compared to previous results with intralesional antimony injections, the EC plus MWT protocol led to more rapid wound closure. The tentatively lower rate of relapses and the acceleration of wound closure in a subgroup of patients with parasite persistence warrant future studies on the activity of DAC N-055.ClinicalTrails.gov NCT00947362.
EVALuna2:7647

Rapid phenotypic antimicrobial susceptibility testing of Gram-negative rods directly from positive blood cultures using the novel Q-linea ASTar system - Esse, Jan; Träger, Johannes; Valenza, Giuseppe; Bogdan, Christian; Held, Jürgen (Journal of Clinical Microbiology, 2023)
Adequate and timely antibiotic therapy is crucial for the treatment of sepsis. Innovative systems, like the Q-linea ASTar, have been developed to perform rapid antimicrobial susceptibility testing (AST) directly from positive blood cultures (BCs). We conducted a prospective study to evaluate ASTar under real-life conditions with a focus on time-to-result and impact on antimicrobial therapy. Over 2 months, all positive BCs that showed Gram-negative rods upon microscopy were tested with the ASTar and our standard procedure (VITEK 2 from short-term culture). Additionally, we included multidrug-resistant Gram-negative bacteria from our archive. Both methods were compared to broth microdilution. In total, 78 bacterial strains (51 prospective and 27 archived) were tested. ASTar covered 94% of the species encountered. The categorical and essential agreement was 95.6% and 90.7%, respectively. ASTar caused 2.4% minor, 2.0% major, and 2.4% very major errors. The categorical agreement was similar to standard procedure. The average time between BC sampling and the availability of the antibiogram for the attending physician was 28 h 49 min for ASTar and 44 h 18 min for standard procedure. ASTar correctly identified all patients who required an escalation of antimicrobial therapy and 75% of those who were eligible for de-escalation. In conclusion, ASTar provided reliable AST results and significantly shortened the time to obtain an antibiogram. However, the percentage of patients that will profit from ASTar in a low-resistance setting is limited, and it is currently unclear if a change of therapy 29 h after BC sampling will have a significant impact on the patient’s prognosis.
CRIS-Team Scopus Importer:2023-12-08
Keywords: AST; blood stream infection; RAST; scum plate method; sepsis; VITEK

Ratiometric luminescence 2D in vivo imaging and monitoring of mouse skin oxygenation - Hofmann, Julian; Meier, Robert J.; Mahnke, Alexander; Schatz, Valentin; Brackmann, Florian; Trollmann, Regina; Bogdan, Christian; Liebsch, Gregor; Wang, Xu Dong; Wolfbeis, Otto S.; Jantsch, Jonathan (Methods and Applications in Fluorescence, 2013)
Tissue oxygenation plays a critical role in the pathogenesis of various diseases, but non-invasive, robust and user-friendly methods for its measurement in vivo still need to be established. Here, we are presenting an in vivo oxygen-detection system that uses ratiometric luminescence imaging (RLI) as a readout scheme to determine the skin oxygen tension of mouse hind footpads via side-by-side comparison with more established techniques including luminescence-lifetime imaging using planar sensor films and the polarographic electrode as the gold standard. We also demonstrate that this technology allows the detection of changes in mouse skin tissue oxygenation induced by subjecting mice to systemic hypoxia. The data demonstrate oxygen imaging based on RLI to be a most useful tool for reliably and easily analyzing and monitoring skin tissue oxygenation in vivo. This technology will advance our understanding of local regulation of skin tissue oxygenation in various disease conditions.
CRIS-Team Scopus Importer:2024-02-26

Reactogenicity correlates only weakly with humoral immunogenicity after COVID-19 vaccination with BNT162b2 mRNA (Comirnaty®) - Held, Jürgen; Esse, Jan; Tascilar, Koray; Steininger, Philipp; Schober, Kilian; Irrgang, Pascal; Alsalameh, Rayya; Tenbusch, Matthias; Seggewies, Christof; Bogdan, Christian (Vaccines, 2021)
mRNA vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), such as BNT162b2 (Comirnaty®), have proven to be highly immunogenic and efficient but also show marked reactogenicity, leading to adverse effects (AEs). Here, we analyzed whether the severity of AEs predicts the antibody response against the SARS-CoV-2 spike protein. Healthcare workers without prior SARS-CoV-2 infection, who received a prime-boost vaccination with BNT162b2, completed a standardized electronic questionnaire on the duration and severity of AEs. Serum specimens were collected two to four weeks after the boost vaccination and tested with the COVID-19 ELISA IgG (Vircell-IgG), the LIAISON® SARS-CoV-2 S1/S2 IgG CLIA (DiaSorin-IgG) and the iFlash-2019-nCoV NAb surrogate neutralization assay (Yhlo-NAb). A penalized linear regression model fitted by machine learning was used to correlate AEs with antibody levels. Eighty subjects were enrolled in the study. Systemic, but not local, AEs occurred more frequently after the boost vaccination. Elevated SARS-CoV-2 IgG antibody levels were measured in 92.5% of subjects with Vircell-IgG and in all subjects with DiaSorin-IgG and Yhlo-NAb. Gender, age and BMI showed no association with the antibody levels or with the AEs. The linear regression model identified headache, malaise and nausea as AEs with the greatest variable importance for higher antibody levels (Vircell-IgG and DiaSorin-IgG). However, the model performance for predicting antibody levels from AEs was very low for Vircell-IgG (squared correlation coefficient r2 = 0.04) and DiaSorin-IgG (r2 = 0.06). AEs did not predict the surrogate neutralization (Yhlo-NAb) results. In conclusion, AEs correlate only weakly with the SARS-CoV-2 spike protein antibody levels after COVID-19 vaccination with BNT162b2 mRNA.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Adverse effects; Adverse reactions; Antibody; BioNTech; Machine learning; MRNA vaccine; Pfizer; SARS-CoV-2; Side effects

Regulation of Lymphocytes by Nitric Oxide - Bogdan, Christian (Humana Press Inc., 2011)
Shortly after the identification of nitric oxide (NO) as a product of macrophages, it was discovered that NO generated by inducible NO synthase (iNOS) inhibits the proliferation of T lymphocytes. Since then, it has become clear that iNOS activity also regulates the development, differentiation, and/or function of various types of T cells and B cells and also affects NK cells. The three key mechanisms underlying the iNOS-dependent immunoregulation are (a) the modulation of signaling processes by NO, (b) the depletion of arginine, and (c) the alteration of accessory cell functions. This chapter highlights important principles of iNOS-dependent immunoregulation of lymphocytes and also reviews more recent evidence for an effect of endothelial or neuronal NO synthase in lymphocytes.
CRIS-Team Scopus Importer:2024-02-26
Keywords: Arginase; B lymphocytes; Endothelial nitric oxide synthase; Inducible nitric oxide synthase; Myeloid (-derived) suppressor cells; Natural killer cells; Neuronal nitric oxide synthase; Nitric oxide; T lymphocytes

Relevance of inducible nitric oxide synthase for immune control of Mycobacterium avium subspecies paratuberculosis infection in mice - Abdissa, Ketema; Ruangkiattikul, Nanthapon; Ahrend, Wiebke; Nerlich, Andreas; Beineke, Andreas; Laarmann, Kristin; Janze, Nina; Lobermeyer, Ulrike; Suwandi, Abdulhadi; Falk, Christine; Schleicher, Ulrike; Weiss, Siegfried; et al. (Virulence, 2020)
Mycobacterium avium subspecies paratuberculosis (MAP) causes Johne's disease (JD), an incurable chronic intestinal bowel disease in ruminants. JD occurs worldwide and causes enormous economic burden in dairy industry. Research on JD pathobiology is hampered by its complexity which cannot completely be mimicked by small animal models. As a model the mouse allows dissecting some pathogenicity features of MAP. However, for unknown reasons MAP exhibits reduced growth in granulomas of infected mice compared to other Mycobacterium avium subspecies. Here, we characterized immune reactions of MAP-infected C57BL/6 mice. After infection, mice appeared fully immunocompetent. A strong antigen-specific T cell response was elicited indicated by IFN gamma production of splenic T cells re-stimulated with MAP antigens. Function of splenic dendritic cells and proliferation of adoptively transferred antigen-specific CD4(+) T cells was unaltered. Isolated splenic myeloid cells from infected mice revealed that MAP resides in CD11b(+) macrophages. Importantly, sorted CD11b(+)CD11c(-) cells expressed high level of type 2 nitric oxide synthase (NOS2) but only low levels of pro- and anti-inflammatory cytokines. Correspondingly, MAP-infected MAC2 expressing myeloid cells in spleen and liver granuloma displayed strong expression of NOS2. In livers of infected Nos2(-/-)mice higher bacterial loads, more granuloma and larger areas of tissue damage were observed 5 weeks post infection compared to wild type mice. In vitro, MAP was sensitive to NO released by a NO-donor. Thus, a strong T cell response and concomitant NOS2/NO activity appears to control MAP infection, but allows development of chronicity and pathogen persistence. A similar mechanism might explain persistence of MAP in ruminants.
CRIS-Team WoS Importer:2020-05-29

Relevant Aspects on cutaneous Leishmaniasis in Mallorca - Burmann, Sven-Niklas; Sunderkoetter, Cord; Boeer-Auer, Almut; Oellig, Frank; Fischer, Marcellus; Bogdan, Christian; Michalowitz, Alena-Lioba; Kreuter, Alexander (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
CRIS-Team WoS Importer:2022-05-13

Relevante Aspekte zur kutanen Leishmaniose auf Mallorca - Burmann, Sven Niklas; Sunderkötter, Cord; Böer-Auer, Almut; Oellig, Frank; Fischer, Marcellus; Bogdan, Christian; Michalowitz, Alena Lioba; Kreuter, Alexander (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
CRIS-Team Scopus Importer:2022-04-29

Renal leishmaniasis as unusual cause of nephrotic syndrome in an HIV patient - Amann, Kerstin Ute; Bogdan, Christian; Harrer, Thomas; Rech, Jürgen (Journal of the American Society of Nephrology, 2012)
Renal involvement is a rare complication in HIV-1-infected patients leading to various pathologies and clinical symptoms. In addition to the classic HIV-1-associated nephropathy with collapsing-type focal segmental glomerulosclerosis and characteristic tubulocystic changes, which is more common in Afro-American than in Caucasian HIV-1 patients, immune complex GNs such as membranous GN and membranoproliferative GN are particularly common renal manifestations. Besides HIV-1 itself, a number of opportunistic infections may cause renal disease in HIV-1-infected patients. In this study, we report an unusual case of HIV-1 infection with a severe renal manifestation of systemic leishmaniasis that developed years after repeated visits to Mediterranean countries. The case presents several remarkable clinical, pathologic, and therapeutic aspects that may be important for daily clinical practice. Copyright © 2012 by the American Society of Nephrology.
CRIS-Team Scopus Importer:2021-02-03

Reply to Martin and Dauby - Kling, Kerstin; Domingo, Cristina; Bogdan, Christian; Wilder-Smith, Annelies; Harder, Thomas (Clinical Infectious Diseases, 2022)
CRIS-Team WoS Importer:2023-01-06

Reply to Raoult - Wenneras, Christine; Bloemberg, Guido; Bogdan, Christian (Clinical Infectious Diseases, 2014)
EVALuna2:7652

Resolution of Cutaneous Leishmaniasis and Persistence of Leishmania major in the Absence of Arginase 1 - Paduch, Katrin; Debus, Andrea; Rai, Baplu; Schleicher, Ulrike; Bogdan, Christian (Journal of Immunology, 2019)
Arginase (Arg) 1 is expressed by hematopoietic (e.g., macrophages) and nonhematopoietic cells (e.g., endothelial cells) and converts L-arginine into ornithine and urea. The enzyme is implicated in tissue repair but also antagonizes the production of NO by type 2 NO synthase in myeloid cells and thereby impedes the control of intracellular parasites such as Leishmania major. In this study, we tested whether Arg1 is required for spontaneous healing of acute cutaneous leishmaniasis in C57BL/6 mice and for lifelong parasite persistence in draining lymph nodes (dLNs) of healed mice. In vitro, bone marrow-derived macrophages and lymphoid endothelial cells readily expressed Arg1 in response to IL-4 and/or IL-13, whereas skin or dLN fibroblasts failed to do so, even during hypoxia. In vivo, Arg1 was found in skin lesions and, to a much lower extent, also in dLNs of acutely infected C57BL/6 mice but became undetectable at both sites after healing. Deletion of Arg1 in hematopoietic and endothelial cells using Tie2Cre(+/-) Arg1(fl/fl) C57BL/6 mice abolished the expression of Arg1 in skin lesions and dLNs but did not affect development and resolution of skin lesions, parasite burden, NO production, or host cell tropism of L. major during the acute or persistent phase of infection. Similar to wild-type controls, parasites persisting in Arg1-deficient mice favored NO synthase 2-negative areas and mainly resided in myeloid cells and fibroblasts. We conclude that Arg1 expression by hematopoietic and endothelial cells is completely dispensable for clinical resolution of cutaneous leishmaniasis and for long-term persistence of L. major.
CRIS-Team WoS Importer:2019-03-06

Rhinophyma-Like Cutaneous Leishmaniasis due to Leishmania aethiopica Treated Successfully with Liposomal Amphotericin B - Kirchberger, Michael Constantin; Schliep, Stefan; Bogdan, Christian (American Journal of Tropical Medicine and Hygiene, 2019)
CRIS-Team WoS Importer:2019-03-20

S1-Leitlinie Diagnostik und Therapie der kutanen und mukokutanen Leishmaniasis in Deutschland - Boecken, Gerhard; Weitzel, Thomas; Sunderkötter, Cord; Fischer, Marcellus; Von Stebut-Boschitz, Esther; Bogdan, Christian; Pietras, Mathias; Anders, Gerlind; Harms-Zwingenberger, Gundel; Burchard, Gerd; Bialek, Ralf; Lippert, Ute; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2009)
CRIS-Team Scopus Importer:2024-02-26

Safety and effectiveness of acellular pertussis vaccination during pregnancy: a systematic review - Vygen-Bonnet, Sabine; Hellenbrand, Wiebke; Garbe, Edeltraut; von Kries, Rüdiger; Bogdan, Christian; Heininger, Ulrich; Röbl-Mathieu, Marianne; Harder, Thomas (BMC Infectious Diseases, 2020)
BACKGROUND: Infants < 3 months of age are at highest risk for developing severe complications after pertussis. The majority of pregnant women has low concentrations of pertussis-specific antibodies and thus newborns are insufficiently protected by maternally transferred antibodies. Acellular pertussis vaccination during pregnancy was recently implemented in various countries. Here, we assessed the evidence for safety and effectiveness of pertussis vaccination during pregnancy. METHODS: We searched Medline, Embase, and ClinicalTrials.gov from January 1st 2010 to January 10th 2019. We assessed risk of bias (ROB) using the Cochrane ROB tool and ROBINS-I. We evaluated the quality of evidence using the GRADE approach. RESULTS: We identified 1273 articles and included 22 studies (14 for safety; 8 for effectiveness), comprising 1.4 million pregnant women in safety studies and 855,546 mother-infant-pairs in effectiveness studies. No significant differences between vaccinated and unvaccinated women and their infants were observed for safety outcomes with the exception of fever and chorioamnionitis. Compared to no vaccination, three studies showed a significantly increased relative risk for the presence of the ICD-9 code for chorioamnionitis in electronic patient data after pertussis vaccination. However, no study reported an increased risk for clinical sequelae of chorioamnionitis after vaccination during pregnancy, such as preterm birth or neonatal intensive care unit admission. Vaccine effectiveness against pertussis in infants of immunized mothers ranged from 69 to 91% for pertussis prevention, from 91 to 94% for prevention of hospitalization and was 95% for prevention of death due to pertussis. Risk of bias was serious to critical for safety outcomes and moderate to serious for effectiveness outcomes. GRADE evidence quality was moderate to very low, depending on outcome. CONCLUSION: Although an increased risk for a diagnosis of fever and chorioamnionitis was detected in pregnant women after pertussis vaccination, there was no association with a higher frequency of clinically relevant sequelae. Vaccine effectiveness for prevention of infant pertussis, hospitalization and death is high. Pertussis vaccination during pregnancy has an overall positive benefit-risk ratio. In view of the overall quality of available evidence ongoing surveillance of chorioamnionitis and its potential sequelae is recommended when pertussis vaccination in pregnancy is implemented. TRIAL REGISTRATION: PROSPERO CRD42018087814, CRD42018090357.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Acellular pertussis vaccine; Chorioamnionitis; Pertussis; Pregnancy; Tdap

Salvage therapy with Sodium chlorosum (formerly DAC N-055) for cases of refractory lupoid cutaneous leishmaniasis: Results from a compassionate use study with 0.09% Sodium chlorosum in amphiphilic basic cream - Molkara, Sara; Poursoltani, Elaheh; Stahl, Kurt Wilhelm; Maleki, Masoud; Khamesipour, Ali; Bogdan, Christian; Salehi, Maryam; Goyonlo, Vahid Mashayekhi (BMC Infectious Diseases, 2019)
Background: Lupoid cutaneous leishmaniasis (LCL) is known as a rare but serious complication of anthroponotic cutaneous leishmaniasis (ACL) resistant to conventional treatments. Sodium chlorosum, a pro-oxidative preparation of pharmaceutical sodium chlorite (NaClO2), has been successfully used for the treatment of Old World cutaneous leishmaniasis lesions (OWCL) and of some LCL cases in Afghanistan. This clinical trial study aimed to evaluate the effect of a last resort therapy with topical 0.09% sodium chlorosum on LCL in Iran. Methods: Twenty Iranian patients (12 women and 8 men) with LCL refractory to treatment were included in this salvage study. A magistral preparation of sodium chlorosum (10 mM NaClO2 in amphiphilic basic cream) was applied twice daily to the lesions for 6 weeks and continued up to 12 weeks in patients who showed a clinical response within the first 6 weeks. Responders were followed up for a maximum of 1 year. Lesions were photographed during weekly visits. Disappearance of erythema and indurated lesions were rated as complete clinical response. Results: Patients with a mean age of 28.6 (±24.3) and with an ACL proven lesion history of 3.8 (±1.4) years were treated for an average of 7.9 (±1.8) weeks. At the end of the treatment period (12th week), a complete response was observed in 9 of 20 patients (45%). During the one-year follow-up period, LCL lesions recurred in 4 of these 9 patients (with one patient showing only a tiny lesion) and one case lost to follow up whereas the other four remained completely lesion-free. Mild temporary side-effects such as erythema and itching were seen in 4 of 20 patients (20%). Conclusions: Topical sodium chlorosum showed promising therapeutic results and can be considered as safe, painless, and relatively effective treatment for LCL, an ethical prerequisite for a two-armed controlled trial. Trial registration: This study was registered in Iranian registry of clinical trials on 2019-02-02 with registration number IRCT20190114042356N1.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Lupoid cutaneous leishmaniasis; Sodium chlorosum (formerly DAC N-055); Treatment

Scavenging of bacteria or bacterial products by magnetic particles functionalized with a broad-spectrum pathogen recognition receptor motif offers diagnostic and therapeutic applications - Friedrich, Bernhard; Lyer, Stefan; Janko, Christina; Unterweger, Harald; Brox, Regine; Cunningham, Sarah; Dutz, Silvio; Taccardi, Nicola; Bikker, Floris J.; Hurle, Katrin; Sebald, Heidi; Lenz, Malte; et al. (Acta Biomaterialia, 2022)
Sepsis is a dysregulated host response of severe bloodstream infections, and given its frequency of occurrence and high mortality rate, therapeutic improvements are imperative. A reliable biomimetic strategy for the targeting and separation of bacterial pathogens in bloodstream infections involves the use of the broad-spectrum binding motif of human GP-340, a pattern-recognition receptor of the scavenger receptor cysteine rich (SRCR) superfamily that is expressed on epithelial surfaces but not found in blood. Here we show that these peptides, when conjugated to superparamagnetic iron oxide nanoparticles (SPIONs), can separate various bacterial endotoxins and intact microbes (E. coli, S. aureus, P. aeruginosa and S. marcescens) with high efficiency, especially at low and thus clinically relevant concentrations. This is accompanied by a subsequent strong depletion in cytokine release (TNF, IL-6, IL-1β, Il-10 and IFN-γ), which could have a direct therapeutic impact since escalating immune responses complicates severe bloodstream infections and sepsis courses. SPIONs are coated with aminoalkylsilane and capture peptides are orthogonally ligated to this surface. The particles behave fully cyto- and hemocompatible and do not interfere with host structures. Thus, this approach additionally aims to dramatically reduce diagnostic times for patients with suspected bloodstream infections and accelerate targeted antibiotic therapy. Statement of significance: Sepsis is often associated with excessive release of cytokines. This aspect and slow diagnostic procedures are the major therapeutic obstacles. The use of magnetic particles conjugated with small peptides derived from the binding motif of a broad-spectrum mucosal pathogen recognition protein GP-340 provides a highly efficient scavenging platform. These peptides are not found in blood and therefore are not subject to inhibitory mechanisms like in other concepts (mannose binding lectine, aptamers, antibodies). In this work, data are shown on the broad bacterial binding spectrum, highly efficient toxin depletion, which directly reduces the release of cytokines. Host cells are not affected and antibiotics not adsorbed. The particle bound microbes can be recultured without restriction and thus be used directly for diagnostics.
CRIS-Team Scopus Importer:2022-03-11
Keywords: GP-340; Magnetic nanoparticles; Pathogen binding; Sepsis; SRCR domain

Serum (1→3)-β-D-glucan and galactomannan levels in patients with cystic fibrosis: a retrospective cohort study - Traeger, Johannes; Melichar, Volker Otto; Meyer, Renate; Rauh, Manfred; Bogdan, Christian; Held, Jürgen (BMC Pulmonary Medicine, 2018)
BACKGROUND: Aspergillus fumigatus is frequently encountered in sputum samples of patients with cystic fibrosis (CF), which traditionally has been interpreted as saprophytic airway colonization. However, this mere bystander role has been challenged by recent data. There is now evidence that Aspergillus fumigatus accelerates the decline of pulmonary function. (1→3)-β-D-glucan (BDG) and galactomannan (GM) are highly sensitive fungal biomarkers that are used to diagnose invasive fungal disease. However, their diagnostic value in CF patients is largely unknown. METHODS: We conducted a retrospective cohort study on 104 CF patients to determine whether serum BDG and GM levels correlate with parameters such as Aspergillus-positive sputum cultures and lung function. RESULTS: Aspergillus fumigatus was persistently detected in 22 of the 104 CF patients (21%). Mean serum BDG and GM levels in the Aspergillus-positive patients were significantly higher than in those without persistent Aspergillus detection (89 versus 40 pg/ml [p = 0.022] and 0.30 versus 0.15 ODI [p = 0.013], respectively). 27 and 7 patients had elevated BDG (≥ 60 pg/ml) or GM levels (> 0.5 ODI), respectivly. BDG and GM levels showed a significant correlation (p = 0.004). Patients with increased serum concentrations of BDG were more frequently Aspergillus-positive (40.7 versus 14.3%, p = 0.004) and had a significantly lower forced expiratory volume in one second (FEV1) than patients with a normal BDG (61.6 versus 77.1%, p = 0.007). In the multivariate analysis, BDG but not GM or the growth of A. fumigatus, proved to be an independent predictor for the FEV1. CONCLUSIONS: CF patients with persistent Aspergillus detection have elevated BDG and GM levels which ranged between healthy and invasively infected patients. Serum BDG may be superior to GM and fungal culture in predicting an impaired lung function in CF patients.
EVALuna2:35821

SOP - Dealing with multidrug-resistant pathogens on the palliative care unit - Ostgathe, Christoph; Stachura, Peter; Hofmann, Sonja; Van Oorschot, Birgitt; Oechsle, Karin; Bogdan, Christian; Kunz, Hans Bernd; Foertsch, Baerbel; Klein, Carsten (Onkologe, 2017)
EVALuna2:33311

SOP - Handling of multidrug-resistant Pathogens in the Palliative Care Unit - Ostgathe, Christoph; Stachura, Peter; Hofmann, Sonja; Van Oorschot, Birgitt; Oechsle, Karin; Bogdan, Christian; Kunz, Hans Bernd; Foertsch, Baerbel; Klein, Carsten (Onkologe, 2018)
EVALuna2:36423

SOP - Management of multiresistent Pathogens in the Palliative Care Unit - Ostgathe, Christoph; Stachura, Peter; Heckel, Maria; Brunner, Sarah; Gahr, Susanne; Hofmann, Sonja; Van Oorschot, Birgitt; Oechsle, Karin; Bogdan, Christian; Kunz, Bernd; Foertsch, Baerbel; Klein, Carsten (Die Onkologie, 2022)
Infobox 1 SOP aus der Reihe „SOPs zur palliativen Versorgung von Patienten im Netzwerk der deutschen Comprehensive Cancer Center“, erstellt von der AG Palliativmedizin der von der Deutschen Krebshilfe geförderten Comprehensive Cancer Center (CCC
CRIS-Team WoS Importer:2022-10-07

SOP – Umgang mit multiresistenten Erregern auf der Palliativstation - Ostgathe, Christoph; Stachura, Peter; Hofmann, Sonja; van Oorschot, Birgitt; Oechsle, Karin; Bogdan, Christian; Kunz, Bernd; Förtsch, Bärbel; Klein, Carsten (Onkologe, 2017)
CRIS-Team Scopus Importer:2024-02-26

SPIONs functionalized with small peptides for binding of lipopolysaccharide, a pathophysiologically relevant microbial product. - Karawacka, Weronika; Janko, Christina; Unterweger, Harald; Mühlberger, Marina; Lyer, Stefan; Taccardi, Nicola; Mokhir, Andriy; Jira, Wolfgang; Peukert, Wolfgang; Boccaccini, Aldo R.; Kolot, Mikhail; Strauss, Richard; et al. (Colloids and Surfaces B-Biointerfaces, 2018)
Systemic inflammation such as sepsis represents an acute life-threatening condition, to which often no timely remedy can be found. A promising strategy may be to functionalize magnetic nanoparticles with specific peptides, derived from the binding motives of agglutinating salivary proteins, that allow immobilization of pathogens. In this work, superparamagnetic iron oxide nanoparticles with stable polycondensed aminoalkylsilane layer were developed, to which the heterobifunctional linkers N-succinimidyl 3-(2-pyridyldithio)-propanoate (SDPD) and N-succinimidyl bromoacetate (SBA) were bound. These linkers were further chemoselectively reacted with the thiol group of singularly present cysteines of selected peptides. The resulting functional nanoparticles underwent a detailed physicochemical characterization. The biocompatibility of the primarily coated aminoalkylsilane particles was also investigated. To test the pathogen-binding efficacy of the particles, the lipopolysaccharide-immobilization capacity of the peptide-coated particles was compared with free peptides. Here, one particle-bound peptide species succeeded in capturing 90% of the toxin, whereas the degree of immobilization of the toxin with a system that varied in the sequence of the peptide dropped to 35%. With these promising results, we hope to develop extracorporeal magnetic clearance systems for removing pathogens from the human body in order to accelerate diagnosis and alleviate acute disease conditions such as sepsis.

Striking inflammation from both sides: Manganese(II) pentaazamacrocyclic SOD mimics act also as nitric oxide dismutases: A single-cell study - Filipovic, Milos; Koh, Alaric C.W.; Arbault, Stephane; Niketic, Vesna; Debus, Andrea; Schleicher, Ulrike; Bogdan, Christian; Guille, Manon; Lemaitre, Fréderic; Amatore, Christian; Ivanovic-Burmazovic, Ivana (Angewandte Chemie International Edition, 2010)
[Figure Presented] macrophage Removing cytotoxics: A Mn- pentaazamacrocycle removes NO; Cy and their ONOO product as shown by real-time amperometry at single cells (see picture). This is the first compound able to completely abolish the cytotoxic effects of reactive oxygen (ROS) and reactive nitrogen species (RNS) in inflammation. © 2010 Wlley-VCH Verlag GmbH & Co. KGaA.

Successful eradication of newly acquired MRSA in six of seven patients with cystic fibrosis applying a short-term local and systemic antibiotic scheme - Kiefer, Alexander; Bogdan, Christian; Melichar, Volker O. (BMC Pulmonary Medicine, 2018)
BACKGROUND: In individuals with cystic fibrosis (CF), colonization with methicillin-resistant Staphylococcus aureus (MRSA) was reported to be associated with a deterioration of pulmonary disease as reflected by an accelerated decline in lung function. Thus, an early eradication of MRSA could be beneficial in these patients. Here, we report on an intensified MRSA eradication protocol. METHODS: Since 2012 a protocol for the eradication of newly acquired MRSA has been used in our CF Clinic, combining oral rifampicin and fusidic acid, inhaled vancomycin, nasal mupirocin, local antiseptic treatment and hygienic directives all of which are applied for only 7 days during an inpatient hospital stay. RESULTS: Since 2012 seven patients (3 male, 4 female; age range 4 to 30 years) newly acquired MRSA. In 6 of the 7 patients (86%) successful eradication of MRSA was achieved upon first treatment using the protocol described above. In one patient a second course of treatment was performed which, however, also failed to eliminate the colonizing MRSA. CONCLUSIONS: Our protocol led to an eradication rate of 86%. The impact of each individual component of the protocol remains to be determined.
EVALuna2:33304

Targeted Second-Line Treatment - Jantsch, Jonathan; Bogdan, Christian (Deutsches Ärzteblatt, 2010)
CRIS-Team Scopus Importer:2024-02-26

The Aspergillus galactomannan Ag VIRCLIA® Monotest and the sõna Aspergillus galactomannan lateral flow assay show comparable performance for the diagnosis of invasive aspergillosis - Küpper, Corinna; Erb, Timothy Moritz; Träger, Johannes; Meintker, Lisa; Valenza, Giuseppe; Bogdan, Christian; Held, Jürgen (Mycoses, 2024)
Background: Rapid galactomannan tests, such as the sõna Aspergillus GM Lateral Flow Assay (GM-LFA) and the Aspergillus Galactomannan Ag VIRCLIA® Monotest (GM-Monotest), which are suitable for the analysis of single samples, have the potential to accelerate diagnosis of invasive aspergillosis (IA). Objectives: To compare the performance of the GM-Monotest and the GM-LFA for the diagnosis of IA. Patients/Methods: Two patient cohorts were analysed: adults who had received an allogeneic haematopoietic stem-cell transplant (alloHSCT-cohort) and patients with proven/probable IA from a 5-year period (cross-sectional IA-cohort). In the alloHSCT-cohort, weekly serum samples were tested, whereas in the cross-sectional IA-cohort sera and bronchoalveolar lavage fluids were analysed. The diagnostic performance was calculated using two definitions for positivity: (1) a single positive GM result and (2) at least two positive GM results from consecutive samples. IA classification followed EORTC/MSG 2019. Results: The alloHSCT-cohort included 101 patients. Four had proven/probable IA, 26 possible IA and 71 no IA. The specificity for one positive serum and two consecutively positive sera was 88.7% and 100% (GM-Monotest) and 85.9% and 98.6% (GM-LFA). Comparison of ROC curves in the alloHSCT-cohort showed no significant difference. The cross-sectional IA-cohort included 59 patients with proven/probable IA. The sensitivity for one positive sample and two consecutively positive samples was 83.1% and 55.1% (GM-Monotest) and 86.4% and 71.4% (GM-LFA). Conclusions: Both assays showed comparable diagnostic performance with a higher sensitivity for the GM-LFA if two consecutive positive samples were required for positivity. However, due to poor reproducibility, positive GM-LFA results should always be confirmed.
CRIS-Team Scopus Importer:2024-08-16
Keywords: antigen; invasive fungal disease; invasive fungal infection; Platelia; POCT; point-of-care test

The Brief Case: Cutaneous Sporotrichosis in an Immunocompetent Patient after Travel to Peru - Wolff, Dorit; Feldt, Torsten; Reifenberger, Julia; Sebald, Heidi; Bogdan, Christian (Journal of Clinical Microbiology, 2018)
EVALuna2:36422

The immunomicrotope of Leishmania control and persistence - Bogdan, Christian; islam, Noor-A-kasida; Barinberg, David; Soulat, Didier; Schleicher, Ulrike; Rai, Baplu (Trends in Parasitology, 2024)
Leishmania is an intracellular protozoan transmitted by sand fly vectors; it causes cutaneous, mucocutaneous, or visceral disease. Its growth and survival are impeded by type 1 T helper cell responses, which entail interferon (IFN)-γ-mediated macrophage activation. Leishmania partially escapes this host defense by triggering immune cell and cytokine responses that favor parasite replication rather than killing. Novel methods for in situ analyses have revealed that the pathways of immune control and microbial evasion are strongly influenced by the tissue context, the micro milieu factors, and the metabolism at the site of infection, which we collectively term the ‘immunomicrotope’. Understanding the components and the impact of the immunomicrotope will enable the development of novel strategies for the treatment of chronic leishmaniasis.
CRIS-Team Scopus Importer:2024-09-13
Keywords: evasion; immunity; Leishmania parasites; leishmaniasis; micro milieu factors; persistence

The impact of the type 1 and type 2 T Helper cell concept on novel vaccine design with emphasis on protection against Leishmania Parasites - Bogdan, Christian; Röllinghoff, Martin (De Gruyter Mouton, 2012)
CRIS-Team Scopus Importer:2024-02-26

TNF-Mediated Restriction of Arginase 1 Expression in Myeloid Cells Triggers Type 2 NO Synthase Activity at the Site of Infection - Schleicher, Ulrike; Paduch, Katrin; Debus, Andrea; Obermeyer, Stephanie; Koenig, Till; Kling, Jessica C.; Ribechini, Eliana; Dudziak, Diana; Mougiakakos, Dimitrios; Murray, Peter J.; Ostuni, Renato; Koerner, Heinrich; et al. (Cell Reports, 2016)
Neutralization or deletion of tumor necrosis factor (TNF) causes loss of control of intracellular pathogens in mice and humans, but the underlying mechanisms are incompletely understood. Here, we found that TNF antagonized alternative activation of macrophages and dendritic cells by IL-4. TNF inhibited IL-4-induced arginase 1 (Arg1) expression by decreasing histone acetylation, without affecting STAT6 phosphorylation and nuclear translocation. In Leishmania major-infected C57BL/6 wild-type mice, type 2 nitric oxide (NO) synthase (NOS2) was detected in inflammatory dendritic cells or macrophages, some of which co-expressed Arg1. In TNF-deficient mice, Arg1 was hyperexpressed, causing an impaired production of NO in situ. A similar phenotype was seen in L. major-infected BALB/c mice. Arg1 deletion in hematopoietic cells protected these mice from an otherwise lethal disease, although their disease-mediating T cell response (Th2, Treg) was maintained. Thus, deletion or TNF-mediated restriction of Arg1 unleashes the production of NO by NOS2, which is critical for pathogen control.
EVALuna2:7700

Transcription factor Fra-1 targets arginase-1 to enhance macrophage-mediated inflammation in arthritis - Hannemann, Nicole; Cao, Shan; Eriksson, Daniel; Schnelzer, Anne; Jordan, Jutta; Eberhardt, Martin; Schleicher, Ulrike; Rech, Jürgen; Uebe, Steffen; Ekici, Arif Bülent; Canete, Juan D.; Chen, Xiaoxiang; et al. (Journal of Clinical Investigation, 2019)
The polarization of macrophages is regulated by transcription factors, such as NF-κB and activator protein 1 (AP-1). In this manuscript, we delineated the role of the transcription factor Fos-related antigen 1 (Fra-1) during macrophage activation and development of arthritis. Network level interaction analysis of microarray data derived from Fra-1- or Fra-2-deficient macrophages revealed a central role of Fra-1, but not of Fra-2, in orchestrating the expression of genes related to wound response, Toll-like receptor activation, and interleukin signaling. ChIP sequencing and standard ChIP analyses of macrophages identified arginase 1 (Arg1) as a target of Fra-1. Luciferase reporter assays revealed that Fra-1 downregulated Arg1 expression by direct binding to the promoter region. Using macrophage-specific Fra-1- or Fra-2-deficient mice, we observed enhanced expression and activity of Arg1 and a reduction of arthritis in the absence of Fra-1, but not of Fra-2. This phenotype was reversed by treatment with the arginase inhibitor Nω-hydroxy-nor-arginine, while -arginine supplementation increased arginase activity and alleviated arthritis, supporting the notion that reduced arthritis in macrophage-specific Fra-1-deficient mice resulted from enhanced Arg1 expression and activity. Moreover, patients with active rheumatoid arthritis (RA) showed increased Fra-1 expression in the peripheral blood and elevated Fra-1 protein in synovial macrophages compared with RA patients in remission. In addition, the Fra-1/ARG1 ratio in synovial macrophages was related to RA disease activity. In conclusion, these data suggest that Fra-1 orchestrates the inflammatory state of macrophages by inhibition of Arg1 expression and thereby impedes the resolution of inflammation.
CRIS-Team Scopus Importer:2019-07-16

Trauma as a Trigger Factor for the First clinical Manifestation of cutaneous Leishmaniasis - Hiernickel, J.; Bogdan, Christian; Erfurt-Berge, Cornelia (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Two Cases of Severe Tick-Borne Encephalitis in Rituximab-Treated Patients in Germany: Implications for Diagnosis and Prevention - Steininger, Philipp; Bobinger, Tobias; Dietrich, Wenke; Lee, De-Hyung; Knott, Michael; Bogdan, Christian; Korn, Klaus; Lang, Roland (Open Forum Infectious Diseases, 2017)
Rituximab (RTX) has become a standard therapy for certain B cell malignancies and autoimmune diseases. We report 2 RTX-treated patients who developed severe tick-borne encephalitis virus (TBEV) infection. The inability to generate new antibody responses renders RTX-treated patients susceptible to TBEV, impedes laboratory diagnosis, and necessitates preventive vaccination in endemic areas.
EVALuna2:22593

Two cases of successful treatment of multilesional cutaneous leishmaniasis with liposomal amphotericin B - Butsch, Florian; Faulde, Michael; Debus, Andrea; Bogdan, Christian; Von Stebut, Esther (Journal der Deutschen Dermatologischen Gesellschaft, 2013)
CRIS-Team Scopus Importer:2024-02-26

Type I Interferon Signaling Is Required for CpG-Oligodesoxynucleotide-Induced Control ofLeishmania major, but Not for Spontaneous Cure of Subcutaneous Primary or SecondaryL. majorInfection - Schleicher, Ulrike; Liese, Jan; Justies, Nicole; Mischke, Thomas; Haeberlein, Simone; Sebald, Heidi; Kalinke, Ulrich; Weiss, Siegfried; Bogdan, Christian (Frontiers in Immunology, 2018)
We previously showed that in mice infected withLeishmania majortype I interferons (IFNs) initiate the innate immune response to the parasite at day 1 and 2 of infection. Here, we investigated which type I IFN subtypes are expressed during the first 8 weeks ofL. majorinfection and whether type I IFNs are essential for a protective immune response and clinical cure of the disease. In self-healing C57BL/6 mice infected with a high dose ofL. major, IFN-α4, IFN-α5, IFN-α11, IFN-α13, and IFN-β mRNA were most prominently regulated during the course of infection. In C57BL/6 mice deficient for IFN-β or the IFN-α/β-receptor chain 1 (IFNAR1), development of skin lesions and parasite loads in skin, draining lymph node, and spleen was indistinguishable from wild-type (WT) mice. In line with the clinical findings, C57BL/6 IFN-β-/-, IFNAR1-/-, and WT mice exhibited similar mRNA expression levels of IFN-γ, interleukin (IL)-4, IL-12, IL-13, inducible nitric oxide synthase, and arginase 1 during the acute and late phase of the infection. Also, myeloid dendritic cells from WT and IFNAR1-/-mice produced comparable amounts of IL-12p40/p70 protein upon exposure toL. major in vitro. In non-healing BALB/c WT mice, the mRNAs of IFN-α subtypes (α2, α4, α5, α6, and α9) were rapidly induced after high-doseL. majorinfection. However, genetic deletion of IFNAR1 or IFN-β did not alter the progressive course of infection seen in WT BALB/c mice. Finally, we tested whether type I IFNs and/or IL-12 are required for the prophylactic effect of CpG-oligodesoxynucleotides (ODN) in BALB/c mice. Local and systemic administration of CpG-ODN 1668 protected WT and IFN-β-/-mice equally well from progressive leishmaniasis. By contrast, the protective effect of CpG-ODN 1668 was lost in BALB/c IFNAR1-/-(despite a sustained suppression of IL-4) and in BALB/c IL-12p35-/-mice. From these data, we conclude that IFN-β and IFNAR1 signaling are dispensable for a curative immune response toL. majorin C57BL/6 mice and irrelevant for disease development in BALB/c mice, whereas IL-12 and IFN-α subtypes are essential for the disease prevention by CpG-ODNs in this mouse strain.
EVALuna2:33302

Uncertainty due to different recommendations on pneumococcal vaccination in adults Frage - Antwort - Falkenhorst, Gerhard; Bogdan, Christian (Internistische Praxis, 2018)
CRIS-Team Scopus Importer:2024-02-26

Vaccinate for Immunodeficiency Application Instructions for Vaccinations recommended by the Permanent Vaccination Commission. (II) Vaccinate for 1. Primary Immunodeficiency Diseases and 2. HIV-Infection - Ehl, Stephan; Bogdan, Christian; Niehues, Tim; Burchard, Gerd; Baumann, Ulrich; Hecht, Jane; Koch, Judith; Neubert, Jennifer; Wiese-Posselt, Miriam; Zepp, Fred (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2018)
EVALuna2:36427

Vaccinate Patients with Immunodeficiency Instructions for Use of Vaccines recommended by the Standing Vaccination Commission (IV) Vaccination for Patients with Autoimmune Diseases, other chronic inflammatory Diseases and under immunomodulatory Therapy - Wagner, Norbert; Assmus, Frauke; Arendt, Gabriele; Baum, Erika; Baumann, Ulrich; Bogdan, Christian; Burchard, Gerd; Foell, Dirk; Garbe, Edeltraut; Hecht, Jane; Mueller-Ladner, Ulf; Niehues, Tim; et al. (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2019)
CRIS-Team WoS Importer:2019-04-16

Vaccination in Patients with Immunodeficiency Instructions for use of the Vaccinations recommended by the Standing Committee on Vaccination (II) Vaccination for 1. Primary Immunodeficiency Diseases and 2. HIV Infection (vol 61, pg 1034, 2018) - Ehl, Stephan; Bogdan, Christian; Niehues, Tim; Burchard, Gerd; Baumann, Ulrich; Hecht, Jane; Koch, Judith; Neubert, Jennifer; Wiese-Posselt, Miriam; Zepp, Fred (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2018)
Erratum zu:Bundesgesundheitsbl (2018)10.1007/s00103-018-2761-8In der Originalpublikation dieses Beitrags fehlt ein Hinweis zu Lebendimpfungen bei Patienten mit Storungen im Bereich der Toll-like-Rezeptor-Signaltransduktion.Am Ende des letzten Absatzes unter Punk 3.6Defekte der ...
EVALuna2:36426

Verunsicherung durch unterschiedliche empfehlungen zur pneumokokkenimpfung erwachsener - Falkenhorst, Gerhard; Bogdan, Christian (Tägliche Praxis, 2020)
CRIS-Team Scopus Importer:2020-10-09

Whipple's disease mimicking rheumatoid arthritis can cause misdiagnosis and treatment failure - Glaser, Cornelia; Rieg, Siegbert; Wiech, Thorsten; Scholz, Christine; Endres, Dominique; Stich, Oliver; Hasselblatt, Peter; Geißdörfer, Walter; Bogdan, Christian; Serr, Annerose; Haecker, Georg; Voll, Reinhard E.; et al. (Orphanet Journal of Rare Diseases, 2017)
Whipple's disease, a rare chronic infectious disorder caused by Tropheryma whipplei, may present with predominant joint manifestations mimicking rheumatoid arthritis (RA).A retrospective single-center cohort study of seven patients was performed. Clinical symptoms were assessed by review of medical charts and Whipple's disease was diagnosed by periodic-acid-Schiff-stain and/or Tropheryma whipplei-specific polymerase-chain-reaction.Median age at disease onset was 54 years, six patients were male. Median time to diagnosis was 5 years. All patients presented with polyarthritis with a predominantly symmetric pattern. Three had erosive arthritis. Affected joints were: wrists (5/7), metacarpophalangeal joints (MCPs) (5/7), knees (5/7), proximal interphalangeal joints (PIPs) (3/7), hips (2/7), elbow (2/7), shoulder (2/7). All patients had increased C-reactive-protein concentrations, while rheumatoid factor and anti-CCP-antibodies were absent, and were initially (mis)classified as RA-patients according to EULAR/ACR-criteria (median DAS28 4.3). Six patients received antirheumatic treatment consisting of prednisone with methotrexate and/or leflunomide, three were additionally treated with at least one biologic agent (abatacept, adalimumab, etanercept, rituximab, tocilizumab). Most patients showed insufficient treatment response. In all patients Tropheryma whipplei was detected in synovial fluid by polymerase-chain-reaction; in three patients the diagnosis of Whipple's disease was further ascertained by periodic-acid-Schiff-staining. Gastrointestinal symptoms and other extra-articular manifestations were absent, mild or non-specific. Treatment was initiated with trimethoprin/sulfamethoxazole in five and doxycycline/hydroxychloroquine in two patients and had to be adapted in five patients. Finally, all patients had good treatment responses with improvement of arthritis and extra-articular manifestations.Whipple's disease is rare and can mimic rheumatoid arthritis. Especially patients with seronegative rheumatoid arthritis with a prolonged disease course and insufficient treatment response should be reevaluated for Whipple's disease.
EVALuna2:7750

Whole-genome analysis of vancomycin-resistant Enterococcus faecium causing nosocomial outbreaks suggests the occurrence of few endemic clonal lineages in Bavaria, Germany - Eisenberger, David; Tuschak, Christian; Werner, Markus; Bogdan, Christian; Bollinger, Thomas; Hossain, Hamid; Friedrich, Petra; Hussein, Ziyad; Pöhlmann, Christoph; Würstl, Benjamin; Nickel, Silke; Lehner-Reindl, Verena; et al. (Journal of Antimicrobial Chemotherapy, 2020)
OBJECTIVES: Infections caused by vancomycin-resistant Enterococcus faecium (VREfm) represent a major public health concern due to limited treatment options. Among invasive isolates of VREfm, ST117, ST80 and ST78 represent the most frequently detected STs by MLST in Germany. In this study, we investigated the genetic diversity of isolates of VREfm recovered from different nosocomial outbreaks in Bavaria, Germany, by WGS. METHODS: Between January 2018 and April 2019, 99 non-replicate isolates of VREfm originating from nosocomial outbreaks at eight different hospitals in Bavaria were investigated for genetic diversity by WGS. In detail, complex types (CTs) were identified by core-genome MLST. Furthermore, an SNP analysis was performed for all VREfm strains. RESULTS: Most of the isolates of this study (76%) belonged to three major clonal groups, which occurred in at least three hospitals: ST80/CT1065 vanB (n = 45; six hospitals), ST117/CT71 vanB (n = 11; four hospitals) and ST78/CT894like vanA (n = 19; three hospitals). Moreover, isolates of the predominant lineage ST80/CT1065 vanB showed a maximum difference of 36 SNPs as revealed by SNP analysis. CONCLUSIONS: Whole-genome analysis of VREfm causing nosocomial outbreaks suggests the occurrence of few endemic clonal lineages in Bavarian hospital settings, namely ST80/CT1065 vanB, ST117/CT71 vanB and ST78/CT894like vanA. Further studies are needed for a better understanding of the factors affecting the successful spread of the above-mentioned lineages.
CRIS-Team Scopus Importer:2020-06-02

β-(1→3)-D-glucan- and mannan-guided early termination of antifungal therapy in ICU patients: a randomized controlled study - Erb, Timothy; Mihai, Sidonia; Strauss, Richard; Herbst, Larissa; Castellanos, Ixchel; Diesch, Katharina; Cipa, Franziska; Bihlmaier, Karl; Lang, Anne-Katharina; Ganslmayer, Marion; Willam, Carsten; Bremer, Frank Felix; et al. (Antimicrobial Agents and Chemotherapy, 2023)
Candida spp. are frequently encountered in specimens from ICUs. However, most of these detections represent colonization. Nevertheless, clinical practice shows that a considerable proportion of these patients will receive antifungal therapy (AT). β-(1→3)-D-glucan (BDG) and mannan are fungal biomarkers with high negative predictive values. We aimed to examine whether biomarker-guided discontinuation of AT can reduce the antifungal consumption. Therefore, we conducted a prospective, randomized intervention study between 1 April 2019 and 31 March 2020. All adult ICU patients with a newly started systemic AT but without fungal infection were eligible for inclusion. Enrolled patients were randomized into an intervention and a control group. In both groups, serum BDG and mannan were determined on days 1 and 2 of AT. If all measurements were negative, AT was discontinued in the intervention group. The primary endpoint was antifungal use. The study was terminated after 12 months. Until this time-point, 41 patients had been included. In the intervention group (n = 19), AT was stopped in only two patients because all others showed either positive BDG and∕or mannan levels. One of these two patients developed candidemia and AT had to be restarted. There was no significant difference in the primary and secondary endpoints. In summary, the strategy of using two negative BDG and mannan levels to stop AT failed to reduce antifungal consumption in our cohort. Indeed, there will inevitably be patients with invasive candidiasis in whom necessary AT is discontinued. The optimal patient population, biomarker set, and termination criteria are critical to the success of biomarker-based termination strategies.
CRIS-Team Scopus Importer:2023-12-15
Keywords: antibiotic stewardship; antifungal therapy; biomarker; Candida infection; candidemia; candidosis; discontinuation; fungal infection